Weekly and monthly disposable water gradient contact lenses
Patent Information
- Application Number
- JP2023049850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-12-13
- Filing Date
- 2023-03-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2038-11-29
AI Technical Summary
【0008】 本発明は、その他の態様では、所望の柔軟性を備える外表面層を備えるだけではなく、約0.4マイクログラム/レンズ以下のポリクオタニウム-1取り込み率(「PU」)、並びに30サイクルの指擦り処理(すなわち、30日間のレンズケアレジームをシミュレートする)後に少なくとも10秒間の水崩壊時間(WBUT)を有することを特徴とする長時間持続する表面親水性及び湿潤性を有するコンタクトレンズを提供する。本発明のコンタクトレンズは、比較的厚く、極めて柔軟な表面層を有するため、より優れた着用快適性を提供することができる。より重要なことに、本発明のコンタクトレンズは、市場に存在する多目的レンズケア溶液と適合性があり、日常的なレンズケアレジームにおいて遭遇する過酷なレンズケア取り扱い条件(例えば指擦り、不注意によるコンタクトレンズの反転など)を耐えることができる。このため、これらは1週間又は1ヶ月用使い捨てコンタクトレンズとしての使用に好適である。
Smart Images

Figure 0007635289000066 
Figure 0007635289000067 
Figure 0007635289000068
Abstract
Description
[Technical Field]
[0001] The present invention relates generally to weekly or monthly disposable water gradient contact lenses, and more particularly to durable, high moisture, soft, abrasion-resistant silicone hydrogel contact lenses having a relatively thick hydrogel coating thereon and having a relatively high resistance to the uptake of polycationic antimicrobial agents. [Background technology]
[0002] A new class of soft contact lenses, water-gradient silicone hydrogel contact lenses, has been developed and successfully introduced to the market as the DAILIES® TOTAL 1® (Alcon) daily disposable contact lens. This new class of silicone hydrogel contact lenses is characterized by a water-gradient structural morphology that increases the water content from the core to the surface from 33% to over 80% (see U.S. Pat. No. 8,480,227). This unique design provides a highly lubricated, extremely soft, and highly water-rich lens surface, thereby providing patients with superior wearing comfort.
[0003] Such soft contact lenses can be manufactured according to the cost-effective method described in U.S. Patent No. 8,529,057. Water-gradient silicone hydrogel contact lenses can be manufactured by forming an anchoring layer on each contact lens by dipping the contact lens in a coating solution of a polyanionic polymer, followed by covalently bonding a water-soluble, highly branched hydrophilic polymer material directly to the anchoring layer during autoclaving within the lens package. The water-soluble, highly branched hydrophilic polymer material is prepared by partially reacting polyamidoamine-epichlorohydrin (PAE) with a wetting agent at various concentration ratios of PAE to wetting agent and reaction temperatures for a given reaction time that minimizes or eliminates surface defects (e.g., surface cracks) while achieving the desired lubricity of the surface gel.
[0004] Although newly developed water-gradient silicone hydrogel contact lenses can provide patients with superior wear comfort due to their extremely soft, high-moisture, and relatively thick hydrogel coating, they may not be compatible with all lens care solutions on the market. For example, due to the presence of an anchoring layer of polyanionic material, these new contact lenses may incorporate (absorb) large amounts of polycation-type antibacterial agents (e.g., polyhexamethylene biguanide, polyquaternium-1 (also known as Polyquad®), commonly found in most multipurpose lens care solutions), and therefore may be incompatible with some multipurpose lens care solutions on the market. These polycation-type antibacterial agents adsorbed by contact lenses may be released into the eye when the lenses are worn by the patient, which may cause undesirable clinical symptoms in some individuals, such as diffuse corneal staining and product intolerance. Due to incompatibility with some multipurpose lens care solutions, newly developed water-gradient silicone hydrogel contact lenses, which require near-daily cleaning and disinfection with lens care solutions, may not be suitable for use as weekly or monthly disposable contact lenses.
[0005] U.S. Patent Application Publication Nos. 2015 / 0166205 A1 and 2016 / 0326046 A1 disclose methods for reducing the tendency of polycationic antimicrobial agents to adhere and accumulate on water-gradient contact lenses by adding a step involving the use of polyamidoamine-epichlorohydrin (PAE). However, these methods have several drawbacks. For example, while these methods may reduce the tendency of polycationic antimicrobial agents to adhere and accumulate on hydrogel-coated contact lenses, they also reduce the lubricity, wettability, and / or hydrophilicity of the resulting contact lenses. Furthermore, the reduction in the adhesion and accumulation of polycationic antimicrobial agents may not be sufficient to render the contact lenses compatible with all multipurpose lens care solutions on the market. Furthermore, contact lenses obtained by these methods may not be able to withstand the finger rubbing required in lens care regimes involving multipurpose lens care solutions or inadvertent lens inversion during lens manufacturing or handling, as finger rubbing and lens inversion can damage the hydrogel coating on the contact lens, as evidenced by crack lines visible to the eye under dark field after the contact lens inverts or is rubbed between fingers.
[0006] Therefore, a need remains for weekly or monthly disposable water gradient contact lenses that are highly resistant to finger rubs yet are compatible with all lens care solutions, including multipurpose lens care solutions. Summary of the Invention [Means for solving the problem]
[0007] In some embodiments, the present invention provides contact lenses that not only have a highly desirable water gradient structural morphology, but also have a polyquaternium-1 uptake ("PU") of about 0.4 micrograms / lens or less, and long-lasting surface hydrophilicity and wettability characterized by a water-break-up time (WBUT) of at least 10 seconds after 30 cycles of finger rubbing (i.e., simulating a 30-day lens care regime) or after simulated abrasion cycling. Because the contact lenses of the present invention have a desirable water gradient structural morphology and a relatively thick, highly flexible, and highly hydrated hydrogel surface layer, they can provide superior wear comfort. More importantly, the water gradient contact lenses of the present invention are compatible with commercially available multi-purpose lens care solutions and can withstand the harsh lens care handling conditions encountered in daily lens care regimes (e.g., finger rubbing, inadvertent contact lens inversion, etc.). Therefore, they are suitable for use as weekly or monthly disposable contact lenses.
[0008] In another aspect, the present invention provides contact lenses that not only have an outer surface layer with desired flexibility, but also have long-lasting surface hydrophilicity and wettability, characterized by a polyquaternium-1 uptake ("PU") of about 0.4 micrograms / lens or less, and a water disintegration time (WBUT) of at least 10 seconds after 30 cycles of finger rubbing (i.e., simulating a 30-day lens care regime). Because the contact lenses of the present invention have a relatively thick and highly flexible surface layer, they can provide superior wear comfort. More importantly, the contact lenses of the present invention are compatible with commercially available multi-purpose lens care solutions and can withstand the harsh lens care handling conditions encountered in daily lens care regimes (e.g., finger rubbing, inadvertent contact lens inversion, etc.). Therefore, they are suitable for use as weekly or monthly disposable contact lenses.
[0009] These and other aspects of the present invention will become apparent from the following description of the presently preferred embodiments. The detailed description is merely illustrative of the invention and does not limit the scope of the invention, which is defined by the appended claims and their equivalents. As will be apparent to those skilled in the art, many variations and modifications of the present invention are possible without departing from the spirit and scope of the novel concepts of the present disclosure. [Brief explanation of the drawings]
[0010] [Figure 1] 1 shows a schematic cross-sectional view of a structural configuration of a contact lens according to a preferred embodiment of the present invention. [Figure 2] 2 shows a schematic cross-sectional view of a structural configuration of a contact lens according to another preferred embodiment of the present invention; [Figure 3] Schematic diagrams of a lens holder for performing simulated lens polishing cycling processes to determine the long-lasting lubricity and / or long-lasting wettability of contact lenses of the present invention: A-oblique view, B-top view, C-side view, D-bottom view, and E-cross-sectional view. [Figure 4] Schematic representation of a lens holder for performing nanoindentation measurements on contact lenses using an Optics11 Puima nanoindentation instrument: A - top view, B - perspective view, and C - cross section. [Figure 5] 1 shows the indentation force at an indentation depth of 400 nm as a function of bulk modulus of contact lenses as measured in the microindentation test of Example 20 using Bruker's Hysitron® BioSoft™ In-Situ Indenter. [Figure 6] 1 shows the indentation force at an indentation depth of 400 nm as a function of the bulk modulus of the contact lens as measured in the nanoindentation test of Example 42 using a nanoindentation instrument (Optics11 Puima). DETAILED DESCRIPTION OF THE INVENTION
[0011] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Generally, the terms and experimental procedures used herein are well known and commonly used in the art. These procedures use conventional methods, such as those provided in the art and various general references. Where a term is provided in the singular, the inventors also intend the plural of the same term. The terms used herein and the experimental procedures described below are well known and commonly used in the art.
[0012] As used herein, "about" means that the number referred to as "about" includes the recited number plus or minus 1 to 10% of the recited number.
[0013] "Contact lens" refers to a structure that can be placed on or in a wearer's eye. A contact lens can, but need not, correct, improve, or modify the user's vision. A contact lens can be made of any suitable material known or later developed in the art and can be a hard lens, a rigid gas permeable lens, a soft lens, or a hybrid lens.
[0014] "Hard contact lens" refers to a contact lens that contains a hard plastic (eg, polymethyl methacrylate) as the bulk (core) material.
[0015] "Rigid gas permeable contact lens" refers to a contact lens that includes a gas permeable material (e.g., a material made from fluorosilicone acrylate) as its bulk (core) material.
[0016] Soft contact lenses may be non-silicone hydrogel lenses, silicone hydrogel lenses, or silicone lenses. "Hydrogel contact lenses" refer to contact lenses comprising a non-silicone hydrogel bulk (core) material. "Silicone hydrogel contact lenses" refer to contact lenses comprising a silicone hydrogel bulk (core) material. "Silicone contact lenses" refer to contact lenses made from a cross-linked silicone material as its bulk (or core or base) material, which has a three-dimensional polymer network (i.e., polymer matrix), is water-insoluble, and can retain less than about 7.5% by weight of water when fully hydrated (preferably less than about 5% by weight, more preferably less than about 2.5% by weight, and even more preferably less than about 1% by weight).
[0017] Hybrid contact lenses have a central optic zone made from a gas permeable lens material surrounded by a peripheral zone made from silicone hydrogel or standard hydrogel lens material.
[0018] "Hydrogel" or "hydrogel material" refers to a crosslinked polymeric material that is water-insoluble but can retain at least 10% by weight of water within its three-dimensional polymer network (i.e., polymer matrix) upon full hydration.
[0019] As used herein, the term "non-silicone hydrogel" refers to a hydrogel that is theoretically free of silicone.
[0020] As used herein, the term "silicone hydrogel" refers to a hydrogel containing silicone. Silicone hydrogels are typically obtained by copolymerizing a polymerizable composition containing at least one silicone-containing vinyl monomer, or at least one silicone-containing vinyl macromer, or at least one silicone-containing prepolymer having an ethylenically unsaturated group.
[0021] As used herein, "hydrophilic" describes a material, or portion thereof, that more readily associates with water than with lipids.
[0022] "Vinyl monomer" refers to a compound that has one and only one ethylenically unsaturated group, is solvent soluble, and is polymerizable actinically or thermally.
[0023] The term "soluble" in reference to a compound or material in a solvent means that the compound or material dissolves in the solvent at room temperature (i.e., about 25±3°C) to provide a solution having a concentration of at least about 0.05% by weight.
[0024] The term "insoluble" in reference to a compound or material in a solvent means that the compound or material dissolves in the solvent at room temperature (as defined above) to give a solution having a concentration of less than 0.005% by weight.
[0025] As used herein, the term "ethylenically unsaturated group" is used broadly herein and is intended to encompass any group containing at least one >C=C< group. Exemplary ethylenically unsaturated groups include (meth)acryloyl [ka] Examples of C═C-containing groups include, but are not limited to, allyl, vinyl, styrenyl, or other C═C-containing groups.
[0026] The term "(meth)acrylamide" refers to methacrylamide and / or acrylamide.
[0027] The term "(meth)acrylate" refers to methacrylate and / or acrylate.
[0028] As used herein, "actinically" in reference to curing, crosslinking, or polymerization of a polymerizable composition, prepolymer, or material means that the curing (e.g., crosslinking and / or polymerization) is effected by actinic radiation, such as, for example, UV / visible light radiation, ionizing radiation (e.g., gamma or X-ray radiation), microwave radiation, etc. Thermal curing or actinic curing methods are well known to those skilled in the art.
[0029] As used herein, "hydrophilic vinyl monomer" refers to a vinyl monomer that, typically as a homopolymer, results in a polymer that is water-soluble or can absorb at least 10 weight percent water.
[0030] As used herein, "hydrophobic vinyl monomer" refers to a vinyl monomer that, typically as a homopolymer, results in a polymer that is water-insoluble and can absorb less than 10 percent by weight of water.
[0031] "Blending vinylic monomer" refers to a vinylic monomer that is capable of dissolving both the hydrophilic and hydrophobic polymerizable components of a polymerizable composition to form a solution.
[0032] "Acrylic monomer" refers to a vinyl monomer having only one (meth)acryloyl group.
[0033] "N-vinyl amide monomer" refers to an amide compound having a vinyl group (-CH=CH2) attached directly to the nitrogen atom of the amide group.
[0034] "Macromer" or "prepolymer" refers to a compound or polymer that contains ethylenically unsaturated groups and has a number average molecular weight greater than 700 Daltons.
[0035] As used herein, the term "vinylic crosslinker" refers to a compound having at least two ethylenically unsaturated groups. "Vinyl crosslinking agent" refers to a subclass of vinyl crosslinkers, each having a number average molecular weight of 700 daltons or less.
[0036] As used herein, the term "polymer" means a material formed by polymerizing or crosslinking one or more monomers, macromers, prepolymers, and / or combinations thereof.
[0037] As used herein, the term "molecular weight" of a polymeric material (including monomeric or macromeric materials) means number average molecular weight unless otherwise specified or unless otherwise dictated by the test conditions.
[0038] "Polysiloxane segment" means [ka] where R1' and R2' are independently C1 to C6. 10 Alkyl, C1-C4 alkyl- or C1-C4 alkoxy-substituted phenyl, C1-C 10 Fluoroalkyl, C1-C 10 Fluoroethers, C6-C 18 Aryl radical, -alk-(OC2H4) γ1 -OR o (wherein alk is a C1-C6 alkyl diradical, R ois H or a C1-C4 alkyl, and γ1 is an integer of 1 to 10), a hydroxyl group (-OH), a carboxyl group (-COOH), -NR3'R4', an amino bond of -NR3'-, an amide bond of -CONR3'-, an amide of -CONR3'R4', a urethane bond of -OCONH-, and a C1-C4 alkoxy group. 40 an organic radical, or a linear hydrophilic polymer chain (wherein R3' and R4', independently of each other, are hydrogen or C1-C 15 and the two substituents are selected from the group consisting of alkyl.
[0039] "Polysiloxane vinyl monomer" refers to a compound that contains at least one polysiloxane segment and only one ethylenically unsaturated group.
[0040] "Polysiloxane vinyl crosslinker" refers to a compound that contains at least one polysiloxane segment and at least two ethylenically unsaturated groups.
[0041] "Chain-extended polysiloxane vinyl crosslinker" refers to a compound that contains at least two ethylenically unsaturated groups and at least two polysiloxane segments, each pair of which is linked by a divalent radical.
[0042] What is "polycarbosiloxane"? [ka] where n1 is an integer of 2 or 3, and R1", R2", R3", and R4", each independently, are C1-C6 alkyl radicals (preferably methyl).
[0043] "Polycarbosiloxane vinyl monomer" refers to a compound containing at least one polycarbosiloxane segment and only one ethylenically unsaturated group.
[0044] "Polycarbosiloxane vinyl crosslinker" refers to a compound containing at least one polycarbosiloxane segment and at least two ethylenically unsaturated groups.
[0045] As used herein, the term "fluid" indicates that the material is capable of flowing like a liquid.
[0046] As used herein, the term "clear" in relation to a polymerizable composition means that the polymerizable composition is a transparent solution or liquid mixture (i.e., has a light transmittance of 85% or greater within the range of 400 to 700 nm).
[0047] The term "alkyl" refers to a monovalent radical obtained by removing a hydrogen atom from a straight- or branched-chain alkane compound. An alkyl group (radical) forms one bond with another group in an organic compound.
[0048] The terms "alkylene divalent group" or "alkylene diradical" or "alkyl diradical" refer interchangeably to the divalent radical obtained by removing one hydrogen atom from an alkyl. An alkylene divalent group forms two bonds with other groups in an organic compound.
[0049] The term "alkyl triradical" refers to a trivalent radical obtained by removing two hydrogen atoms from an alkyl. An alkyl triradical forms three bonds with other groups in organic compounds.
[0050] The terms "alkoxy" or "alkoxyl" refer to a monovalent radical obtained by removing a hydrogen atom from the hydroxyl group of a straight- or branched-chain alkyl alcohol. An alkoxy group (radical) forms one bond with one other group in an organic compound.
[0051] As used herein, unless otherwise specified, the term "amino group" refers to a primary or secondary amino group of formula -NHR', where R' is hydrogen or a C1-C 20 is an unsubstituted or substituted straight or branched chain alkyl group of the formula:
[0052] As used herein, the term "substituted" in connection with an alkyl diradical or alkyl radical means that the alkyl diradical or alkyl radical contains at least one substituent replacing one hydrogen atom of the alkyl diradical or alkyl radical and selected from the group consisting of hydroxy (-OH), carboxy (-COOH), -NH, sulfhydryl (-SH), C1-C4 alkyl, C1-C4 alkoxy, C1-C4 alkylthio (alkyl sulfide), C1-C4 acylamino, C1-C4 alkylamino, di-C1-C4 alkylamino, halogen atoms (Br or Cl), and combinations thereof.
[0053] In this application, "oxazoline" means [ka] In the formula, R 1 is hydrogen, methyl, ethyl, N-pyrrolidonylmethyl, N-pyrrolidonylethyl, N-pyrrolidonylpropyl, or -alk-(OC2H4) m3 -OR ” where alk is a C1-C4 alkyl diradical, R″ is a C1-C4 alkyl (preferably methyl), and m3 is an integer of 1 to 10 (preferably 1 to 5)).
[0054] In this application, the term "polyoxazoline" means [ka] where R 1is hydrogen, methyl, ethyl, N-pyrrolidonylmethyl, N-pyrrolidonylethyl, N-pyrrolidonylpropyl, or -alk-(OC2H4) m3 -OR ” (wherein alk is a C1-C4 alkyl diradical, R″ is a C1-C4 alkyl (preferably methyl), m3 is an integer from 1 to 10 (preferably 1 to 5), and x is an integer from 5 to 500) monovalent radical.
[0055] In this application, the term "poly(2-oxazoline-co-ethyleneimine)" means [ka] refers to a statistical copolymer or polymer segment thereof having the formula: 1 is hydrogen, methyl, ethyl, N-pyrrolidonylmethyl, N-pyrrolidonylethyl, N-pyrrolidonylpropyl, or -alk-(OC2H4) m3 -OR ” (wherein alk is a C1-C4 alkyl diradical, R" is a C1-C4 alkyl (preferably methyl), m3 is an integer from 1 to 10 (preferably 1 to 5), x is an integer from 5 to 500, and z is an integer equal to or less than x) monovalent radical. Poly(2-oxazoline-co-ethyleneimine) can be obtained by hydrolyzing polyoxazoline.
[0056] As used herein, the term "poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin" refers to a polymer obtained by reacting poly(2-oxazoline-co-ethyleneimine) with epichlorohydrin to convert all or a substantial proportion (≥90%) of the secondary amine groups of the poly(2-oxazoline-co-ethyleneimine) to azetidinium groups. Examples of poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin are disclosed in co-pending U.S. Patent Application Publication No. 2016 / 0061995 A1.
[0057] "Epichlorohydrin-functionalized polyamine" or "epichlorohydrin-functionalized polyamidoamine" refers to a polymer obtained by reacting a polyamine or polyamidoamine with epichlorohydrin to convert all or a substantial percentage of the secondary amine groups of the polyamine or polyamidoamine to azetidinium groups.
[0058] The term "polyamidoamine-epichlorohydrin" refers to an epichlorohydrin-functionalized adipic acid-diethylenetriamine copolymer.
[0059] In this application, the term "azetidinium" or "3-hydroxyazetidinium" refers to [ka] refers to a positively charged (i.e., cationic) divalent radical (or group or moiety) of
[0060] The term "thermally crosslinkable" in reference to a polymeric material or functional group means that the polymeric material or functional group is capable of undergoing a crosslinking (or coupling) reaction with another material or functional group at relatively high temperatures (about 40°C to about 140°C), while the polymeric material or functional group is not capable of undergoing the same crosslinking (or coupling) reaction with another material or functional group to a detectable extent at a temperature of about 5°C to about 15°C for a period of about 1 hour.
[0061] The term "azlactone" refers to a compound of the formula [ka] where p is 0 or 1 and independently 3 R and 4 R is C1 to C8 alkyl (preferably methyl).
[0062] The term "aziridine group" means a group of the formula [ka] where R1 is hydrogen, methyl, or ethyl.
[0063] As used herein, the term "phosphorylcholine" refers to a compound of the formula [ka] wherein n is an integer of 1 to 5, and R1, R2, and R3, each independently, are C1 to C8 alkyl or C1 to C8 hydroxyalkyl.
[0064] As used herein, the term "reactive vinyl monomer" refers to any vinyl monomer having at least one reactive functional group selected from the group consisting of a carboxyl group, a primary amino group, and a secondary amino group.
[0065] As used herein, the term "non-reactive vinyl monomer" refers to any vinyl monomer (either hydrophilic or hydrophobic) that does not contain a carboxyl group, a primary amino group, a secondary amino group, an epoxide group, an isocyanate group, an azlactone group, or an aziridine group.
[0066] A free radical initiator can be either a photoinitiator or a thermal initiator. A "photoinitiator" refers to a chemical that initiates a free radical crosslinking / polymerization reaction through the use of light. A "thermal initiator" refers to a chemical that initiates a radical crosslinking / polymerization reaction through the use of heat energy.
[0067] "Spatial confinement of actinic radiation" refers to the act or process of directing energy radiation in the form of light rays, for example, by a mask or screen, or a combination thereof, to impinge on an area having a clearly defined peripheral boundary in a spatially confined manner. Spatial confinement of UV radiation can be achieved by using a mask or screen having radiation (e.g., UV) transparent regions, radiation (e.g., UV) opaque regions surrounding the radiation transparent regions, and a projection contour that is the boundary between the radiation opaque and radiation transparent regions, as shown schematically in the drawings of U.S. Pat. Nos. 6,800,225 (FIGS. 1-11), 6,627,124 (FIGS. 1-9), 7,384,590 (FIGS. 1-6), and 7,387,759 (FIGS. 1-6). The mask or screen allows for the spatial projection of a beam of radiation (e.g., UV radiation) having a cross-sectional profile defined by the projection contour of the mask or screen. The projected beam of radiation (e.g., UV radiation) limits the radiation (e.g., UV radiation) impinging on lens formulations located on the path of the projected beam from the first molding surface to the second molding surface of the mold. The resulting contact lens comprises an anterior surface defined by the first molding surface, an opposing posterior surface defined by the second molding surface, and a lens edge defined by the cross-sectional profile of the projected UV beam (i.e., the spatial limit of the radiation). The radiation used for crosslinking is radiant energy, particularly UV radiation, gamma rays, electron beams, or heat rays, and the radiant energy is preferably in the form of a substantially parallel beam to achieve good energy limitation on the one hand and efficient use of energy on the other hand.
[0068] The specific "oxygen permeability" of the material, Dk i is the rate at which oxygen passes through the material. As used herein, the term "oxygen permeability (Dk)" in relation to a hydrogel (silicone or non-silicone) or contact lens refers to the corrected oxygen permeability (Dk) measured at about 34-35°C according to the procedure described in Example 1 of U.S. Patent Application Publication No. 2012 / 0026457 A1 and corrected for the surface resistance to oxygen flow caused by boundary layer effects.c Oxygen permeability is conventionally expressed in units of barrers, where "barrer" means [(cm 3 oxygen)(mm) / (cm 2 )(sec)(mmHg)]×10 -10 It is defined as follows.
[0069] The "oxygen transmissibility" of a lens or material, Dk / t, is the rate at which oxygen passes through a particular lens or material having an average thickness t [in mm] over the area being measured. Oxygen transmissibility is conventionally expressed in units of barrers / mm, where "barrers / mm" is [(cm 3 oxygen) / (cm 2 )(sec)(mmHg)]×10 -9 It is defined as follows.
[0070] As used herein, "ophthalmologically compatible" refers to a material, or surface of a material, that can be in intimate contact with the ocular environment for extended periods of time without significant damage to the ocular environment and without significant user discomfort.
[0071] The term "ophthalmically safe" in reference to a packaging solution for sterilizing and storing contact lenses means that contact lenses stored in the solution are safe to place directly on the eye without rinsing after autoclaving, and that the solution is safe and sufficiently comfortable for routine contact with the eye through a contact lens. An ophthalmically safe packaging solution after autoclaving has an eye-compatible tonicity and pH, and is substantially free of eye-irritating or eye-cytotoxic materials in accordance with international ISO standards and US FDA regulations.
[0072] As used herein, the term "water gradient" in relation to a contact lens means an increase in water content observed passing from the core to the surface of the contact lens, reaching a maximum water content in a region near and including the surface of the contact lens. It will be understood that the increase in water content from the core to the surface of the contact lens may be continuous and / or gradual, so long as the maximum water content is achieved in a region near and including the surface of the contact lens.
[0073] As used herein, the term "cross section" of a contact lens refers to a cross section of the lens obtained by cutting the lens with a knife or cutting tool at an angle substantially perpendicular to either the anterior or posterior surface of the lens. Those skilled in the art are aware that cross sections of contact lenses can be obtained by cutting the contact lens manually (i.e., by hand cutting) or by cutting with a cryostat microtome or lath. The resulting cross section of the contact lens can be polished using ion etching or similar techniques.
[0074] The term "modulus" or "elastic modulus" in relation to contact lenses or materials refers to the tensile modulus or Young's modulus, which is a measure of the stiffness of a contact lens or material. The modulus can be measured using a method according to the ANSI Z80.20 standard. Those skilled in the art are familiar with methods for determining the modulus of a silicone hydrogel material or contact lens. For example, all commercially available contact lenses have a reported modulus value.
[0075] The terms "surface modulus," "surface flexibility," "surface elastic modulus," "surface Young's modulus," or "surface compressibility modulus" are used interchangeably herein and refer to nanomechanical (elastic) properties measured by atomic force microscopy (AFM) on the surface of a material or contact lens cross-section in a fully hydrated state (in phosphate buffer solution, pH about 7.3±0.2) using nanoindentation techniques, as known to those skilled in the art. Jan Domke and Manfred Radmacher reported that the elastic properties of thin films can be measured with AFM (Langmuir 1998, 14, 3320-3325). AFM nanoindentation can be performed according to the experimental procedure described by Gonzalez-Meijome JM, Almeida JB and Parrafita MA in Microscopy: Science, Technology, Applications and Education, "Analysis of Surface Mechanical Properties of Unworn and Worn Silicone Hydrogel Contact Lenses Using Nanoindentation with AFM", pp. 554-559, A. Mendez-Vilas and J. Diaz (Eds.), Formatex Research Center, Badajoz, Spain (2010). It should be noted that the cross-sectional surface of the contact lens (performed by Gonzalez-Meijome JM, Almeida JB and Parrafita MA in these papers) is analyzed using AFM nanoindentation, rather than the anterior or posterior surface of the contact lens.Nanoindentation, Peakforce QNM, and Harmonic Force techniques are described in a paper by Kim Sweers et al. in Nanoscale Research Letters 2011, 6:270, entitled "Nanomechanical properties of a-synuclein amyloid fibrils: a comparative study by nanoindentation, harmonic force microscopy, and Peakforce QNM." It will also be appreciated that when surface modulus measurements are performed using an AFM across a cross-section of a fully hydrated contact lens from the anterior surface to the bulk, or from the bulk to the posterior surface (or vice versa), the surface modulus profile across the cross-section of the contact lens can be determined along the shortest line between the anterior and posterior surfaces of the cross-section of the contact lens. It will further be appreciated that, to a good approximation, any experimentally and directly measured quantity can be used to represent the surface modulus, as long as the measured quantity is proportional to the surface modulus. Alternatively, microindentation or nanoindentation techniques may be used when colloidal spheres of various sizes are used to measure the surface modulus.
[0076] As used herein, the terms "inner layer" or "bulk material" in relation to a contact lens refer interchangeably to the layer that has the three-dimensional shape of the contact lens, includes the central curved surface (dividing the contact lens into two portions, one containing the anterior surface and the other containing the posterior surface), and has a variable thickness.
[0077] As used herein, the term "external surface hydrogel layer" in relation to a contact lens means the outermost hydrogel layer on the surface of the contact lens, which consists of the anterior outer hydrogel layer and the posterior outer hydrogel layer, and which completely covers the inner layer (or lens bulk material).
[0078] As used herein, the term "front outer hydrogel layer" in relation to a contact lens means a hydrogel layer that comprises the front surface of a contact lens, that is substantially uniform in thickness (i.e., that varies by no more than about 20% from the average thickness of the layer), and that has an average thickness of at least about 0.25 μm.
[0079] As used herein, the term "posterior outer hydrogel layer" in relation to a contact lens means a hydrogel layer that comprises the posterior surface of a contact lens, that is substantially uniform in thickness (i.e., that varies by no more than about 20% from the average thickness of the layer), and that has an average thickness of at least about 0.25 μm.
[0080] As used herein, the term "transition layer" in the context of contact lenses means a layer of polymeric material located between the inner layer (or lens bulk material) and one of the anterior and posterior outer hydrogel layers. Each transition layer is substantially uniform in thickness (i.e., the thickness varies by no more than about 20% from the average thickness of that layer).
[0081] In this application, the "average thickness" of the anterior or posterior hydrogel layer or transition layer is simply referred to as the "anterior posterior hydrogel layer thickness," "posterior posterior hydrogel layer thickness," or "transition layer thickness" measured using an AFM on a cross-section of a contact lens in a specified state, e.g., fully hydrated or when fully hydrated (i.e., in phosphate buffer solution, pH about 7.3±0.2), or in a dry state (e.g., fully oven dried).
[0082] FIG. 1 schematically illustrates a preferred embodiment of a contact lens of the present invention. According to a preferred embodiment of the present invention, contact lens 100 has an anterior surface (or front curve or convex surface) 101 and an opposing posterior surface (or base curve or concave surface) 102, which rests on the cornea of the eye when worn by a user. Contact lens 100 comprises an inner (or middle) layer (or lens bulk material) 110 and anterior and posterior outer hydrogel layers 120. The inner layer 110 is the bulk material of contact lens 100 and has a three-dimensional shape closely resembling contact lens 100. The anterior and posterior outer hydrogel layers 120 are substantially uniform in thickness and are made from a hydrogel material that is substantially free of silicone (preferably completely free of silicone) and has a water content higher than that of the inner layer 110. The anterior and posterior outer hydrogel layers 120 merge at the peripheral edge 103 of contact lens 100, completely covering the inner layer 110.
[0083] 2 is a schematic illustration of a contact lens of the present invention according to another preferred embodiment. The contact lens 100 comprises an inner (or intermediate) layer (or lens bulk material) 110, anterior and posterior outer hydrogel layers 120, and two transition layers 115. Each of the two transition layers 115 is positioned between the inner layer 110 and one of the two outer hydrogel layers 120.
[0084] As used herein, the term "equilibrium water content" in relation to a contact lens or polymeric material means the amount of water (expressed as % by weight) present in the contact lens or polymeric material when fully hydrated (equilibrated) in saline (about 0.79% by weight NaCl), measured at room temperature (as defined above).
[0085] As used herein, the terms "crosslinked coating" or "hydrogel coating" or "hydrogel layer" on a contact lens are used interchangeably to refer to a crosslinked polymeric material having a three-dimensional network that can contain water when fully hydrated. The three-dimensional network of the crosslinked polymeric material can be formed by crosslinking two or more linear or branched polymers via crosslinking linkages.
[0086] As used herein, the term "water swelling coefficient" in relation to the anterior or posterior outer hydrogel layer of the present contact lenses means
number
[0087] The water-swelling rate of the outer surface hydrogel layer of a contact lens is considered to be proportional to the equilibrium water content of the outer surface hydrogel layer. The higher the water-swelling rate of the outer surface hydrogel layer, the higher the equilibrium water content of the outer surface hydrogel layer. Furthermore, the water-swelling rate of the outer surface hydrogel layer is considered to be proportional to the mesh size of the outer surface hydrogel layer, and therefore proportional to the flexibility of the outer surface hydrogel layer. The mesh size of the hydrogel is inversely proportional to the crosslinking density of the hydrogel, which in turn is proportional to the length of the crosslinked chains. The higher the water-swelling rate of the outer surface hydrogel layer, the more flexible the outer surface hydrogel layer. Therefore, the water-swelling rate can be a good indicator of both the equilibrium water content and flexibility of the outer surface hydrogel layer.
[0088] As used herein, the terms "surface compressive force at an indentation depth of 400 nm" or "indentation force at an indentation depth of 400 nm" refer to the averaged normal force at the indentation depth along the loading curve, as measured in the microindentation or nanoindentation test described in Example 1.
[0089] As used herein, the term "reduced indentation force" or "Δ(IF)" in relation to contact lenses. 400nm " means the difference between the predicted indentation force (μN) at an indentation depth of 400 nm based on the bulk modulus (MPa) of the contact lens and the measured indentation force (μN) at an indentation depth of 400 nm of the contact lens in the microindentation or nanoindentation test described in Example 1, which can be calculated by the following equation:
number
[0090] Every contact lens can have different mechanical properties at its surface, especially when the contact lens has a soft hydrogel coating thereon. The mechanical properties of the region near and including the surface of the contact lens can be characterized by measuring the surface compressive or indentation force as a function of displacement in a microindentation or nanoindentation test.
[0091] It has been found that for contact lenses that do not have any soft hydrogel coating thereon, the indentation force at a given displacement or indentation depth (e.g., 400 nm) correlates well with the bulk (Young's) modulus (i.e., there is a linear bulk modulus-indentation force relationship between bulk modulus and indentation force at an indentation depth of 400 nm), whereas for contact lenses that have a soft hydrogel coating thereon, the indentation force at 400 nm indentation depth is much less than would be predicted based on the linear bulk modulus-indentation force relationship (i.e., a decrease in indentation force at an indentation depth of 400 nm). The decrease in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), 400nm It is believed that this can be used to quantitatively characterize contact lenses having a water gradient structure. When a contact lens has a sufficiently thick (≧0.25 μm) outer surface hydrogel layer thereon, this reduces the indentation force (Δ(IF)) at an indentation depth of 400 nm by about 40% or more. 400nm ) The Δ(IF) of the water gradient contact lens 400nm The value of Δ(IF) may depend on both the flexibility and thickness of the outer surface hydrogel layer on the contact lens. 400nm ) is proportional to the flexibility and / or thickness of the outer surface hydrogel layer (or outer surface layer) of the contact lens. 400nm The larger Δ(IF) is, the softer and / or thicker the outer surface hydrogel layer (or outer surface layer) is, and the smaller the force induced on the corneal surface. 400nmcan be a good indicator of the combined effect of the flexibility and thickness of the outer surface hydrogel layer (or outer surface layer) on a water gradient contact lens.
[0092] As used herein, the term "normalized surface compressive force" or "NSCF" in relation to contact lenses means the ratio of the surface compressive force or indentation force at an indentation depth of 400 nm of a contact lens (determined in a microindentation test using a probe size of 1 mm as described in Example 1) to the modulus of elasticity of the contact lens, which has units of μN / MPa, i.e.,
number
[0093] It has been found that if a contact lens does not have an outer surface hydrogel layer thereon, it will have a normalized surface compressive force of about 14 μN / MPa or slightly higher as measured with a 1 mm colloidal probe, regardless of the bulk modulus of the contact lens. Therefore, it is believed that normalizing the surface compressive force across the modulus of the contact lens is intended to equalize the contribution of the bulk material of the contact lens to the surface compressive force. However, if a contact lens has a sufficiently thick outer surface hydrogel layer thereon, it will have a normalized surface compressive force (at an indentation depth of 400 nm) of less than about 14 μN / MPa. Δ(IF) 400nmSimilarly, it is believed that the normalized surface compressive force at an indentation depth of 400 nm can be used to qualitatively and quantitatively characterize contact lenses having a water gradient structural morphology. If a contact lens has a sufficiently thick (≧0.25 μm) outer surface hydrogel layer thereon, it will have a normalized surface compressive force (at an indentation depth of 400 nm) of about 12 μN / MPa or less. It will also be understood that the normalized surface compressive force (NSCF) at an indentation depth of 400 nm of a water gradient contact lens depends on both the flexibility and thickness of the outer surface hydrogel layer on the contact lens. The NSCF is proportional to the flexibility of the outer surface hydrogel layer (or outer surface layer) of the contact lens. The smaller the normalized surface compressive force at an indentation depth of 400 nm, the more flexible the outer surface hydrogel layer (or outer surface layer) and the smaller the force induced on the corneal surface. The NSCF is inversely proportional to the thickness of the outer surface hydrogel layer (or outer surface layer). The thicker the outer surface hydrogel layer (or outer surface layer), the smaller the normalized surface compressive force at an indentation depth of 400 nm. Therefore, the normalized surface compressive force at an indentation depth of 400 nm can be a good indicator of the combined effect of the flexibility and thickness of the outer surface hydrogel layer (or outer surface layer) on a water gradient contact lens.
[0094] As used herein, the term "Polyquaternium-1 Uptake" or "PU" in relation to contact lenses refers to the amount of Polyquaternium-1 absorbed by a contact lens as determined according to the procedure described in Example 1.
[0095] As used herein, the term "long-lasting surface hydrophilicity and wettability" in relation to contact lenses means that the contact lenses have a water break-up time (WBUT) of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling. The determination of the WBUT of contact lenses, the finger rubbing cycles, and the simulated abrasion cycling are performed according to the procedures described in Example 1.
[0096] As used herein, the term "long-lasting lubricity" in relation to contact lenses means that the contact lenses have a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling. The determination of the friction rating of the contact lenses, the finger rubbing cycles, and the simulated abrasion cycling are performed according to the procedures described in Example 1.
[0097] As used herein, the term "30 cycles of finger rubbing" or "n cycles of finger rubbing" means that a contact lens is subjected to 30 or n repeated finger rubbing procedures, which consist essentially of finger rubbing the contact lens with RENU® Multipurpose Lens Care Solution (or an equivalent, i.e., the multipurpose lens care solution disclosed in Table I of U.S. Pat. No. 5,858,937) for 20 seconds (while wearing disposable powder-free latex gloves), followed by rinsing the finger-rubbed contact lens with phosphate-buffered saline for at least 20 seconds. The 30 or n finger rubbing cycles can reasonably mimic the daily cleaning and disinfection of a 30-day or n-day lens care regime.
[0098] "UVA" refers to radiation occurring in wavelengths between 315 and 380 nanometers, "UVB" refers to radiation occurring in wavelengths between 280 and 315 nanometers, and "violet" refers to radiation occurring in wavelengths between 380 and 440 nanometers.
[0099] "UVA Transmittance" (or "UVA %T"), "UVB Transmittance" or "UVB %T", and "Violet Transmittance" or "Violet %T" are calculated using the following formulas:
number
[0100] The term "essentially wettable" in relation to silicone hydrogel contact lenses means that after the silicone hydrogel contact lenses are formed by thermally or actinically polymerizing (i.e., curing) a silicone hydrogel lens formulation, the silicone hydrogel contact lenses, without being subjected to any surface treatment, have a water break-up time (WBUT) of about 10 seconds or more and a water contact angle (WCA) with trapped air bubbles of about 80 degrees or less. cb According to the present invention, WBUT and WCA cb is measured according to the procedure described in Example 1.
[0101] As used herein, "surface modification" or "surface treatment" means that an article has been treated, either before or after formation of the article, with a surface treatment process (or surface modification process) that (1) applies a coating to the surface of the article, (2) adsorbs a chemical species to the surface of the article, (3) changes the chemical nature (e.g., electrostatic charge) of chemical groups on the surface of the article, or (4) otherwise modifies the surface properties of the article. Exemplary surface treatment processes include, but are not limited to, surface treatment with energy (e.g., plasma, electrostatic charge, irradiation, or other energy source), chemical treatment, grafting of hydrophilic vinyl monomers or macromers onto the surface of the article, mold-transfer coating process disclosed in U.S. Pat. No. 6,719,929, incorporation of wetting agents into lens formulations for producing contact lenses as suggested in U.S. Pat. Nos. 6,367,929 and 6,822,016, reinforced mold transfer coating disclosed in U.S. Pat. No. 7,858,000, and hydrophilic coatings consisting of covalent bonding or physical vapor deposition of one or more layers of one or more hydrophilic polymers onto the surface of a contact lens as disclosed in U.S. Pat. Nos. 8,147,897 and 8,409,599, and U.S. Patent Application Publication Nos. 2011 / 0134387, 2012 / 0026457, and 2013 / 0118127.
[0102] "Post-cure surface treatment," in the context of a lens bulk material or contact lens, refers to a surface treatment process that is performed after the lens bulk material or contact lens formed by curing (i.e., thermally or actinically polymerizing) a lens formulation. "Lens formulation" refers to a polymerizable composition that contains all of the polymerizable components necessary to produce a contact lens or lens bulk material as known to those skilled in the art.
[0103] An "organic solution" refers to a solution that is a homogeneous mixture of an organic solvent and one or more solutes dissolved in the organic solvent. An organic coating solution refers to an organic solution that contains at least one polymeric coating material as a solute in the solution.
[0104] "Organic solvent" is intended to mean a solvent system consisting of one or more organic solvents and no more than about 40% by weight of water, based on the weight of the solvent system, preferably no more than about 30% by weight, more preferably no more than about 20% by weight, even more preferably no more than 10% by weight, and especially no more than about 5% by weight.
[0105] The present invention broadly relates to a disposable water gradient contact lens for weekly or monthly use that has a layered structure morphology that provides a unique water gradient from the inside to the outside of the contact lens and relatively long-lasting wettability / hydrophilicity, as well as being resistant to finger abrasion and compatible with lens care solutions, including multipurpose lens care solutions. The layered structure morphology comprises an inner layer (i.e., lens bulk material) having an equilibrium water content of about 70% by weight or less, and an outer surface hydrogel layer (consisting of a front outer hydrogel layer and a rear outer hydrogel layer) that completely covers the inner layer (or lens bulk material), has an equilibrium water content at least 1.2 times (preferably at least 80% by weight) the equilibrium water content of the inner layer (or lens bulk material), and has a sufficient thickness (about 0.25 μm to about 25 μm) when fully hydrated.
[0106] According to the present invention, the outer surface hydrogel layer must not only have a relatively high water swelling rate but also a sufficient thickness to provide better wearing comfort. A relatively high water swelling rate of the outer surface hydrogel layer can ensure that the contact lens has a high equilibrium water content and a very soft surface. However, if the outer surface hydrogel layer is too thin, the outer surface hydrogel layer will be easily completely collapsed against the lens bulk material by a slight compressive force, thereby losing the advantages associated with the water gradient structural mechanism of the contact lens of the present invention. At a given high water swelling rate, it is believed that the wearing comfort provided by the contact lens of the present invention will improve as the thickness of its outer surface hydrogel layer increases, and then plateau after a certain thickness value.
[0107] The present invention solves problems present in the prior art related to the incompatibility of water gradient contact lenses with multipurpose lens care solutions and their poor finger rub resistance. It has been found that a relatively thick anchor layer (i.e., reactive base coating) of a reactive polyanionic polymer (e.g., a carboxyl-containing polyanionic polymer) on the contact lens is necessary to form a thick outer surface hydrogel layer. The thicker the anchor layer, the thicker the outer surface hydrogel layer. However, a relatively thick anchor layer results in a higher concentration of reactive groups (e.g., carboxyl groups) in the anchor layer and a higher uptake rate of polycationic antimicrobial agents present in the lens care solution. Previous attempts to reduce the uptake rate of polycationic antimicrobial agents by water gradient contact lenses have primarily relied on reducing the thickness of the anchor layer and using polyanionic materials with higher pKa values. These approaches result in an excessively thin outer surface hydrogel layer, which reduces the durability and / or lubricity of the outer surface hydrogel layer and compromises the wearing comfort provided by the resulting contact lens.
[0108] It has been found that the anchor layer and outer surface hydrogel layer of a water gradient contact lens in manufacture and / or a preformed water gradient contact lens can be treated with a small, flexible, hydrophilic charge neutralizer to convert most or most of the negatively charged groups in the water gradient contact lens to uncharged ester bonds, and simultaneously crosslink the anchor layer to enhance the durability of the outer surface hydrogel layer on the contact lens with no or minimal effect on the wettability, hydrophilicity, and lubricity of the outer surface hydrogel layer on the contact lens.
[0109] The durability of hydrogel coatings on SiHy contact lenses has also been found to be highly dependent on the processing conditions under which the underlying base coating, comprised of a polyanionic polymer, is formed. When a base coating is applied to a SiHy contact lens in a single coating step for a given coating period (e.g., 50 minutes) (i.e., by contacting it with a sole coating solution of polyanionic polymer (pH<4.5)) followed by one or more rinsing steps, the durability of the hydrogel coating formed on such a base coating can vary depending on the refractive power (i.e., center thickness) of the SiHy contact lens during coating. For example, the durability of the hydrogel coating on a coated SiHy contact lens with a refractive power of -10.0 diopters is inferior to that of a coated SiHy contact lens with a refractive power of -3.0 diopters. Increasing the coating period did not improve the variation in hydrogel coating durability depending on the refractive power (center thickness) of the contact lens. However, it has been found that when base coatings are applied onto SiHy contact lenses by contacting the lenses with one coating solution of a polyanionic polymer (having a low pH), even for a shorter coating period (e.g., 25 minutes), followed by rinsing with a buffered saline solution having a neutral or slightly basic pH, and then contacting the lenses again with another coating solution of a polyanionic polymer (having a low pH) for a shorter period (e.g., 25 minutes), the durability of the hydrogel coatings formed on such base coatings can be significantly improved and does not vary with the optical power (i.e., central thickness) of the SiHy contact lenses being coated.
[0110] Furthermore, it has been found that the PU of a coated SiHy contact lens having a hydrogel coating thereon is highly dependent on the pH and / or salt concentration (i.e., ionic strength) of the buffered saline solution used to rinse the treated SiHy contact lens having a base coating (of a polyanionic polymer) thereon prior to forming the hydrogel coating on the base coating. A lower PU can be achieved by using a rinse solution having a higher pH and / or higher ionic strength (higher salt concentration). Combined with the discovery described above regarding how to significantly improve the durability of hydrogel coatings on water gradient contact lenses, this discovery may enable the production of water gradient contact lenses with durable hydrogel coatings and minimized PU.
[0111] The present invention provides water gradient contact lenses that are compatible with multipurpose lens care solutions and resistant to finger abrasion, making them suitable for use as weekly or monthly disposable contact lenses. The contact lenses of the present invention have a desirable water gradient structural morphology and a relatively thick, highly flexible, and highly hydrated hydrogel surface layer, which can provide superior wearing comfort.
[0112] The present invention, in one aspect, provides a polyquaternium-1 uptake ("PU") of about 0.40 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less) and a PU of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, and even more preferably at least 17.5 seconds) after 30 cycles of finger rubbing or simulated abrasion cycling. and / or long-lasting surface hydrophilicity and wettability characterized by a water disintegration time of at least about 10 seconds, and most preferably at least 20 seconds, and / or long-lasting lubricity characterized by a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less), wherein the contact lens comprises an anterior surface and an opposite posterior surface, and a layered structural morphology comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer, the inner layer having a first equilibrium water content of about 70% by weight or less. and Independent front and rear outer hydrogel layers between about 0.25 μm and about 25 μm thick and and a second equilibrium water content higher than the first equilibrium water content, and the independent front and rear outer hydrogel layers have a water swelling rate of at least 140% (preferably at least 170%, more preferably at least 200%, even more preferably at least 250%, and most preferably at least 300%). Preferably, the contact lens is substantially free (i.e., less than three), or preferably free, of surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0113] In another aspect, the present invention provides a lens-like ointment comprising a polyquaternium-1 uptake ("PU") of about 0.40 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less), and a long-lasting surface hydrophilicity and wettability characterized by a water disintegration time of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, even more preferably at least 17.5 seconds, and most preferably at least 20 seconds) after 30 cycles of finger rubbing or simulated abrasion cycling; and / or a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less), and a water content gradient from the inside to the outside of the contact lens, the contact lens comprising a lens bulk material completely coated with an outer surface hydrogel layer having a thickness of about 0.25 μm to about 25 μm as measured by atomic force microscopy across a cross section from the posterior surface to the anterior surface of the contact lens in a fully hydrated state, the lens bulk material having a first equilibrium water content of about 70 wt% or less, and the outer surface hydrogel layer having a second equilibrium water content that is at least 1.2 times the first equilibrium water content and is at least 80 wt%. Preferably, the contact lens is substantially free (i.e., less than three), or preferably free, of surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0114] In a further aspect, the present invention provides a lens having a polyquaternium-1 uptake ("PU") of about 0.40 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less) on the anterior surface and the opposite posterior surface, and a polyquaternium-1 uptake ("PU") of about 0.40 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less) for at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, and even more preferably at least 17 seconds) after 30 cycles of finger rubbing or simulated abrasion cycling. and a structural configuration characterized by a cross-sectional surface-modulus profile along a shortest line between the anterior and posterior surfaces of the contact lens, comprising an anterior-lateral zone including and proximal to the anterior surface, an inner zone including and peripheral to the central portion of the shortest line, and a posterior-lateral zone including and proximal to the posterior surface, wherein the anterior-lateral zone has an average anterior surface modulus (
number
number
number
number
[0115] In another further aspect, the present invention provides a lens having a normalized surface compressive force at an indentation depth of 400 nm using a 1 mm microindentation probe of about 12 μN / MPa or less (preferably about 10 μN / MPa or less, more preferably about 8 μN / MPa or less, even more preferably about 6 μN / MPa or less, and most preferably about 4 μN / MPa or less), a polyquaternium-1 uptake ("PU") of about 0.4 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less), and after 30 cycles of finger rubbing or simulated finger rubbing. and / or long-lasting lubricity characterized by a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less) after abrasion cycling treatment, the contact lens comprising an anterior surface and an opposite posterior surface, and a layered structural morphology comprising, in the direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer. Preferably, the contact lens is substantially free (i.e., less than three), or preferably free, of surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0116] In a still further aspect, the present invention provides a method for producing a lens with a normalized surface compressive force at an indentation depth of 400 nm of about 12 μN / MPa or less (preferably about 10 μN / MPa or less, more preferably about 8 μN / MPa or less, even more preferably about 6 μN / MPa or less, and most preferably about 4 μN / MPa or less) using a 1 mm microindentation probe, and a polyquaternium-1 uptake rate ("PU" or less) of about 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less). "), and long-lasting surface hydrophilicity and wettability characterized by a water disintegration time of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, even more preferably at least 17.5 seconds, and most preferably at least 20 seconds) after 30 cycles of finger rubbing or simulated abrasion cycling, and / or long-lasting lubricity characterized by a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less), wherein the contact lens comprises a lens bulk material that is a polymeric material.
[0117] In yet another further aspect, the present invention provides a lens having a reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF)400 nm, of about 50% or more (preferably about 55% or more, more preferably about 60% or more, even more preferably about 65% or more, and most preferably about 70% or more), and a polyquaternium-1 uptake ("PU") of about 0.4 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less), after 30 cycles of finger rubbing or simulated abrasion cycling. and / or long-lasting surface hydrophilicity and wettability characterized by a water disintegration time of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, even more preferably at least 17.5 seconds, and most preferably at least 20 seconds), and / or long-lasting lubricity characterized by a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less), wherein the contact lens comprises an anterior surface and an opposite posterior surface, and a layered structural morphology comprising, in the direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer. Preferably, the contact lens is substantially free (i.e., less than three), or preferably free, of surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0118] In yet another further aspect, the present invention provides a method for producing a polymeric nanoparticle having a reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), of about 40% or more (preferably about 50% or more, more preferably about 55% or more, even more preferably about 60% or more, and most preferably about 65% or more). 400nmand a polyquaternium-1 uptake ("PU") of about 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less); and long-lasting surface hydrophilicity and wettability characterized by a water disintegration time of at least 10 seconds (preferably at least 12.5 seconds, more preferably at least 15 seconds, even more preferably at least 17.5 seconds, and most preferably at least 20 seconds) after 30 cycles of finger rubbing or simulated abrasion cycling; and / or long-lasting lubricity characterized by a friction rating of 2.0 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less), wherein the contact lens comprises a lens bulk material that is a polymeric material.
[0119] When the reduction in indentation force of a contact lens is determined in a nanoindentation test by using an Optics11 Piuma and a Piuma probe with a tip radius of about 9.0 μm, the reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF) 400nm teeth,
number
[0120] The reduction in indentation force of a contact lens is determined by microindentation testing using a Bruker Hysitron® BioSoft™ In-Situ Indenter and a 1 mm hemispherical borosilicate glass probe, where the reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), is 400nm teeth,
number
[0121] According to all of the various aspects of the present invention, the inner layer or bulk material of the contact lenses of the present invention can be derived directly from a preformed contact lens. The preformed contact lens can be any contact lens that has not undergone any surface treatment after being manufactured according to any lens manufacturing process, any plasma-treated contact lens, or any commercially available contact lens, as long as it does not have a water gradient structure. Those skilled in the art are familiar with methods for manufacturing preformed contact lenses. Those skilled in the art are familiar with methods for manufacturing preformed contact lenses. For example, preformed contact lenses can be manufactured in a conventional "spin-casting mold" as described, for example, in U.S. Pat. No. 3,408,429, or by a static full-cast molding process as described in U.S. Pat. Nos. 4,347,198, 5,508,317, 5,583,463, 5,789,464, and 5,849,810, or by lathe-cutting buttons of polymeric material used in manufacturing customized contact lenses. In cast molding, a lens formulation is typically dispensed into a mold and cured (ie, polymerized and / or crosslinked) in the mold to produce a contact lens.
[0122] Lens molds for producing contact lenses are well known to those skilled in the art and are used, for example, in cast molding or spin casting. For example, a mold (for cast molding) generally comprises at least two mold sections (or portions) or mold halves, i.e., a first and a second mold half. The first mold half defines a first molding (or optical) surface, and the second mold half defines a second molding (or optical) surface. The first and second mold halves are configured to receive each other, thereby forming a lens-forming cavity between the first and second molding surfaces. The molding surfaces of the mold halves are the cavity-forming surfaces of the mold and are in direct contact with the lens-forming material.
[0123] Methods for manufacturing mold sections for cast molding contact lenses are generally known to those skilled in the art. The process of the present invention is not limited to any particular mold formation method. Indeed, any mold formation method may be used with the present invention. The first and second mold halves can be formed by a variety of techniques, such as injection molding or lathe cutting. Examples of suitable processes for forming mold halves are disclosed in U.S. Patent Nos. 4,444,711, 4,460,534, 5,843,346, and 5,894,002.
[0124] To manufacture molds for contact lenses, virtually any material known in the art for mold manufacturing can be used. For example, polymeric materials such as polyethylene, polypropylene, polystyrene, PMMA, Topas® COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene manufactured by Ticona GmbH, Frankfurt, Germany and Summit, New Jersey) can be used. Other materials that allow ultraviolet light to pass through, such as quartz glass and sapphire, can also be used.
[0125] In a preferred embodiment, a reusable mold is used in which the lens-forming composition is actinically cured under the spatial confinement of actinic radiation to form a contact lens. Examples of preferred reusable molds are those disclosed in U.S. Patent Nos. 6,627,124, 6,800,225, 7,384,590, and 7,387,759. Reusable molds can be fabricated from fused silica, sapphire, CaF2, cyclic olefin copolymers (e.g., Topas® COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene) from Ticona GmbH (Frankfurt, Germany and Summit, New Jersey), Zeonex® and Zeonor® from Zeon Chemicals LP (Louisville, KY)), polymethyl methacrylate (PMMA), polyoxymethylene from DuPont (Delrin), Ultem® (polyetherimide) from GEPlastics, PrimoSpire®, and the like.
[0126] According to the present invention, the polymerizable composition can be introduced (dispensed) into the cavity formed by the mold by any known method.
[0127] After the polymerizable composition is dispensed into the mold, it is polymerized to produce a contact lens. Crosslinking may be initiated thermally or actinically, preferably by exposing the lens-forming composition in the mold to spatial confinement of actinic radiation to crosslink the polymerizable components in the polymerizable composition.
[0128] Opening the mould so that the moulded article can be removed from it may be done in a manner known per se.
[0129] The molded contact lenses may be subjected to lens extraction to remove unpolymerized polymerizable components. The extraction solvent may be any solvent known to those skilled in the art. Examples of suitable extraction solvents are described below.
[0130] In a preferred embodiment, the preformed contact lens is a hard contact lens comprising a hard plastic material as the bulk material of the lens. Preferably, the hard plastic material is crosslinked polymethyl acrylate. Those skilled in the art are familiar with methods for producing hard plastic materials comprising crosslinked polymethyl methacrylate.
[0131] In another preferred embodiment, the preformed contact lens is a rigid gas permeable contact lens.Those skilled in the art know how to make rigid gas permeable contact lenses.
[0132] In another preferred embodiment, the preformed contact lens is a hybrid contact lens having a central optic zone made from a rigid gas permeable lens material surrounded by a peripheral zone made from a hydrogel material.
[0133] In another preferred embodiment, the preformed contact lens is a soft silicone contact lens, which comprises crosslinked silicone material as the bulk material of the lens.Useful crosslinked silicone materials include, but are not limited to, crosslinked polysiloxane, silicone elastomer, silicone rubber, etc., obtained by crosslinking silicone composition by any known method.Silicone contact lens can be prepared by any conventional technique known to those skilled in the art (for example, lathe cutting method, spin casting method, cast molding method, etc.).
[0134] In another preferred embodiment, the preformed contact lenses are non-silicone hydrogel contact lenses (or so-called conventional hydrogel contact lenses).
[0135] Preformed non-silicone hydrogel contact lenses may be any commercially available non-silicone hydrogel contact lens or may be manufactured by any known method. For example, non-silicone hydrogel lens formulations for manufacturing preformed non-silicone hydrogel contact lenses, for cast molding or spin casting, or for manufacturing rods used in lathe cutting of contact lenses typically contain (1) (a) at least one hydrophilic vinyl monomer (e.g., hydroxyethyl methacrylate, glycerol methacrylate, N-vinylpyrrolidone, or a combination thereof), and (b) a crosslinker, a hydrophobic vinyl monomer, a lubricant (or a so-called internal wetting agent incorporated into the lens formulation), a free radical initiator (photoinitiator or thermal initiator), a UV-absorbing vinyl monomer, a high-energy visible light ("HEVL")-absorbing vinyl monomer, a visibility tinting agent, a fluoropolymer ... or (2) an aqueous solution comprising one or more water-soluble prepolymers and at least one component selected from the group consisting of a hydrophilic vinyl monomer, a crosslinker, a hydrophobic vinyl monomer, a lubricant (or so-called internal wetting agent incorporated into the lens formulation), a free-radical initiator (photoinitiator or thermal initiator), a UV-absorbing vinyl monomer, an HEVL-absorbing vinyl monomer, a visibility colorant (e.g., a reactive dye, a polymerizable dye, a pigment, or a mixture thereof), an antimicrobial agent (e.g., preferably silver nanoparticles), a bioactive agent, and combinations thereof. The resulting pre-formed hydrogel contact lens can then be subjected to extraction with an extraction solvent to remove unpolymerized components from the resulting lens, and a hydration process, as is well known to those skilled in the art. It will be appreciated that the presence of a lubricant in a hydrogel lens formulation may improve the lubricity of a preformed hydrogel contact lens compared to the lubricity of a control preformed hydrogel contact lens obtained from a control hydrogel lens formulation that does not contain a lubricant.
[0136] Examples of water-soluble prepolymers include water-soluble crosslinkable poly(vinyl alcohol) prepolymers described in U.S. Pat. Nos. 5,583,163 and 6,303,687, water-soluble vinyl-terminated polyurethane prepolymers described in U.S. Pat. No. 6,995,192, polyvinyl alcohol, polyethyleneimine, or polyvinylamine derivatives disclosed in U.S. Pat. No. 5,849,841, water-soluble crosslinkable polyurea prepolymers, crosslinkable polyacrylamides described in U.S. Pat. Nos. 6,479,587 and 7,977,430, vinyl lactams, MMA, and comonomers disclosed in U.S. Pat. No. 5,712,356, and the like. crosslinkable statistical copolymers of vinyl lactam, vinyl acetate, and vinyl alcohol disclosed in U.S. Pat. No. 5,665,840; polyether-polyester copolymers containing crosslinkable side chains disclosed in U.S. Pat. No. 6,492,478; branched polyalkylene glycol-urethane prepolymers disclosed in U.S. Pat. No. 6,165,408; polyalkylene glycol-tetra(meth)acrylate prepolymers disclosed in U.S. Pat. No. 6,221,303; and crosslinkable polyallylamine gluconolactone prepolymers disclosed in U.S. Pat. No. 6,472,489.
[0137] Numerous non-silicone hydrogel lens formulations have been described in numerous patents and patent applications published as of the filing date of this application and are used to manufacture commercially available non-silicone hydrogel contact lenses. Examples of commercially available non-silicone hydrogel contact lenses include, but are not limited to, alfafilcon A, acofilcon A, deltafilcon A, etafilcon A, focofilcon A, helfilcon A, helfilcon B, hilafilcon B, hioxifilcon A, hioxifilcon B, hioxifilcon D, methafilcon A, methafilcon B, nelfilcon A, nesofilcon A, ocufilcon A, ocufilcon B, ocufilcon C, ocufilcon D, omafilcon A, phemfilcon A, polymacon, samfilcon A, telfilcon A, tetrafilcon A, and vifilcon A.
[0138] In a preferred embodiment, the inner layer is comprised of a non-silicone hydrogel material comprising at least 50 mole percent repeat units of at least one hydroxyl-containing vinyl monomer, preferably selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, N-2-hydroxyethyl (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, vinyl alcohol, allyl alcohol, and combinations thereof, more preferably selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and vinyl alcohol. The mole percentage of repeat units can be calculated based on the non-silicone hydrogel lens formulation for producing the non-silicone hydrogel contact lens.
[0139] In another preferred embodiment, the preformed contact lenses are non-silicone hydrogel contact lenses, preferably naturally wettable silicone hydrogel contact lenses.
[0140] Preformed silicone hydrogel contact lenses may be any commercially available silicone hydrogel contact lens or may be manufactured by any known method. For example, SiHy lens formulations for producing preformed silicone hydrogel (SiHy) contact lenses, for casting or spin-casting, or for manufacturing SiHy rods used in lathe-cutting contact lenses, generally contain at least one component selected from the group consisting of silicone-containing vinyl monomers, silicone-containing vinyl crosslinkers, silicone-containing prepolymers, hydrophilic vinyl monomers, hydrophobic vinyl monomers, non-silicone vinyl crosslinkers, free-radical initiators (photoinitiators or thermal initiators), silicone-containing prepolymers, and combinations thereof, as known to those skilled in the art. The resulting preformed SiHy contact lenses can then be subjected to extraction with an extraction solvent to remove unpolymerized components from the resulting lenses, and a hydration process, as known to those skilled in the art. Furthermore, the preformed SiHy contact lenses may be colored contact lenses (i.e., SiHy contact lenses having at least one color pattern printed thereon, as known to those skilled in the art).
[0141] According to the present invention, silicone-containing vinyl monomer can be any silicone-containing vinyl monomer known to those skilled in the art.Preferred examples of silicone-containing vinyl monomer include but are not limited to the vinyl monomer that each has bis(trialkylsilyloxy) alkylsilyl group or tris(trialkylsilyloxy) silyl group, polysiloxane vinyl monomer, polycarbosiloxane vinyl monomer, 3-methacryloxypropylpentamethyldisiloxane, t-butyldimethylsiloxyethyl vinyl carbonate, trimethylsilylethyl vinyl carbonate, and trimethylsilylmethyl vinyl carbonate, and combinations thereof.
[0142] Examples of preferred vinyl monomers each having a bis(trialkylsilyloxy)alkylsilyl group or a tris(trialkylsilyloxy)silyl group include tris(trimethylsilyloxy)silylpropyl(meth)acrylate, [3-(meth)acryloxy-2-hydroxypropyloxy]propylbis(trimethylsiloxy)methylsilane, [3-(meth)acryloxy-2-hydroxypropyloxy]propylbis(trimethylsiloxy)butylsilane, 3-(meth)acryloxy-2-(2-hydroxyethoxy) ... N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl)-2-methylacrylamide, N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl)(meth)acrylamide, N-[tris(dimethylpropylsiloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylphenylsiloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylethylsiloxy)silylpropyl]-(meth)acrylamide N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl](meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl](meth)acrylamide, N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl](meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N-2-(meth)acryloxyethyl-O-(methyl-bis-trimethylsilyl)ethyl
[0033] Examples of suitable silyl compounds include, but are not limited to, 3-(trimethylsiloxy-3-propyl)silyl carbamate, 3-(trimethylsilyl)propyl vinyl carbonate, 3-(vinylcarbonylthio)propyl-tris(trimethyl-siloxy)silane, 3-[tris(trimethylsiloxy)silyl]propyl vinyl carbamate, 3-[tris(trimethylsiloxy)silyl]propyl allyl carbamate, 3-[tris(trimethylsiloxy)silyl]propyl vinyl carbonate, those disclosed in U.S. Pat. Nos. 9,097,840, 9,103,965, and 9,475,827, and mixtures thereof. The preferred silicone-containing vinyl monomers described above can be obtained from commercial sources or can be prepared according to the procedures described in U.S. Pat. Nos. 7,214,809, 8,475,529, 8,658,748, 9,097,840, 9,103,965, and 9,475,827.
[0143] Examples of preferred polysiloxane vinyl monomers include, but are not limited to, mono-(meth)acryloyl-terminated monoalkyl-terminated polysiloxanes of formula (I), such as α-(meth)acryloxypropyl-terminated ω-butyl (or ω-methyl)-terminated polydimethylsiloxane, α-(meth)acryloxy-2-hydroxypropyloxypropyl-terminated ω-butyl (or ω-methyl)-terminated polydimethylsiloxane, α-(2-hydroxypropyl-methacryloxypropyl) ... propyl)-ω-butyl-decamethylpentasiloxane, α-[3-(meth)acryloxyethoxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxy-propyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxyisopropyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3 -(meth)acryloxybutyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxyethylamino-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxypropylamino-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxypropylamino-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloxybutylamino-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane having an α-(meth)acryloxy(polyethyleneoxy)-2-hydroxypropyloxypropyl] end and an ω-butyl (or ω-methyl) end, polydimethylsiloxane having an α-(meth)acryloxy-2-hydroxypropyloxy-ethoxypropyl] end and an ω-butyl (or ω-methyl) end, polydimethylsiloxane having an α-(meth)acryloxy-2-hydroxypropyloxy-ethoxypropyl] end and an ω-butyl (or ω-methyl) end, polydimethylsiloxane having an α-(meth)acryloxy-2-hydroxypropyl-N-ethylaminopropyl] end and an ω-butyl (or ω-methyl) end,α-[(meth)acryloxy-2-hydroxypropyl-aminopropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[(meth)acryloxy-2-hydroxypropyloxy-(polyethyleneoxy)propyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-(meth)acryloylamidopropyloxypropyl terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-N-methyl-(meth)acryloylamidopropyloxypropyl terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acrylamidoethoxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acrylamidopropyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acrylamidoisopropyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acrylamidoisopropyloxy-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(meth)acryloylamido-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(N-methyl-(meth)acryloylamido)-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, α-[3-(N-methyl-(meth)acryloylamido)-2-hydroxypropyloxypropyl] terminated ω-butyl (or ω-methyl) polydimethylsiloxane, N-methyl-N'-(propyltetra(dimethylsiloxy)dimethylbutylsilane)(meth)acryloyl acrylamidopropyl tetra(dimethylsiloxy)dimethylbutylsilane) (meth)acrylamide, N-(2,3-dihydroxypropane)-N'-(propyltetra(dimethylsiloxy)dimethylbutylsilane) (meth)acryloylamide propyl tetra(dimethylsiloxy)dimethylbutylsilane, monovinyl carbonate terminated monoalkyl terminated polydimethylsiloxane, monovinyl carbamate terminated monoalkyl terminated polydimethylsiloxane, those disclosed in U.S. Pat. Nos. 9,097,840 and 9,103,965, and mixtures thereof. Preferred polysiloxane vinyl monomers include, but are not limited to:They can be obtained from commercial suppliers (e.g., Shin-Etsu Chemical Co., Ltd., Gelest, etc.), or can be prepared according to the procedures described in patents such as U.S. Pat. Nos. 6,867,245, 8,415,405, 8,475,529, 8,614,261, and 9,217,813, or based on coupling reactions well known to those skilled in the art, by reacting a hydroxyalkyl (meth)acrylate or (meth)acrylamide or (meth)acryloxypolyethylene glycol with a monoepoxypropyloxypropyl-terminated polydimethylsiloxane, by reacting glycidyl (meth)acrylate with a monocarbinol-terminated polydimethylsiloxane, a monoaminopropyl-terminated polydimethylsiloxane, or a monoethylaminopropyl-terminated polydimethylsiloxane, or by reacting isocyanatoethyl (meth)acrylate with a monocarbinol-terminated polydimethylsiloxane.
[0144] Any polycarbosiloxane vinyl monomer can be used in the present invention. Examples of preferred polycarbosiloxane vinyl monomers include, but are not limited to, those disclosed in U.S. Patent Nos. 7,915,323 and 8,420,711, and U.S. Patent Application Publication Nos. 2012 / 244088A1 and 2012 / 245249A1.
[0145] Any suitable silicone-containing vinyl crosslinker can be used in the present invention. Examples of preferred silicone-containing vinyl crosslinkers include, but are not limited to, polysiloxane vinyl crosslinkers, polycarbosiloxane vinyl crosslinkers, and combinations thereof.
[0146] Any suitable polysiloxane vinyl crosslinker can be used in the present invention. Examples of preferred polysiloxane vinyl crosslinkers include di-(meth)acryloyl-terminated polydimethylsiloxane, di-vinyl carbonate-terminated polydimethylsiloxane, di-vinyl carbamate-terminated polydimethylsiloxane, N,N,N',N'-tetrakis(3-methacryloxy-2-hydroxypropyl)-α,ω-bis-3-aminopropyl-polydimethylsiloxane, Macromer A, Macromer B, and Macromer B described in U.S. Pat. No. 5,760,100. Polysiloxane-containing macromers selected from the group consisting of Macromer C and Macromer D, U.S. Pat. Nos. 4,136,250, 4,153,641, 4,182,822, 4,189,546, 4,343,927, 4,254,248, 4,355,147, 4,276,402, 4,327,203, 4,341,889, 4,486,577, and 4,543,398 Specification, Specification No. 4605712, Specification No. 4661575, Specification No. 4684538, Specification No. 4703097, Specification No. 4833218, Specification No. 4837289, Specification No. 4954586, Specification No. Specification No. 4954587, Specification No. 5010141, Specification No. 5034461, Specification No. 5070170, Specification No. 5079319, Specification No. 5039761, Specification No. 5346946, Specification No. 535899. and polysiloxane-containing macromers disclosed in U.S. Patent Nos. 5, 5,387,632, 5,416,132, 5,451,617, 5,486,579, 5,962,548, 5,981,675, 6,039,913, and 6,762,264; and polysiloxane-containing macromers disclosed in U.S. Patent Nos. 4,259,467, 4,260,725, and 4,261,875.
[0147] Examples of preferred di-(meth)acryloyloxy-terminated polysiloxane vinyl crosslinkers include the reaction product of glycidyl methacrylate with a di-amino-terminated polydimethylsiloxane, the reaction product of glycidyl methacrylate with a di-hydroxyl-terminated polydimethylsiloxane, the reaction product of isocyantoethyl (meth)acrylate with a di-hydroxyl-terminated polydimethylsiloxane, and the monovalent C4-C6 alkyl acrylates each having one methyl substituent and two to six hydroxyl groups as disclosed in U.S. Pat. No. 1,008,1697. 40di-(meth)acryloyloxy-terminated polysiloxane vinyl crosslinkers each having hydrophilized siloxane units with organic radical substituents; chain-extended polysiloxabe vinyl crosslinkers as disclosed in U.S. Patent Application Publication Nos. 201008843A1 and 20120088844A1; U.S. Patent Nos. 5,034,461, 5,416,132, 5,449,729, 5,760,100, 7,423,074, and 8,529,057; Chain-extended polysiloxane vinyl crosslinkers described in the specification, chain-extended polysiloxane vinyl crosslinkers described in U.S. Patent Application Publication No. 2018-0100053, chain-extended polysiloxane vinyl crosslinkers described in U.S. Patent Application Publication No. 2018-0100038, chain-extended polysiloxane vinyl crosslinkers described in U.S. Patent No. 8,993,651, α,ω-bis[3-(meth)acrylamidopropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropyl] terminated polydimethylsiloxane, Dimethylsiloxane, α,ω-bis[3-(meth)acryloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyethoxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxy-isopropyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidoethoxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidopropyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidoisopropyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidobutyloxy-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyethylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[(meth)acrylamidoethylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidopropylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidobutylamino-2-hydroxypropyloxypropyl] terminated polydimethylsiloxane Examples of the hydroxypropyl ester include, but are not limited to, α,ω-bis[(meth)acryloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyl-N-ethylaminopropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyl-aminopropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyloxy-(polyethyleneoxy)propyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-ethoxypropyl]-terminated polydimethylsiloxane, and α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-(polyethyleneoxy)propyl]-terminated polydimethylsiloxane.
[0148] Any polycarbosiloxane vinyl crosslinker can be used in the present invention. Examples of preferred polycarbosiloxane vinyl crosslinkers include, but are not limited to, those disclosed in U.S. Patent Nos. 7,915,323 and 8,420,711, and U.S. Patent Application Publication Nos. 2012 / 0244088 and 2012 / 0245249.
[0149] Any hydrophilic vinyl monomer can be used in the present invention. Examples of preferred hydrophilic vinyl monomers include alkyl(meth)acrylamides (described below), hydroxyl-containing acrylic monomers (described below), amino-containing acrylic monomers (described below), carboxyl-containing acrylic monomers (described below), N-vinylamide monomers (described below), methylene-containing pyrrolidone monomers (i.e., pyrrolidone derivatives each having a methylene group bonded to the pyrrolidone ring at the 3- or 5-position) (described below), acrylic monomers having C1-C4 alkoxyethoxy groups (described below), vinyl ether monomers (described below), allyl ether monomers (described below), phosphorylcholine-containing vinyl monomers (described below), N-2-hydroxyethyl vinyl carbamate, N-carboxyvinyl-β-alanine (VINAL), N-carboxyvinyl-α-alanine, and combinations thereof.
[0150] Examples of alkyl(meth)acrylamides include, but are not limited to, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-3-methoxypropyl(meth)acrylamide, and combinations thereof.
[0151] Examples of hydroxyl-containing acrylic monomers include, but are not limited to, N-2-hydroxylethyl (meth)acrylamide, N,N-bis(hydroxyethyl) (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, glycerol methacrylate (GMA), di(ethylene glycol) (meth)acrylate, tri(ethylene glycol) (meth)acrylate, tetra(ethylene glycol) (meth)acrylate, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, poly(ethylene glycol)ethyl (meth)acrylamide having a number average molecular weight of up to 1500, and combinations thereof.
[0152] Examples of amino-containing acrylic monomers include, but are not limited to, N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-2-dimethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, N-3-dimethylaminopropyl(meth)acrylamide, 2-aminoethyl(meth)acrylate, 2-methylaminoethyl(meth)acrylate, 2-ethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 3-methylaminopropyl(meth)acrylate, 3-ethylaminopropyl(meth)acrylate, 3-amino-2-hydroxypropyl(meth)acrylate, trimethylammonium 2-hydroxypropyl(meth)acrylate hydrochloride, dimethylaminoethyl(meth)acrylate, and combinations thereof.
[0153] Examples of carboxyl-containing acrylic monomers include, but are not limited to, 2-(meth)acrylamidoglycolic acid, (meth)acrylic acid, ethylacrylic acid, and combinations thereof.
[0154] Examples of preferred N-vinylamide monomers include N-vinylpyrrolidone (also known as N-vinyl-2-pyrrolidone), N-vinyl-3-methyl-2-pyrrolidone, N-vinyl-4-methyl-2-pyrrolidone, N-vinyl-5-methyl-2-pyrrolidone, N-vinyl-6-methyl-2-pyrrolidone, N-vinyl-3-ethyl-2-pyrrolidone, N-vinyl-4,5-dimethyl-2-pyrrolidone, N-vinyl-5,5-dimethyl-2-pyrrolidone, N-vinyl-3,3,5-trimethyl-2-pyrrolidone, N-vinylpiperidone (also known as N-vinyl-2-piperidone), N-vinyl-3-methyl-2-piperidone, N-vinyl-4-methyl-2-piperidone, N-vinyl-5-methyl-2-piperidone, N-vinyl-6-methyl-2-piperidone, N-vinyl-6-ethyl-2-piperidone, and N-vinyl- These include, but are not limited to, 3,5-dimethyl-2-piperidone, N-vinyl-4,4-dimethyl-2-piperidone, N-vinylcaprolactam (also known as N-vinyl-2-caprolactam), N-vinyl-3-methyl-2-caprolactam, N-vinyl-4-methyl-2-caprolactam, N-vinyl-7-methyl-2-caprolactam, N-vinyl-7-ethyl-2-caprolactam, N-vinyl-3,5-dimethyl-2-caprolactam, N-vinyl-4,6-dimethyl-2-caprolactam, N-vinyl-3,5,7-trimethyl-2-caprolactam, N-vinyl-N-methylacetamide, N-vinylformamide, N-vinylacetamide, N-vinylisopropylamide, N-vinyl-N-ethylacetamide, N-vinyl-N-ethylformamide, and mixtures thereof. Preferably, the N-vinylamide monomer is N-vinylpyrrolidone, N-vinyl-N-methylacetamide, or a combination thereof.
[0155] Examples of preferred methylene-containing (=CH) pyrrolidone monomers include, but are not limited to, 1-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 1-n-propyl-3-methylene-2-pyrrolidone, 1-n-propyl-5-methylene-2-pyrrolidone, 1-isopropyl-3-methylene-2-pyrrolidone, 1-isopropyl-5-methylene-2-pyrrolidone, 1-n-butyl-3-methylene-2-pyrrolidone, 1-tert-butyl-3-methylene-2-pyrrolidone, and combinations thereof.
[0156] Examples of preferred acrylic monomers having a C1-C4 alkoxyethoxy group include, but are not limited to, ethylene glycol methyl ether (meth)acrylate, di(ethylene glycol) methyl ether (meth)acrylate, tri(ethylene glycol) methyl ether (meth)acrylate, tetra(ethylene glycol) methyl ether (meth)acrylate, C1-C4 alkoxypoly(ethylene glycol) (meth)acrylate having a weight average molecular weight of up to 1500, methoxy-poly(ethylene glycol)ethyl (meth)acrylamide having a number average molecular weight of up to 1500, and combinations thereof.
[0157] Examples of preferred vinyl ether monomers include, but are not limited to, ethylene glycol monovinyl ether, di(ethylene glycol) monovinyl ether, tri(ethylene glycol) monovinyl ether, tetra(ethylene glycol) monovinyl ether, poly(ethylene glycol) monovinyl ether, ethylene glycol methyl vinyl ether, di(ethylene glycol) methyl vinyl ether, tri(ethylene glycol) methyl vinyl ether, tetra(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) methyl vinyl ether, and combinations thereof.
[0158] Examples of preferred allyl ether monomers include, but are not limited to, allyl alcohol, ethylene glycol monoallyl ether, di(ethylene glycol) monoallyl ether, tri(ethylene glycol) monoallyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, ethylene glycol methyl allyl ether, di(ethylene glycol) methyl allyl ether, tri(ethylene glycol) methyl allyl ether, tetra(ethylene glycol) methyl allyl ether, poly(ethylene glycol) methyl allyl ether, and combinations thereof.
[0159] Examples of preferred phosphorylcholine-containing vinyl monomers include (meth)acryloyloxyethyl phosphorylcholine (also known as MPC, or 2-((meth)acryloyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate), (meth)acryloyloxypropyl phosphorylcholine (also known as 3-((meth)acryloyloxy)propyl-2'-(trimethylammonio)ethyl phosphate), 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloyloxy]ethyl [(meth)acryloylamino]ethyl-2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl-2'-(trimethylammonio)ethyl phosphate, 5-((meth)acryloyloxy)pentyl-2'-(trimethylammonio)ethyl phosphate, 6-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)ethyl phosphate 2-((meth)acryloyloxy)ethyl-2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tripropylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tributylammonio)ethyl phosphate, 2-((meth)acryloyloxy)propyl-2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)pentyl -2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)ethyl phosphate, 2-(vinyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(allyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(vinyloxycarbonyl)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(allyloxycarbonyl)ethyl-2'-(trimethylammonio)ethyl phosphate,These include, but are not limited to, 2-(vinylcarbonylamino)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(allyloxycarbonylamino)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(butenoyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate, and combinations thereof.
[0160] According to the present invention, any hydrophobic vinyl monomer can be in the present invention.Examples of preferred hydrophobic vinyl monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, styrene, chloroprene, vinyl chloride, vinylidene chloride, (meth)acrylonitrile, 1-butene, butadiene, vinyl toluene, vinyl ethyl ether, perfluorohexylethyl-thio-carbonyl-aminoethyl-methacrylate, isobornyl (meth)acrylate, trifluoroethyl (meth)acrylate, hexafluoro-isopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate, and combinations thereof.
[0161] According to the present invention, any non-silicone vinyl crosslinker may be present in the present invention. Examples of preferred non-silicone vinyl crosslinkers include ethylene glycol di-(meth)acrylate, diethylene glycol di-(meth)acrylate, triethylene glycol di-(meth)acrylate, tetraethylene glycol di-(meth)acrylate, glycerol di-(meth)acrylate, 1,3-propanediol di-(meth)acrylate, 1,3-butanediol di-(meth)acrylate, 1,4-butanediol di-(meth)acrylate, glycerol 1,3-diglycerolate ... meth)acrylate, ethylene bis[oxy(2-hydroxypropane-1,3-diyl)]di-(meth)acrylate, bis[2-(meth)acryloxyethyl]phosphate, trimethylolpropane di-(meth)acrylate, and 3,4-bis[(meth)acryloyl]tetrahydrofuan, diacrylamide, dimethacrylamide, N,N-di(meth)acryloyl-N-methylamine, N,N-di(meth)acryloyl-N-ethylamine, N,N'-methylenebis Examples of the acrylic acid copolymer include, but are not limited to, (meth)acrylamide, N,N'-ethylenebis(meth)acrylamide, N,N'-dihydroxyethylenebis(meth)acrylamide, N,N'-propylenebis(meth)acrylamide, N,N'-2-hydroxypropylenebis(meth)acrylamide, N,N'-2,3-dihydroxybutylenebis(meth)acrylamide, 1,3-bis(meth)acrylamidopropan-2-yl dihydrogen phosphate, piperazine diacrylamide, tetraethylene glycol divinyl ether, triethylene glycol divinyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, triallyl isocyanurate, triallyl cyanurate, trimethylopropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, allyl methacrylate, allyl acrylate, N-allyl-methacrylamide, N-allyl-acrylamide, and combinations thereof.Preferred non-silicone vinyl crosslinkers are tetra(ethylene glycol) di-(meth)acrylate, tri(ethylene glycol) di-(meth)acrylate, ethylene glycol di-(meth)acrylate, di(ethylene glycol) di-(meth)acrylate, tetraethylene glycol divinyl ether, triethylene glycol divinyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, triallyl isocyanurate, triallyl cyanurate, and combinations thereof.
[0162] Any thermal polymerization initiator can be used in the present invention. Suitable thermal polymerization initiators are known to those skilled in the art and include, for example, peroxides, hydroperoxides, azo-bis(alkyl or cycloalkylnitriles), persulfates, percarbonates, or mixtures thereof.Examples of preferred thermal polymerization initiators include benzoyl peroxide, t-butyl peroxide, t-amyl peroxybenzoate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, 2,5-bis(tert-butylperoxy)-2,5-dimethyl-3-hexane, bis(1-(tert-butylperoxy)-1-methylethyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di-t-butyl diperoxyphthalate, t-butyl hydroperoxide, t-butyl peracetate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl carbonate, acetyl peroxide, lauroyl peroxide, decanoyl peroxide, dicetyl peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate (Perkadox 16S), di(2-ethylhexyl) peroxydicarbonate, t-butyl peroxypivalate (Lupersol 11), t-butyl peroxy-2-ethylhexanoate (Trigonox 21-C50), 2,4-pentanedione peroxide, dicumyl peroxide, peracetic acid, potassium persulfate, sodium persulfate, ammonium persulfate, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (VAZO 33), 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride (VAZO 44), 2,2'-azobis(2-amidinopropane)dihydrochloride (VAZO 50), 2,2'-azobis(2,4-dimethylvaleronitrile) (VAZO 52), 2,2'-azobis(isobutyronitrile) (VAZO 64 or AIBN), 2,2'-azobis-2-methylbutyronitrile (VAZO 67), 1,1-azobis(1-cyclohexanecarbonitrile) (VAZO 88), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(methylisobutyrate), 4,4'-azobis(4-cyanovaleric acid), and combinations thereof.Preferably, the thermal initiator is 2,2'-azobis(isobutyronitrile) (AIBN or VAZO 64).
[0163] Suitable photoinitiators include benzoin methyl ether, diethoxyacetophenone, benzoylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, and Darocur and Irgacur types, preferably Darocur 1173® and Darocur 2959®, and germanium-based Norrish Type I photoinitiators (e.g., those described in U.S. Pat. No. 7,605,190). Examples of benzoylphosphine initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide. Reactive photoinitiators that can be incorporated into macromers or used as special monomers are also suitable. Examples of reactive photoinitiators are disclosed in EP 632,329.
[0164] Any silicone-containing prepolymer containing hydrophilic and hydrophobic segments can be used in the present invention.Examples of such silicone-containing prepolymers include those described in US Patent Nos. 6,039,913, 7,091,283, 7,268,189, 7,238,750, 7,521,519, 8,383,744 and 8,642,712, and US Patent Application Publication Nos. 2008 / 0015315A1, 2008 / 0143958A1, 2008 / 0143003A1, 2008 / 0234457A1 and 2008 / 0231798A1.
[0165] The SiHy contact lens formulation may further include other essential ingredients known to those skilled in the art, such as, for example, UV absorbing vinyl monomers, HEVL absorbing vinyl monomers, visibility colorants (e.g., reactive dyes, polymeric dyes, pigments, or mixtures thereof, as known to those skilled in the art), antimicrobial agents (e.g., preferably silver nanoparticles), bioactive agents, leachable lubricants, leachable tear stabilizers, and mixtures thereof.
[0166] In accordance with preferred embodiments of the present invention, the preformed silicone hydrogel contact lenses of the present invention may further comprise (but preferably do comprise) repeating units of one or more UV-absorbing vinyl monomers, and optionally (but preferably) one or more UV / HEVL-absorbing vinyl monomers. The term "UV / HEVL-absorbing vinyl monomer" refers to a vinyl monomer that can absorb UV light and high-energy visible light (i.e., light having a wavelength between 380 nm and 440 nm).
[0167] Any suitable UV-absorbing and UV / HEVL-absorbing vinyl monomers may be used in the polymerizable compositions to prepare the preformed SiHy contact lenses of the present invention. Examples of preferred UV-absorbing and UV / HEVL-absorbing vinyl monomers include 2-(2-hydroxy-5-vinylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-acrylyloxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methacrylamidomethyl-5-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-vinylphenyl)-2H- ... 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methacryloxypropyl-3'-t-butyl-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacryloxypropylphenyl)benzotriazole, 2-hydroxy-5-methoxy-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-1), 2-hydroxy -5-methoxy-3-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-5), 3-(5-fluoro-2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-2), 3-(2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-3), 3-(5-chloro-2H-benzo[d][1,2, 3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate (WL-4), 2-hydroxy-5-methoxy-3-(5-methyl-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-6), 2-hydroxy-5-methyl-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate (WL-7), 4-allyl-2-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl)-6-methoxyphenol (WL-8), 2-{2'-hydroxy-3'-tert-5'[3"-(4"-vinylbenzyloxy)propoxy]phenyl}-5-methoxy-2H-benzotriazole, phenol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-ethenyl-(UVAM), 2-[2'-hydroxy-5'-(2-methacryloxyethyl)phenyl)]-2H-benzotriazole (2-methyl-, 2-propenoic acid),2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl ester, Norbloc), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-2H-benzotriazole, 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-methoxy-2H-benzotriazole (UV13), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-methoxy-2H-benzotriazole rt-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-chloro-2H-benzotriazole (UV28), 2-[2'-hydroxy-3'-tert-butyl-5'-(3'-acryloyloxypropoxy)phenyl]-5-trifluoromethyl-2H-benzotriazole (UV23), 2-(2'-hydroxy-5-methacrylamidophenyl)-5-methoxybenzotriazole (UV6), 2-(3-allyl-2-hydroxy-5-methylphenyl)- 2-(2-hydroxy-3-methallyl-5-methylphenyl)-2H-benzotriazole (UV9), 2-(2-hydroxy-3-methallyl-5-methylphenyl)-2H-benzotriazole (UV12), 2-3'-t-butyl-2'-hydroxy-5'-(3"-dimethylvinylsilylpropoxy)-2'-hydroxy-phenyl)-5-methoxybenzotriazole (UV15), 2-(2'-hydroxy-5'-methacryloylpropyl-3'-tert-butyl-phenyl)-5-methoxy-2H-benzotriazole (U V16), 2-(2'-hydroxy-5'-acryloylpropyl-3'-tert-butyl-phenyl)-5-methoxy-2H-benzotriazole (UV16A), 2-methylacrylic acid 3-[3-tert-butyl-5-(5-chlorobenzotriazol-2-yl)-4-hydroxyphenyl]-propyl ester (16-100, CAS#96478-15-8), 2-(3-(tert-butyl)-4-hydroxy-5-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)phenoxy)ethyl methacrylate (16-102), Phenol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-methoxy-4-(2-propen-1-yl) (CAS# 1260141-20-5), 2-[2-hydroxy-5-[3-(methacryloyloxy)propyl]-3-tert-butylphenyl]-5-chloro-2H-benzotriazole, Phenol, 2-(5-ethenyl-2H-benzotriazol-2-yl)-4-methyl-, homopolymer (9CI) (CAS# 83063-87-0). According to the present invention, the polymerizable composition comprises from about 0.1% to about 3.0% by weight, preferably from about 0.2% to about 2.5% by weight, and more preferably from about 0.3% to about 2.0% by weight, of one or more UV-absorbing vinyl monomers, relative to the amount of all polymerizable components in the polymerizable composition.
[0168] When vinyl monomers capable of absorbing ultraviolet and high-energy visible light (HEVL) are used in the present invention, a germanium-based Norrish Type I photoinitiator and a light source containing light in the range of about 400 to about 550 nm are preferably used to initiate free radical polymerization. Any germanium-based Norrish Type I photoinitiator can be used in the present invention as long as it is capable of initiating free radical polymerization under irradiation with a light source containing light in the range of about 400 to about 550 nm. Examples of Germane-based Norrish Type I photoinitiators are the acylgermanium compounds described in U.S. Pat. No. 7,605,190.
[0169] A bioactive agent is any compound capable of preventing ocular disease or alleviating the symptoms of ocular disease. The bioactive agent may be a drug, an amino acid (e.g., taurine, glycine, etc.), a polypeptide, a protein, a nucleic acid, or any combination thereof. Examples of drugs useful herein include, but are not limited to, rebamipide, ketotifen, olaptidine, cromoglycolate, cyclosporine, nedocromil, levocabastine, lodoxamide, ketotifen, or pharmaceutically acceptable salts or esters thereof. Other examples of bioactive agents include 2-pyrrolidone-5-carboxylic acid (PCA), α-hydroxyl acids (e.g., glycolic acid, lactic acid, malic acid, tartaric acid, mandelic acid, and citric acid and their salts), linoleic acid and γ-linoleic acid, and vitamins (e.g., B5, A, B6, etc.).
[0170] Examples of leachable lubricants include, but are not limited to, mucin-like materials (e.g., polyglycolic acid) and non-crosslinkable hydrophilic polymers (i.e., without ethylenically unsaturated groups). Any hydrophilic polymer or copolymer that does not contain any ethylenically unsaturated groups can be used as a leachable lubricant. Preferred examples of non-crosslinkable hydrophilic polymers include, but are not limited to, polyvinyl alcohol (PVA), polyamides, polyimides, polylactones, homopolymers of vinyl lactams, copolymers of at least one vinyl lactam with or without one or more hydrophilic vinyl comonomers, homopolymers of acrylamide or methacrylamide, copolymers of acrylamide or methacrylamide with one or more hydrophilic vinyl monomers, polyethylene oxide (i.e., polyethylene glycol (PEG)), polyoxyethylene derivatives, poly-NN-dimethylacrylamide, polyacrylic acid, poly(2-ethyloxazoline), heparin polysaccharides, polysaccharides, and mixtures thereof. The number average molecular weight M of the non-crosslinkable hydrophilic polymer is: n is preferably 5,000 to 1,000,000.
[0171] Examples of exudative tear stabilizing agents include, but are not limited to, phospholipids, monoglycerides, diglycerides, triglycerides, glycolipids, glyceroglycolipids, sphingolipids, glycosphingolipids, fatty alcohols, fatty acids, mineral oils, and mixtures thereof. Preferably, the tear stabilizing agent is a phospholipid, monoglyceride, diglyceride, triglyceride, glycolipid, glyceroglycolipid, sphingolipid, glycosphingolipid, fatty acid having 8 to 36 carbon atoms, fatty alcohol having 8 to 36 carbon atoms, or mixtures thereof.
[0172] The polymerizable composition (SiHy lens formulation) may be a solvent-free clear liquid prepared by mixing all polymerizable components and other necessary ingredients, or it may be a solution prepared by dissolving all desired components in any suitable solvent known to those skilled in the art, such as a mixture of water and one or more organic solvents miscible with water, an organic solvent, or a mixture of one or more organic solvents. The term "solvent" refers to a chemical that cannot participate in a free-radical polymerization reaction.
[0173] Solventless lens SiHy lens formulations typically contain at least one blend vinyl monomer as a reactive solvent to dissolve all other polymerizable components of the solventless SiHy lens formulation. Examples of preferred blend vinyl monomers include C1-C 10Examples of suitable vinyl monomers include alkyl (meth)acrylates (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, etc.), cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, isobornyl (meth)acrylate, styrene, 4,6-trimethylstyrene (TMS), t-butylstyrene (TBS), trifluoroethyl (meth)acrylate, hexafluoroisopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate, or combinations thereof. Preferably, methyl methacrylate is used as the blend vinyl monomer in preparing the solventless SiHy lens formulations.
[0174] Any solvent can be used in the present invention. Examples of preferred organic solvents include tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ether, ethylene glycol n-butyl ether, ketones (e.g., acetone, methyl ethyl ketone, etc.), diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether dipropyl ether, and the like. propylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate, methyl lactate, ethyl lactate, i-propyl lactate, methylene chloride, 2-butanol, 1-propanol, 2-propanol, menthol, cyclohexanol, cyclopentanol, and exonorborneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butanol, tert-amyl alcohol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-Dimethyl-3-octanol, 1-chloro-2-methyl-2-propanol, 2-methyl-2-heptanol, 2-methyl-2-octanol, 2-2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, 1-ethylcyclopentanol, 1-ethyl The solvents include, but are not limited to, 2-ethylcyclopentanol, 3-hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol, and 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-propanol, t-amyl alcohol, isopropanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethylformamide, dimethylacetamide, dimethylpropionamide, N-methylpyrrolidinone, and mixtures thereof.
[0175] Numerous SiHy lens formulations have been described in numerous patents and patent applications published as of the filing date of this application and are used in the manufacture of commercially available SiHy contact lenses. Examples of commercially available SiHy contact lenses include, but are not limited to, asmofilcon A, balafilcon A, comfilcon A, delefilcon A, efrofilcon A, enfilcon A, fanfilcon A, galyfilcon A, lotrafilcon A, lotrafilcon B, narafilcon A, narafilcon B, senofilcon A, senofilcon B, senofilcon C, smafilcon A, somofilcon A, and stenfilcon A.
[0176] The SiHy lens formulation (ie, polymerizable composition) can be cured (polymerized) thermally or actinically, preferably in a mold for casting a contact lens, as is well known to those skilled in the art.
[0177] Thermal polymerization is conveniently carried out at temperatures of, for example, 25 to 120°C, preferably 40 to 100°C. The reaction time may vary within a wide range but is conveniently, for example, 1 to 24 hours, or preferably 2 to 12 hours. It is advantageous to previously degas the components and solvents used in the polymerization reaction and to carry out the copolymerization reaction under an inert atmosphere, for example, under a nitrogen or argon atmosphere.
[0178] The actinic polymerization may then be triggered off by actinic radiation, for example light, in particular UV light or visible light of a suitable wavelength. The spectral requirements can be controlled, if appropriate, by the addition of suitable sensitizers.
[0179] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polysiloxane vinyl monomer (preferably selected from those described above) and at least one repeating unit of a hydrophilic vinyl monomer (preferably selected from those described above).
[0180] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polysiloxane vinyl crosslinker (preferably selected from those described above) and repeating units of at least one hydrophilic vinyl monomer (preferably selected from those described above).
[0181] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polysiloxane vinyl monomer (preferably selected from those described above) and at least one repeating unit of a hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0182] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polysiloxane vinyl crosslinker (preferably selected from those described above) and repeating units of at least one hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0183] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl monomer (preferably selected from those described above) and at least one repeating unit of a hydrophilic vinyl monomer (preferably selected from those described above).
[0184] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl crosslinker (preferably selected from those described above) and repeating units of at least one hydrophilic vinyl monomer (preferably selected from those described above).
[0185] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl monomer (preferably selected from those described above) and at least one repeating unit of a hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0186] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl crosslinker (preferably selected from those described above) and repeating units of at least one hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0187] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one silicone-containing vinyl monomer (preferably selected from those described above) having a bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl group, and repeating units of at least one hydrophilic vinyl monomer (preferably selected from those described above).
[0188] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl crosslinker (preferably selected from those described above), repeating units of at least one silicone-containing vinyl monomer having a bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl group (preferably selected from those described above), and repeating units of at least one hydrophilic vinyl monomer (preferably selected from those described above).
[0189] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one silicone-containing vinyl monomer having a bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl group (preferably selected from those described above) and repeating units of at least one hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0190] In a preferred embodiment, the inner layer or lens bulk material is comprised of a silicone hydrogel material comprising repeating units of at least one polycarbosiloxane vinyl crosslinker (preferably selected from those described above), repeating units of at least one silicone-containing vinyl monomer having a bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl group (preferably selected from those described above), and repeating units of at least one hydrophilic N-vinylamide monomer (preferably selected from those described above).
[0191] According to any one of the preferred embodiments of the present invention, the inner layer or lens bulk material is comprised of a silicone hydrogel material further comprising repeat units of one or more blended vinyl monomers, preferably in an amount of about 25% by weight or less (preferably about 20% by weight or less, more preferably about 15% by weight or less), based on the dry weight of the inner layer of silicone hydrogel material. The amount of repeat units of the blended vinyl monomers can be calculated based on the amount of the blended vinyl monomers in the polymerizable composition used to prepare the pre-formed silicone hydrogel contact lens (i.e., the inner layer) relative to the total amount of all polymerizable components in the polymerizable composition.
[0192] According to any one of the preferred embodiments of the present invention, the inner layer or lens bulk material is comprised of a silicone hydrogel material further comprising one or more repeating units of a non-silicone vinyl crosslinker (preferably selected from those described above), preferably in an amount of about 1.0 wt. % or less (preferably about 0.8 wt. % or less, more preferably about 0.05 wt. % to about 0.6 wt. %) based on the dry weight of the inner layer. The amount of repeating units of the non-silicone vinyl crosslinker can be calculated based on the amount of the non-silicone vinyl crosslinker in the polymerizable composition used to prepare the pre-formed silicone hydrogel contact lens (i.e., the inner layer) relative to the total amount of all polymerizable components of the polymerizable composition.
[0193] According to any one of the preferred embodiments of the present invention, the inner layer or lens bulk material is made of a naturally wettable silicone hydrogel material (i.e., a preformed silicone hydrogel contact lens that is naturally wettable without being subjected to any post-cure surface treatment). Naturally wettable preformed SiHy contact lenses are disclosed in U.S. Patent Nos. 6,367,929, 6,822,016, 7,052,131, 7,249,848, 6,867,245, 7,268,198, 7,540,609, 7,572,841, and 7,750,079. Specifications, Specification No. 7934830, Specification No. 8231218, Specification No. 8367746, Specification No. 8445614, Specification No. 8481662, Specification No. Specification No. 8487058, Specification No. 8513325, Specification No. 8703891, Specification No. 8820928, Specification No. 8865789, Specification No. 89371 Specification No. 10, Specification No. 8937111, Specification No. 9057821, Specification No. 9057822, Specification No. 9121998, Specification No. 9,125,808 Specification, Specification No. 9140825, Specification No. 9140908, Specification No. 9156934, Specification No. 9164298, Specification No. 9170349, Specification No. Nos. 9,188,702, 9,217,813, 9,296,159, 9,322,959, 9,322,960, 9,360,594, and 9,529,119, and U.S. Provisional Patent Application Nos. 16 / 000,930 and 16 / 000,933.
[0194] According to the present invention, the silicone hydrogel material of the inner layer (or bulk lens material) has an oxygen permeability of at least about 50 barrers, preferably at least about 60 barrers, more preferably at least about 70 barrers, even more preferably at least about 90 barrers, and most preferably at least about 110 barrers. The silicone hydrogel material may also have an equilibrium water content of about 10% to about 70% by weight, preferably about 10% to about 65% by weight, more preferably about 10% to about 60% by weight, even more preferably about 15% to about 55% by weight, and most preferably about 15% to about 50% by weight. The silicone hydrogel material may further have a bulk modulus or bulk Young's modulus of about 0.3 MPa to about 1.8 MPa, preferably about 0.4 MPa to about 1.5 MPa, and more preferably about 0.5 MPa to about 1.2 MPa (hereinafter, the terms "flexibility," "modulus," and "Young's modulus" are used interchangeably herein to refer to bulk modulus unless the term is modified by the word "surface"). The oxygen permeability, modulus, and water content of the inner layer of the silicone hydrogel material of the contact lens of the present invention can be determined by measuring the oxygen permeability, modulus, and water content of the preformed SiHy lens from which the inner layer is derived.It should be understood that, because the outer hydrogel layer is much thinner, as a reasonable approximation, the modulus of the SiHy contact lens of the present invention can be considered to be the modulus of the silicone hydrogel material of the inner layer.Those skilled in the art are familiar with methods for determining the modulus and water content of silicone hydrogel materials or SiHy contact lenses.For example, all commercially available SiHy contact lenses have reported values for oxygen permeability, modulus, and water content.
[0195] According to various aspects of the present invention, the thicknesses of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer vary depending on the inner layer or lens bulk material of the present contact lenses to ensure biocompatibility of the contact lenses, provide sufficient wearing comfort, and prevent exposure of the underlying lens bulk material to the eye.
[0196] When the inner layer or lens bulk material is a hard plastic material (i.e., a preformed hard contact lens) or a hard gas permeable lens material (i.e., a preformed rigid gas permeable contact lens), the thickness of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer is from about 1.0 μm to about 20 μm, preferably from about 2.0 μm to about 15 μm, more preferably from about 2.0 μm to about 10 μm, and even more preferably from about 2.5 μm to about 8 μm.
[0197] When the inner layer or lens bulk material is a crosslinked silicone material (i.e., a preformed silicone contact lens), the thickness of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer is from about 2.0 μm to about 25 μm, preferably from about 3.0 μm to about 25 μm, more preferably from about 4.0 μm to about 20 μm, and even more preferably from about 5.0 μm to about 20 μm.
[0198] When the inner layer or lens bulk material is a crosslinked non-silicone hydrogel material (i.e., a preformed non-silicone hydrogel contact lens), the thickness of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer is from about 0.25 μm to about 20 μm, preferably from about 0.50 μm to about 15 μm, more preferably from about 0.5 μm to about 10 μm, and even more preferably from about 0.5 μm to about 6 μm.
[0199] When the inner layer or lens bulk material is a silicone hydrogel material that is not naturally wettable (i.e., a preformed silicone hydrogel contact lens), the thickness of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer is from about 0.5 μm to about 25 μm, preferably from about 1.0 μm to about 20 μm, more preferably from about 1.0 μm to about 15 μm, and even more preferably from about 1.5 μm to about 10 μm.
[0200] When the inner layer or lens bulk material is a naturally wettable cross-linked silicone hydrogel material (i.e., a preformed silicone hydrogel contact lens), the thickness of the outer surface hydrogel layer, the anterior outer surface hydrogel layer, and the posterior outer surface hydrogel layer is from about 0.25 μm to about 20 μm, preferably from about 0.5 μm to about 20 μm, more preferably from about 0.5 μm to about 15 μm, and even more preferably from about 1.0 μm to about 10 μm.
[0201] The anterior and posterior outer hydrogel layers of the present contact lenses are preferably substantially identical to one another (ie, resulting in outer surface hydrogel layers) and are crosslinked coatings applied onto preformed contact lenses.
[0202] In a preferred embodiment, the independent front and rear outer hydrogel layers and the outer surface hydrogel layer comprise at least 25 mol % (preferably at least 35 mol %, more preferably at least 45 mol %, and even more preferably at least 55 mol %) of an alkyl(meth)acrylamide (any one of the above), N-2-dimethylaminoethyl(meth)acrylamide, dimethylaminoethyl(meth)acrylate, a hydroxyl-containing acrylic monomer (any one of the above), an N-vinylamide monomer (any one of the above), a methylene-containing pyrrolidone monomer (i.e., pyrrolidone derivatives each having a methylene group attached to the pyrrolidone ring at the 3- or 5-position (any one of the above), (meth)acrylate monomers having a C1-C4 alkoxyethoxy group (any one of the above), vinyl ether monomers (any one of the above), allyl ether monomers (any one of the above), and combinations thereof (preferably, (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxylethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-2,3-Dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, glycerol methacrylate (GMA), tetra(ethylene glycol) (meth)acrylate, poly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, N-vinylformamide, N-vinylacetamide, 1-methyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, tetra(ethylene glycol) methyl ether (meth)acrylate, methoxypoly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, and the like. The hydroxyl group is selected from the group consisting of (meth)acrylamide, C1-C4-alkoxy polyethylene glycol (meth)acrylate having a weight average molecular weight of up to 1500, tetra(ethylene glycol) monovinyl ether, poly(ethylene glycol) monovinyl ether, tetra(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) methyl vinyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, tetra(ethylene glycol) methyl allyl ether, poly(ethylene glycol) methyl allyl ether, vinyl alcohol, allyl alcohol, and combinations thereof, more preferably (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxyethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-2,The group consisting of 3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, glycerol methacrylate (GMA), poly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, methoxypoly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, methoxypolyethylene glycol (meth)acrylate having a weight average molecular weight of up to 1500, poly(ethylene glycol) monovinyl ether, poly(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) monoallyl ether, poly(ethylene glycol) methyl allyl ether, vinyl alcohol, allyl alcohol, and combinations thereof. and even more preferably, the crosslinked polymeric material comprises repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxylethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-2,3-dihydroxypropyl(meth)acrylamide, N-tris(hydroxymethyl)methyl(meth)acrylamide, poly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol)(meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, methoxypoly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, methoxypolyethylene glycol(meth)acrylate having a weight average molecular weight of up to 1500, and combinations thereof.
[0203] In a preferred embodiment, the independent front and rear outer hydrogel layers, and the outer surface hydrogel layer, are crosslinked polymeric materials comprising at least 25 mol % (preferably at least 35 mol %, more preferably at least 45 mol %, and even more preferably at least 55 mol %) of repeating monomer units of at least one phosphrylcholine-containing vinyl monomer, preferably selected from the group consisting of (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloylamino]ethyl-2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl-2'-(trimethylammonio)ethyl phosphate, and combinations thereof.
[0204] In a preferred embodiment, the independent front and rear outer hydrogel layers and the outer surface hydrogel layer are crosslinked polymeric materials comprising poly(ethylene glycol) chains, preferably derived directly from (1) pol(ethylene glycol) having only one functional group selected from -NH, -SH, or -COOH, (2) pol(ethylene glycol) having two terminal functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof, (3) multi-arm poly(ethylene glycol) having one or more functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof, and (4) combinations thereof.
[0205] According to a preferred embodiment, the anterior and posterior outer hydrogel layers of the present contact lenses are identical to one another and are substantially uniform in thickness, merge at the edge of the contact lens to completely cover the inner layer, and have an equilibrium water content of at least 80% by weight, preferably at least 85% by weight, more preferably at least about 90% by weight, and even more preferably at least 95% by weight.
[0206] According to a preferred embodiment, the outer surface hydrogel layer of the present contact lenses comprises an equilibrium water content of at least 80% by weight, preferably at least 85% by weight, more preferably at least about 90% by weight, and even more preferably at least 95% by weight.
[0207] According to the present invention, each of the front and rear outer hydrogel layers is substantially free of silicone, and preferably completely free of silicone. However, when X-ray photoelectron spectroscopy (XPS) is used to verify the presence or absence of silicon in the outer hydrogel layer (typically at a probing depth of 1.5-6 nm), it is well known that samples are inevitably contaminated with silicon from the environment, as demonstrated by the detection of silicon by XPS on the surface of theoretically free samples, such as polyethylene sheet from Goodfellow (1.3±0.2%), DAILIES® AquaComfortPlus™ contact lenses from Alcon (1.7±0.9%), or ACUVUE® Moist from Johnson & Johnson (2.8±0.9%). Thus, the term "substantially silicon-free" is used herein to mean that the surface silicon atomic concentration measured by XPS on a SiHy contact lens is less than about 200%, preferably less than about 175%, more preferably less than about 150%, and even more preferably less than about 125% of the silicon atomic concentration of a control sample known to be inherently (theoretically) silicon-free (e.g., polyethylene sheet, DAILIES® AquaComfortPlus™ contact lens from Alcon, or ACUVUE® Moist from Johnson & Johnson). Alternatively, each outer hydrogel layer of a SiHy contact lens of the present invention is substantially silicon-free, as characterized by having a silicon atomic concentration of less than about 5%, preferably less than about 4%, and even more preferably less than about 3% of the total elemental percentage as measured by XPS analysis of the contact lens in the dry state. It will be appreciated that, optionally (though not preferred), a small percentage of silicone may be incorporated into the polymer network of the outer hydrogel layer, so long as it does not significantly degrade the surface properties (hydrophilicity, wettability, and / or lubricity) of the contact lens.
[0208] In a preferred embodiment, each of the front and rear outer hydrogel layers (crosslinked coatings) has high finger-rubbing resistance, as characterized by the absence of visible surface crack lines under dark field after rubbing the contact lens between fingers. It is believed that surface cracks caused by finger rubbing may reduce surface lubricity and / or may not prevent silicone from migrating (exposing) to the surface. Surface cracks may also indicate excessive crosslink density in the surface layer, which may affect the surface modulus. Preferably, the non-silicone hydrogel material in the outer hydrogel layer (crosslinked coating) contains crosslinks derived from azetidinium groups during a thermally induced coupling reaction.
[0209] In another preferred embodiment, the contact lenses of the present invention further comprise two transition layers of polymeric material in their layered configuration. Each of the two transition layers is positioned between the inner layer and one of the anterior and posterior outer hydrogel layers. Each transition layer has a substantially uniform thickness. Each transition layer has a thickness of at least about 0.05 μm, preferably from about 0.05 μm to about 10 μm, more preferably from about 0.1 μm to about 7.5 μm, and even more preferably from about 0.15 μm to about 5 μm. The transition layers merge at the peripheral edge of the contact lens and completely surround the inner layer of lens material.
[0210] As is well known to those skilled in the art, the layered morphology of the contact lenses of the present invention can be verified by atomic force microscopy (AFM) analysis of cross-sections of contact lenses in a fully hydrated state (i.e., directly in water or buffered saline). As is well known to those skilled in the art, the average thickness of each outer hydrogel layer can be determined from the AFM image.
[0211] The two transition layers of the present contact lenses are essentially base (or primer or anchor) coatings (or layers) that are applied to a preformed contact lens before the crosslinked coating (outer hydrogel layer) is applied thereto. The transition layer (base coating or anchor layer) serves to anchor / attach the outer hydrogel layer. Preferably, the transition layer comprises a carboxyl (COOH)-containing polymer crosslinked with polyaziridine, preferably acrylic or methacrylic acid or C2-C6 crosslinked with polyaziridine. 12 The transition layers may include homo- or copolymers of alkylacrylic acids. It will be appreciated that the carboxyl-containing polymer may penetrate into the bulk material and extend into the outer hydrogel layers. If such penetration occurs into the inner layers of the lens material, each transition layer will comprise carboxyl-containing polymer and lens material intertwined together.
[0212] In another preferred embodiment, each of the independent front and back outer hydrogel layers has a reduced surface modulus relative to the inner layer by at least about 20%, preferably at least about 25%, more preferably at least about 30%, even more preferably at least about 35%, and most preferably at least about 40%.
[0213] The surface modulus of the cross section can be characterized (imaged) by AFM (e.g., according to nanoindentation) to visualize any changes in surface modulus from the posterior surface side to the anterior surface side across the cross section. A significant change (e.g., about 30% or more) observed in the surface modulus (by examining the AFM image) along the shortest line between the anterior and posterior surfaces across the cross section of a fully hydrated contact lens over a thickness of about 0.02 μm, preferably about 0.01 μm, indicates a transition from one layer to another.
[0214] In any one of the above-described preferred embodiments of the various aspects of the present invention, the contact lenses of the present invention have a friction rating of about 2 or less (preferably about 1.5 or less, more preferably about 1.0 or less, and even more preferably about 0.5 or less) after 30 cycles of manual rubbing testing.
[0215] In any one of the above-described preferred embodiments of the various aspects of the present invention, the contact lenses of the present invention have a UVB transmittance of about 10% or less (preferably about 5% or less, more preferably about 2.5% or less, and even more preferably about 1% or less) from 280 to 315 nanometers, a UVA transmittance of about 30% or less (preferably about 20% or less, more preferably about 10% or less, and even more preferably about 5% or less) from 315 to 380 nanometers, and a violet transmittance of 0% to about 70%, preferably 5% to about 60%, more preferably 5% to about 50%, and even more preferably 5% to about 40% from 380 nm to 440 nm.
[0216] The contact lenses of the present invention may be obtained or developed by any method known to those skilled in the art.
[0217] For example, the contact lenses of the present invention can be obtained by neutralizing a preformed water gradient contact lens with a polyaziridine having a number average molecular weight of about 2000 daltons or less (preferably 250 daltons to 1500 daltons, more preferably 300 daltons to 1000 daltons, and even more preferably 350 daltons to about 800 daltons) and at least two aziridine groups.
[0218] Preformed water gradient contact lenses are described in U.S. Patent Nos. 8,480,227, 8,529,057, and 9,505,184, as well as U.S. Patent Application Publication Nos. 2017 / 0068018A1, 2017 / 0068019A1, 2017 / 0165932A1, 2018 / 0079157A1, 2018 / 0079158A1, and 2018 / 0079158A1. Similar to the procedures described in 018 / 0081197A1, 2018 / 0113236A1, and 2018 / 0120590A1, a contact lens precursor comprising an anchor layer (or base coating) of a polyanionic polymer having reactive functional groups (e.g., carboxyl groups) can be obtained by heating in an aqueous solution containing a thermally crosslinkable hydrophilic polymer material.
[0219] A contact lens precursor having an anchor layer thereon can be obtained by contacting a preformed contact lens with a polyanionic polymer solution having a pH of about 1.0 to about 3.0 for a length of time sufficient to form an anchor layer of the polyanionic polymer having a desired thickness.
[0220] Contacting a preformed contact lens with a polymeric coating solution can occur by dipping it into the coating solution or by spraying it with the coating solution. One contacting process involves simply dipping the contact lens into a bath of coating solution for a period of time, or alternatively, dipping the contact lens sequentially into a series of baths of coating solution, each bath for a predetermined shorter period of time. Another contacting process involves simply spraying the coating solution. However, numerous alternative methods involve various combinations of spraying and dipping steps that can be planned by one skilled in the art.
[0221] Any polyanionic polymer can be used to form the anchor layer on a preformed contact lens, so long as it contains at least 60 mole percent repeating units of one or more carboxyl-containing acrylic monomers (any one of those described above). Examples of preferred polyanionic polymers include, but are not limited to, polyacrylic acid, polymethacrylic acid, poly(ethylacrylic acid), poly(acrylic acid-co-methacrylic acid), poly[ethylacrylic acid-co-(meth)acrylic acid], poly(N,N-2-acrylamidoglycolic acid), poly[(meth)acrylic acid-co-acrylamide], poly[(meth)acrylic acid-co-vinylpyrrolidone], poly[ethylacrylic acid-co-acrylamide], poly[ethylacrylic acid-co-vinylpyrrolidone], poly[(meth)acrylic acid-co-vinyl acetate], poly[ethylacrylic acid-co-vinyl acetate], or combinations thereof. Preferably, the polyanionic polymer is polyacrylic acid, polymethacrylic acid, or a combination thereof.
[0222] In accordance with the present invention, a polyanionic polymer having a number average molecular weight M for forming an anchor layer (or base coating) on a preformed contact lens with or without a plasma coating is used. n is at least about 25,000 daltons, preferably at least about 50,000 daltons, and more preferably from about 100,000 daltons to about 5,000,000 daltons.
[0223] A solution of polyanionic polymers for forming an anchor layer (or base coating) on a preformed contact lens with or without a plasma coating can be prepared by dissolving one or more polyanionic polymers in water, a mixture of water and one or more water-miscible organic solvents, an organic solvent, or a mixture of one or more organic solvents. Preferably, the polyanionic polymer is dissolved in a mixture of water and one or more organic solvents, an organic solvent, or a mixture of one or more organic solvents. It is believed that a solvent system containing at least one organic solvent can swell the preformed contact lens, allowing a portion of the polyanionic polymer to penetrate into the preformed contact lens and increase the durability and thickness of the anchor layer (base coating). Any of the above organic solvents can be used to prepare the polyanionic polymer solution, as long as they can dissolve the polyanionic polymer.
[0224] The concentration of the polyanionic polymer is about 0.001% by weight to about 2.5% by weight, preferably about 0.002% by weight to about 1.5% by weight, and more preferably 0.003% by weight to about 0.75% by weight, based on the total weight of the organic solution.
[0225] As known to those skilled in the art, the thickness of the anchor layer (base coating) can be adjusted by varying the concentration of the polyanionic polymer, the contact time of the preformed contact lens with the polyanionic polymer solution, the solvent system (e.g., the amount of one or more organic solvents), or a combination thereof.
[0226] Alternatively, a contact lens precursor having an anchor layer thereon can be obtained by grafting a polyanionic polymer onto the surface of a preformed contact lens using any graft polymerization technique known to those skilled in the art. For example, a dry preformed contact lens is first subjected to plasma treatment in a plasma atmosphere with a compound having at least one reactive functional group (e.g., a vinyl monomer having a primary or secondary amino group, a carboxyl group, an epoxy group, an azlactone group, an aziridine group, or an isocyanate group) to form a plasma coating having reactive functional groups. The plasma-treated contact lens is then reacted with a compound having a free radical initiator moiety (e.g., a thermal initiator or a photoinitiator) or preferably a living polymerization initiator moiety (e.g., an atom transfer radical polymerization (ATRP) initiator or a reversible addition-fragmentation chain transfer (RAFT) initiator) and a functional group co-reactive with the functional group of the plasma coating on the contact lens, in the presence or absence of a coupling agent under coupling reaction conditions known to those skilled in the art. The resulting contact lens having free radical initiator moieties thereon is immersed in a solution of one or more carboxyl-containing vinyl monomers (preferably the carboxyl-containing acrylic monomers described above) and subjected to conditions to initiate free radical polymerization of these carboxyl-containing vinyl monomers to form a layer of graft-from polyanionic polymer of the carboxyl-containing vinyl monomer.
[0227] According to the present invention, the thermally crosslinkable hydrophilic polymeric material for forming the outer surface hydrogel layer or the front and rear outer hydrogel layers (i.e., crosslinked hydrophilic coating) contains crosslinkable groups, preferably thermally crosslinkable groups (e.g., epoxy groups, azetidinium groups, or a combination thereof), more preferably azetidinium groups. Preferably, the water-soluble and crosslinkable hydrophilic polymeric material is a partially crosslinked polymeric material containing a three-dimensional network and thermally crosslinkable groups, preferably azetidinium groups, within or attached to the network. The term "partially crosslinked" in relation to a polymeric material means that the crosslinkable groups of the starting material for producing the polymeric material are not completely consumed in the crosslinking reaction. For example, such a thermally crosslinkable hydrophilic polymeric material contains azetidinium groups and is the partial reaction product of at least one azetidinium-containing polymer and at least one hydrophilic enhancing agent (i.e., wetting agent) having at least one carboxyl, primary amine, secondary amine, or thiol group, according to the crosslinking reaction shown in Scheme I: [ka] In the formula, X1 is -S-*, -OC(=O)-*, or -NR'-*, in which R' is hydrogen or C1 to C 20 where * represents an organic radical.
[0228] Any suitable azetidinium-containing polymer can be used in the present invention. Examples of azetidinium-containing polymers include, but are not limited to, epichlorohydrin-functionalized polyamines, homopolymers of azetidinium-containing vinyl monomers, and copolymers of azetidinium-containing vinyl monomers with one or more vinyl monomers.
[0229] Preferably, the azetidinium-containing polymer is an epichlorohydrin-functionalized polyamine. The epichlorohydrin-functionalized polyamine can be obtained by reacting epichlorohydrin with a polyamine polyamine or a secondary amino group-containing polymer. For example, poly(alkyleneimine) or poly(amidoamine), which is a polycondensate derived from a polyamine and a dicarboxylic acid (e.g., adipic acid-diethylenetriamine copolymer), can be reacted with epichlorohydrin to form an epichlorohydrin-functionalized polymer. A homopolymer or copolymer of mono-alkylaminoalkyl(meth)acrylate or mono-alkylaminoalkyl(meth)acrylamide can also be reacted with epichlorohydrin to form an epichlorohydrin-functionalized polyamine. Poly(2-oxazoline-c o-Ethyleneimine copolymers can be reacted with epichlorohydrin to form epichlorohydrin-functionalized polyamines (i.e., poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin). Reaction conditions for epichlorohydrin functionalization of polyamine or polyamidoamine polymers are taught in EP 1465931. Preferred epichlorohydrin-functionalized polyamines are polyamidoamine-epichlorohydrin (PAE) or poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin.
[0230] Polyamidoamine-epichlorohydrin is commercially available, for example, Kymene® or Polycup® resins (epichlorohydrin-functionalized adipic acid-diethylenetriamine copolymers) from Hercules.
[0231] Poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin can be prepared according to the procedure described in US Patent Application Publication No. 2016 / 0061995A1.
[0232] Homopolymers and copolymers of azetidinium-containing vinyl monomers can be obtained according to the procedures described in US Patent Application Publication No. 2013 / 0337160 A1.
[0233] Any suitable hydrophilicity enhancer can be used in the present invention as long as it is ophthalmically compatible and contains at least one amino group, at least one carboxyl group, and / or at least one thiol group, preferably at least one carboxyl group, at least one thiol group, or a combination thereof.
[0234] Preferred classes of hydrophilicity enhancers include primary amino, secondary amino, carboxyl, or thiol-containing monosaccharides (e.g., 3-amino-1,2-propanediol, 1-thiolglycerol, 5-keto-D-gluconic acid, galactosamine, glucosamine, galacturonic acid, gluconic acid, glucosamine acid, mannosamine, sugar acid 1,4-lactone, saccharic acid, ketodeoxynonulosonic ... acid), N-methyl-D-glucamine, 1-amino-1-deoxy-β-D-galactose, 1-amino-1-deoxysorbitol, 1-methylamino-1-deoxysorbitol, N-aminoethylgluconamide), primary amino, secondary amino, carboxyl, or thiol-containing disaccharides (e.g., chondroitin disaccharide sodium salt, di(β-D-xylopyranosyl)amine, digalacturonic acid, heparin disaccharide, hyaluronic acid disaccharide, lactobionic acid), and primary amino, secondary amino, carboxyl, or thiol-containing oligosaccharides (e.g., carboxymethyl-β-cyclodextrin sodium salt, trigalacturonic acid), and combinations thereof.
[0235] Another preferred class of hydrophilic enhancers is hydrophilic polymers having one or more (primary or secondary) amino, carboxyl, and / or thiol groups. More preferably, the content of amino (-NHR' (R' is as defined above)), carboxyl (-COOH), and / or thiol (-SH) groups in the hydrophilic polymer as the hydrophilic enhancer is less than about 40 wt%, preferably less than about 30 wt%, more preferably less than about 20 wt%, and even more preferably less than about 10 wt%, based on the total weight of the hydrophilic polymer.
[0236] One preferred class of hydrophilic polymers as hydrophilic enhancers is, for example, carboxymethylcellulose (repeating unit -[CH 10-m O5(CH2CO2H) m ]- (where m is 1-3), carboxyethyl cellulose (having a carboxyl content of about 40% or less estimated based on the composition of the repeating unit -[CH 10-m O5(C2H4CO2H) m ]- (where m is 1 to 3), carboxypropyl cellulose (having a carboxyl content of about 36% or less estimated based on the composition of the repeating unit -[CH 10-m O5(C3H6CO2H) m ]- (where m is 1-3), hyaluronic acid (having a carboxyl content of about 32% or less estimated based on the composition of the repeating unit -(C 13 H 20 chondroitin sulfate (which has an estimated carboxyl content of about 11% based on the composition of the repeating unit -(C 12 H 18 O 13 NS (CO₂H)-) (having an estimated carboxyl content of about 9.8% based on the composition), or combinations thereof.
[0237] Another preferred class of hydrophilic polymers for use as hydrophilicity enhancers includes poly(ethylene glycol) (PEG) (e.g., PEG-NH, PEG-SH, PEG-COOH) with mono-amino (primary or secondary amino), carboxyl, or thiol groups, HN-PEG-NH, HOOC-PEG-COOH, HS-PEG-SH, HN-PEG-COOH, HOOC-PEG-SH, HN-PEG-SH, multi-arm PEG with one or more amino (primary or secondary), carboxyl, or thiol groups, PEG dendrites with one or more amino (primary or secondary), carboxyl, or thiol groups, and the like. These include, but are not limited to, drimers, diamino (primary or secondary) or dicarboxyl terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers, monoamino (primary or secondary) or monocarboxyl terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers, copolymers that are the polymerization product of a composition comprising (1) up to about 60% by weight, preferably from about 0.1% to about 30% by weight, more preferably from about 0.5% to about 20% by weight, and even more preferably from about 1% to about 15% by weight of one or more reactive vinyl monomers, and (2) at least one non-reactive hydrophilic vinyl monomer, and combinations thereof.
[0238] According to the present invention, the reactive vinyl monomer may be a carboxyl-containing vinyl monomer, a primary amino-containing vinyl monomer, or a secondary amino-containing vinyl monomer.
[0239] Examples of preferred carboxyl-containing vinyl monomers include, but are not limited to, acrylic acid, methacrylic ethylacrylic acid, N-2-(meth)acrylamidoglycolic acid, and combinations thereof.
[0240] Examples of preferred primary and secondary amino-containing vinyl monomers include, but are not limited to, N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, 2-aminoethyl(meth)acrylate, 2-methylaminoethyl(meth)acrylate, 2-ethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 3-methylaminopropyl(meth)acrylate, 3-ethylaminopropyl(meth)acrylate, 3-amino-2-hydroxypropyl(meth)acrylate, and combinations thereof.
[0241] According to the present invention, the non-reactive vinyl monomer is a vinyl monomer that does not contain any carboxyl group, primary amino group, secondary amino group, epoxide group, isocyanate group, azlactone group, or aziridine group. The non-reactive vinyl monomer is preferably an uncharged hydrophilic vinyl monomer that does not contain a carboxyl group or an amino group (any of the above-described ones can be used herein), a phosphorylcholine-containing vinyl monomer (any of the above-described ones can be used herein), or a combination thereof.
[0242] More preferably, the hydrophilic polymer as the hydrophilicity enhancer is Poly(ethylene glycol) having one and only one functional group of -NH, -SH, or -COOH; Poly(ethylene glycol) having two terminal functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof; multi-arm poly(ethylene glycol) having one or more functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof; monoamide, monocarboxyl, diamino, or dicarboxyl terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers; (1) About 0.1% by weight to about 30% by weight, preferably about 0.5% by weight to about 20% by weight, more preferably about 1% by weight to about 15% by weight of acrylic acid, methacrylic acid, ethylacrylic acid, 2-(meth)acrylamidoglycolic acid, N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, 2-aminoethyl(meth)acrylate, 2-methylaminoethyl(meth)acrylate, 2-ethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 3-methylaminopropyl(meth)acrylate (2) a copolymer that is the polymerization product of a composition comprising at least one non-reactive hydrophilic vinyl monomer selected from the group consisting of acryamide, N,N-dimethylacrylamide, N-vinylpyrrolidone, (meth)acryloyloxyethyl phosphorylcholine, N-vinyl-N-methylacetamide, glycerol (meth)acrylate, hydroxyethyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, C1-C4-alkoxy polyethylene glycol (meth)acrylate having a weight average molecular weight of up to 400 Daltons, vinyl alcohol, and combinations thereof; The non-reactive hydrophilic vinyl monomers herein include alkyl(meth)acrylamides (any one of the above), N-2-dimethylaminoethyl(meth)acrylamide, dimethylaminoethyl(meth)acrylate, hydroxyl-containing acrylic monomers (any one of the above), N-vinylamide monomers (any one of the above), methylene-containing pyrrolidone monomers (i.e., pyrrolidone derivatives each having a methylene group attached to the pyrrolidone ring at the 3- or 5-position) (any one of the above), acrylic monomers having a C1-C4 alkoxyethoxy group (any one of the above), vinyl ether monomers (any one of the above), allyl ether monomers (any one of the above), phosphorylcholine-containing vinyl monomers (any one of the above). and combinations thereof (preferably, (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloylamino]ethyl-2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl-2'-(trimethylammonio)ethyl phosphate, (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxylethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, glycerol methacrylate (GMA), tetra(ethylene glycol) (meth)acrylate, poly(ethylene glycol) ethyl (meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol) (meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, N-vinylformamide, N-vinylacetamide, 1-methyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, tetra(ethylene glycol) methyl ether (meth)acrylate, methoxypoly(ethylene glycol)ethyl (meth)acrylamide having a number average molecular weight of up to 1500, C1-C4-alkoxypolyethylene glycol (meth)acrylate having a weight average molecular weight of up to 1500, tetra(ethylene glycol) monovinyl ether, poly(ethylene glycol) monovinyl ether, tetra(ethylene glycol) methyl vinyl ether, poly(ethylene glycol) methyl vinyl ether, tetra(ethylene glycol) monoallyl ether, poly(ethylene glycol) monoallyl ether, tetra(ethylene glycol) methyl allyl ether, poly(ethylene glycol) methyl allyl ether, vinyl alcohol, allyl alcohol, and combinations thereof are preferably selected from the group consisting of (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, and the like. Folic acid, 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-[(meth)acryloylamino]ethyl-2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl-2'-(trimethylammonio)ethyl phosphate, (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxyethyl(meth)acrylamide, N,and (meth)acrylamide, N-bis(hydroxyethyl)(meth)acrylamide, N-2,3-dihydroxypropyl(meth)acrylamide, N-tris(hydroxymethyl)methyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, glycerol methacrylate (GMA), poly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol)(meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, methoxypoly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, methoxypolyethylene glycol(meth)acrylate having a weight average molecular weight of up to 1500, poly(ethylene glycol)monovinyl ether, poly(ethylene glycol)methylvinyl ether, poly(ethylene glycol)monoallyl ether, poly(ethylene glycol)methylallyl ether, vinyl alcohol, allyl alcohol, and combinations thereof, and even more preferably selected from the group consisting of (meth)acryloyloxyethyl phosphonic acid esters. lylcholine, (meth)acryloyloxypropylphosphorylcholine, 2-[(meth)acryloylamino]ethyl-2'-(trimethylammonio)ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, (meth)acrylamide, dimethyl(meth)acrylamide, N-2-hydroxyethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-2,3-dihydroxypropyl(meth)acrylamide, N-tris(hydroxymethyl )methyl(meth)acrylamide, poly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, poly(ethylene glycol)(meth)acrylate having a number average molecular weight of up to 1500, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, methoxypoly(ethylene glycol)ethyl(meth)acrylamide having a number average molecular weight of up to 1500, methoxypolyethylene glycol(meth)acrylate having a weight average molecular weight of up to 1500, and combinations thereof.
[0243] Functionalized PEGs and functionalized multi-armed PEGs can be obtained from a variety of commercial sources, such as Creative PEGWorks, Polyscience, and Shearwater Polymers.
[0244] Monoamino-, monocarboxyl-, diamino-, or dicarboxyl-terminated homo- or copolymers of one or more nonreactive hydrophilic vinyl monomers or phosphorylcholine-containing vinyl monomers can be prepared according to the procedures described in U.S. Patent No. 6,218,508. For example, to prepare diamino- or dicarboxyl-terminated homo- or copolymers of nonreactive hydrophilic vinyl monomers, a nonreactive vinyl monomer, a chain transfer agent having an amino or carboxyl group (e.g., 2-aminoethanethiol, 2-mercaptopropionic acid, thioglycolic acid, thiolactic acid, or other hydroxymercaptans, aminomercaptans, or carboxyl-containing mercaptans), and optionally other vinyl monomers are copolymerized (thermally or actinically) with a reactive vinyl monomer (having an amino or carboxyl group) in the presence of a free radical initiator. Typically, the molar ratio of the chain transfer agent to all vinyl monomers other than the reactive vinyl monomer is about 1:5 to about 1:100, where the molar ratio of the chain transfer agent to the reactive vinyl monomer is 1:1. In such preparations, a chain transfer agent having an amino or carboxyl group is used to control the molecular weight of the resulting hydrophilic polymer and terminate the resulting hydrophilic polymer, thereby imparting one terminal amino or carboxyl group to the resulting hydrophilic polymer, while the reactive vinyl monomer imparts the other terminal carboxyl or amino group to the resulting hydrophilic polymer. Similarly, to prepare monoamino- or monocarboxyl-terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers, the non-reactive vinyl monomer, a chain transfer agent having an amino or carboxyl group (e.g., 2-aminoethanethiol, 2-mercaptopropionic acid, thioglycolic acid, thiolactic acid, or other hydroxymercaptans, aminomercaptans, or carboxyl-containing mercaptans), and optionally other vinyl monomers are copolymerized (thermally or actinically) in the absence of any reactive vinyl monomer.
[0245] Copolymers containing non-reactive hydrophilic vinyl monomers and reactive vinyl monomers (e.g., carboxyl-containing vinyl monomers, primary amino-group-containing vinyl monomers, or secondary amino-group-containing vinyl monomers) can be prepared according to any well-known radical polymerization method or obtained from commercial suppliers. Copolymers containing methacryloyloxyethyl phosphorylcholine and carboxyl-containing vinyl monomers (or amino-containing vinyl monomers) can be obtained from NOF Corporation (e.g., LIPIDURE®-A and -AF) or can be prepared according to the procedures described in U.S. Pat. No. 9,127,099.
[0246] The weight average molecular weight M of a hydrophilic polymer (as a hydrophilic enhancer) having at least one amino, carboxyl, or thiol group w is preferably about 500 to about 5,000,000, more preferably about 1,000 to about 2,000,000, and even more preferably about 5,000 to about 1,000,000 daltons.
[0247] Water-soluble and thermally crosslinkable hydrophilic polymeric materials can be prepared according to the processes disclosed in U.S. Patent Application Publication Nos. 2016 / 0061995A1 and 2013 / 0337160A1, and U.S. Patent No. 8,529,057.
[0248] In a preferred embodiment, the water-soluble, thermally crosslinkable polymeric material can be obtained by heating a reactive aqueous solution containing at least one azetidinium-containing polymer and at least one hydrophilicity enhancing agent (i.e., wetting agent) having at least one reactive functional group selected from the group consisting of amino, carboxyl, thiol, and combinations thereof, to a temperature of about 35°C to about 85°C and maintaining the temperature for a sufficient period of time (about 8 hours or less, preferably about 5 hours, more preferably about 2 hours to about 4 hours). The reactive aqueous solution preferably contains about 70 mM to about 170 mM (preferably about 90 mM to about 150 mM, more preferably about 100 mM to about 130 mM) of one or more ionic compounds and a pH of at least 8.0 (preferably at least 8.5, more preferably at least 9.0, and even more preferably at least 9.5). It should be understood that the reaction time should be long enough to covalently bond the hydrophilicity enhancing agent onto the polymer chain of the azetidinium-containing polymer, but short enough not to consume all of the azetidinium groups on the azetidinium-containing polymer and not to form too many crosslinks between the azetidinium-containing polymer and the hydrophilicity enhancing agent to form a gel (i.e., not be water-soluble). The resulting polymeric material is a lightly crosslinked polymeric material with a highly branched structure that still contains thermally crosslinkable azetidinium groups.
[0249] Those skilled in the art are familiar with methods for adjusting the pH of the reactive mixture, for example, by adding a base (e.g., NaOH, KOH, NH4OH, or mixtures thereof) or an acid (e.g., HCl, H2SO4, H3PO4, citric acid, acetic acid, boric acid, or mixtures thereof).
[0250] According to the present invention, any ionic compound can be used in the reactive mixture. Preferably, the ionic compound is one used as an ionic tonicity adjuster and an ionic buffer in ophthalmic solutions. Examples of preferred ionic tonicity adjusters include, but are not limited to, sodium chloride, potassium chloride, and combinations thereof. Examples of preferred ionic buffers include various salts of phosphoric acid (e.g., NaH2PO4, Na2HPO4, Na3PO4, KH2PO4, K2HPO4, K3PO4, or mixtures thereof), various salts of boric acid (e.g., sodium borate, potassium borate, or mixtures thereof), various salts of citric acid (e.g., monosodium citrate, disodium citrate, trisodium citrate, monopotassium citrate, dipotassium citrate, tripotassium citrate, or mixtures thereof), and various salts of carbonate (e.g., Na2CO3, NaHCO3, K2CO3, KHCO3, or mixtures thereof).
[0251] A reactive aqueous solution for preparing a water-soluble thermally crosslinkable polymeric material can be prepared by dissolving a desired amount of an azetidinium-containing polymer, a desired amount of a hydrophilicity enhancing agent having at least one reactive functional group, and a desired amount of other components (e.g., an ionic buffer, an ionic tonicity adjuster, etc.) in water (or a mixture of water and a small amount of a water-soluble organic solvent) to form an aqueous solution, and then adjusting the pH of the aqueous solution as needed.
[0252] According to the present invention, the concentration ratio of the hydrophilicity enhancing agent to the azetidinium-containing polymer in the reactive aqueous solution must be selected so as not to render the resulting water-soluble, thermally crosslinkable polymer material water-insoluble (i.e., solubility of less than 0.005 g per 100 mL of water at room temperature) and not to consume more than about 99%, preferably about 98%, more preferably about 97%, and even more preferably about 96% of the azetidinium groups of the azetidinium-containing polymer.
[0253] In a preferred embodiment, the reactive aqueous solution contains 0.01 wt % to about 10 wt % (preferably 0.05 wt % to about 5 wt %, more preferably 0.08 wt % to about 1 wt %, and even more preferably 0.1 wt % to about 0.4 wt %) of the azetidinium-containing polymer and about 0.01 wt % to about 10 wt % (preferably 0.02 wt % to about 5 wt %, more preferably 0.05 wt % to about 2 wt %, and even more preferably 0.08 wt % to about 1.0 wt %) of a hydrophilicity enhancer having at least one reactive functional group (carboxyl, primary amino, secondary amino group), and the concentration ratio of the azetidinium-containing polymer to the hydrophilicity enhancer is about 1000:1 to 1:1000 (preferably about 500:1 to about 1:500, more preferably about 250:1 to about 1:250, and even more preferably about 100:1 to about 1:100).
[0254] In a preferred embodiment, the water-soluble, thermally crosslinkable polymeric material comprises (i) about 20% to about 95% by weight of a first polymer chain derived from polyamidoamine-epichlorohydrin or poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin, and (ii) about 5% to about 80% by weight of a hydrophilic portion or second polymer chain derived from at least one hydrophilicity enhancing agent having at least one reactive functional group selected from the group consisting of an amino group, a carboxyl group, a thiol group, and a combination thereof, preferably a carboxyl or thiol group, wherein the hydrophilic portion or second polymer chain is derived from one azetidinium group of the polyamidoamine-epichlorohydrin or poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin, respectively. (iii) an azetidinium group that is part of the first polymer chain or is a pendant or terminal group covalently attached to the first polymer chain. The composition of the chemically modified poly(2-oxazoline-co-ethyleneimine)-epichlorohydrin or chemically modified polyamidoamine-epichlorohydrin is determined by the composition of the reaction mixture (based on the total weight of the reactants) used to prepare such polymers, according to the crosslinking reaction shown in Scheme I above. For example, if the reaction mixture contains about 75 wt. % polyamidoamine-epichlorohydrin and about 25 wt. % at least one hydrophilic enhancing agent, based on the total weight of the reactants, the resulting chemically modified polyamidoamine-epichlorohydrin will contain about 75 wt. % first polymer chains derived from polyamioamine-epichlorohydrin and about 25 wt. % hydrophilic moieties or second polymer chains derived from the at least one hydrophilic enhancing agent.
[0255] In accordance with the present invention, a preformed contact lens having an anchor layer thereon is heated in an aqueous solution containing a thermally crosslinkable hydrophilic polymeric material having azetidinium groups and, optionally (but preferably), amino groups, thiol groups, carboxyl groups, or combinations thereof, at a temperature of about 60°C to about 140°C for a period sufficient to crosslink the thermally crosslinkable hydrophilic polymeric material and simultaneously covalently bond the crosslinked thermally crosslinkable hydrophilic polymeric material onto the anchor layer to form a water gradient contact lens.
[0256] Preferably, the heating step is carried out by autoclaving a preformed contact lens having an anchor layer thereon, immersed in an aqueous coating solution, which is a packaging solution (i.e., a buffered aqueous solution having a pH of 6.7 to 7.6) in a sealed lens package, at a temperature of about 115°C to about 125°C for about 20 to 90 minutes. During autoclaving, it is believed that those azetidinium groups not involved in the crosslinking reaction can be hydrolyzed to 2,3-dihydroxypropyl (HO-CH-CH(OH)-CH-) groups, and that azetidinium-containing polymeric materials present in the lens packaging solution, if applicable, can be converted to non-reactive polymeric wetting agents capable of improving lens insertion comfort. As a result, the second aqueous coating solution is ophthalmically safe after autoclaving.
[0257] Those skilled in the art are familiar with lens packages (or containers) for autoclaving and storing contact lenses. Any lens package can be used in the present invention. Preferably, the lens package is a blister package comprising a base and a cover, the cover being removably sealed to the base, and the base comprising a cavity for receiving a sterile packaging solution and a contact lens.
[0258] The lenses are packaged in individual packages, sealed, and sterilized (e.g., by autoclaving at or above about 120°C under pressure for at least 30 minutes) before being distributed to users. Those skilled in the art will be familiar with methods for sealing and sterilizing lens packages.
[0259] In accordance with the present invention, the packaging solution contains at least one buffer and one or more other ingredients known to those skilled in the art, including, but not limited to, tonicity agents, surfactants, antibacterial agents, preservatives, and lubricants (e.g., cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone).
[0260] The packaging solution contains a buffering agent in an amount sufficient to maintain the pH of the packaging solution within a desired range, e.g., a physiologically acceptable range, preferably about 6.5 to about 7.5. Any known physiologically compatible buffering agent may be used. Buffering agents suitable for use as components of the contact lens care compositions of the present invention are known to those skilled in the art. Examples are boric acid, borates such as sodium borate, citric acid, citrates such as potassium citrate, bicarbonates such as sodium bicarbonate, tris (i.e. 2-amino-2-hydroxymethyl-1,3-propanediol), bis-tris [i.e. bis-(2-hydroxyethyl)-imino-tris-(hydroxymethyl)-methane], bis-trispropane [i.e. 1,3-bis(tris(hydroxymethyl)methylamino)propane], bis-aminopolyols, triethanolamine, ACES [i.e. N-(2-hydroxyethyl)-2-aminoethanesulfonic acid], BES [i.e. N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid], HEPES [ i.e., 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid], MES [i.e., 2-(N-morpholino)ethanesulfonic acid], MOPS [i.e., 3-[N-morpholino]-propanesulfonic acid], PIPES [i.e., piperazine-N,N'-bis(2-ethanesulfonic acid)], TES {i.e., N-[tris(hydroxymethyl)methyl]-2-aminoethanesulfonic acid}, salts thereof, phosphate buffers such as NaHPO, NaHPO, and KHPO, or mixtures thereof. The amount of each buffer in the packaging solution is preferably 0.001% to 2% by weight, preferably 0.01% to 1% by weight, and most preferably about 0.05% to about 0.30% by weight.
[0261] The packaging solution has a tonicity of about 200 to about 450 milliosmoles (mOsm), preferably about 250 to about 350 mOsm. The tonicity of the packaging solution can be adjusted by adding organic or inorganic substances that affect tonicity. Suitable ophthalmically acceptable tonicity agents include, but are not limited to, sodium chloride, potassium chloride, glycerol, propylene glycol, polyols, mannitol, sorbitol, xylitol, and mixtures thereof.
[0262] The packaging solution of the present invention has a viscosity of about 1 centipoise to about 5 centipoise at 25°C.
[0263] In a preferred embodiment, the packaging solution preferably comprises from about 0.01% to about 2% by weight, more preferably from about 0.05% to about 1.5% by weight, even more preferably from about 0.1% to about 1% by weight, and most preferably from about 0.2% to about 0.5% by weight of a water-soluble, thermally crosslinkable hydrophilic polymeric material having azetidinium groups.
[0264] The resulting water gradient contact lens can then be heated at a temperature of 40° C. to 140° C. in an aqueous solution containing a polyaziridine having a number average molecular weight of about 2000 daltons or less and at least two aziridine groups in an amount sufficient to provide a water gradient contact lens having a PU of about 0.40 or 0.30 micrograms / lens or less (preferably about 0.20 micrograms / lens or less, more preferably about 0.15 micrograms / lens or less, even more preferably about 0.10 micrograms / lens or less, and most preferably about 0.05 micrograms / lens or less). Preferably, the aqueous solution is a lens packaging solution containing the necessary polyaziridine in addition to all of the necessary components described above for the lens packaging solution.
[0265] Any polyaziridine can be used in the present invention to neutralize the negative charges present in water gradient contact lenses. Examples of preferred polyaziridines include, but are not limited to, trimethylolpropane tris(2-methyl-1-aziridinepropionate) (also known as PZ-28), pentaerythritol tris[3-(1-aziridinyl)propionate] (also known as PZ-33), trimethylolpropane tris(3-aziridinopropionate), the Michael reaction product of a vinyl crosslinker having at least two (meth)acryloyl groups with 2-methylaziridine (or aziridine), and combinations thereof. Preferably, polyaziridines containing at least methyl-aziridinyl groups are used in the present invention.
[0266] In an alternative process for manufacturing the contact lenses of the present invention, in a process for preparing a water gradient contact lens, a contact lens precursor having an anchor layer thereon is heated in an aqueous solution containing a thermally crosslinkable hydrophilic polymer material (any one of those described above) in the presence of a polyaziridine having a number average molecular weight of about 2000 daltons or less and at least two aziridine groups. For example, a preformed contact lens having an anchor layer thereon is first contacted with a solution containing such a polyaziridine at room temperature or below to add the polyaziridine to the preformed contact lens, and then the polyaziridine-loaded contact lens having an anchor layer thereon is heated in an aqueous solution containing a thermally crosslinkable hydrophilic polymer material (any one of those described above) at a temperature of about 60°C to about 140°C to form the contact lens of the present invention. Alternatively, a preformed contact lens having an anchor layer thereon is heated in an aqueous solution containing a thermally crosslinkable hydrophilic polymer material (any one of those described above) and polyaziridine at a temperature of about 60°C to about 140°C to form the contact lens of the present invention.
[0267] Several alternative processes for manufacturing the contact lenses of the present invention are illustrated in the Examples section.
[0268] Although various embodiments of the present invention have been described using specific terms, devices, and methods, such description is for purposes of illustration only. The words used are words of description rather than of limitation. As will be apparent to those skilled in the art, many variations and modifications of the present invention are possible without departing from the spirit and scope of the novel concepts of the present disclosure. Furthermore, it should be understood that aspects of the various embodiments of the present invention may be interchangeable, in whole or in part, or may be combined and / or used together in any manner, as set forth below.
[0269] Embodiment 1 1. A contact lens having a polyquaternium-1 uptake ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less) and a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, the contact lens comprising an anterior surface and an opposite posterior surface, and a layered structural morphology comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer, the inner layer having a first equilibrium water content of about 70% by weight or less. and The front and rear outer hydrogel layers, which are independent of each other, have a thickness of about 0.25 μm to about 25 μm when fully hydrated. and a second equilibrium water content greater than the first equilibrium water content, and the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 140%.
[0270] Embodiment 2 1. A contact lens having a polyquaternium-1 uptake ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less) and a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, the contact lens comprising an anterior surface and an opposite posterior surface, and a layered structural morphology comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer, the inner layer having a first equilibrium water content of about 70% by weight or less. and The front and rear outer hydrogel layers, which are independent of each other, have a thickness of about 0.25 μm to about 25 μm when fully hydrated. and a second equilibrium water content greater than the first equilibrium water content, and the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 140%.
[0271] Embodiment 3 3. The contact lens of embodiment 1 or 2, wherein the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 170%.
[0272] Embodiment 4 3. The contact lens of embodiment 1 or 2, wherein the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 200%.
[0273] Embodiment 5 3. The contact lens of embodiment 1 or 2, wherein the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 250%.
[0274] Embodiment 6 3. The contact lens of embodiment 1 or 2, wherein the separate anterior and posterior outer hydrogel layers have a water swelling rate of at least 300%.
[0275] Embodiment 7 a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasive cycling; a water content gradient that increases from the interior to one of the anterior or posterior surfaces of the contact lens, A contact lens comprising a lens bulk material completely coated with a front outer hydrogel layer and a rear outer hydrogel layer, the independent front and rear outer hydrogel layers having a thickness of about 0.25 μm to about 25 μm when fully hydrated, the lens bulk material having a first equilibrium water content of about 70% or less by weight, and the independent front and rear outer hydrogel layers having a second equilibrium water content that is at least 1.2 times the first equilibrium water content and is at least 80% by weight.
[0276] Embodiment 8 a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling; a water content gradient that increases from the inside to the outside of the contact lens, A contact lens comprising a lens bulk material completely coated with a front outer hydrogel layer and a rear outer hydrogel layer, the independent front and rear outer hydrogel layers having a thickness of about 0.25 μm to about 25 μm when fully hydrated, the lens bulk material having a first equilibrium water content of about 70% or less by weight, and the independent front and rear outer hydrogel layers having a second equilibrium water content that is at least 1.2 times the first equilibrium water content and is at least 80% by weight.
[0277] Embodiment 9 a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, Contact lenses are an anterior surface and an opposite posterior surface, and a layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, an anterior outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer; A contact lens wherein each of the separate anterior and posterior outer hydrogel layers has a surface modulus that is reduced by at least about 20% compared to the inner layer.
[0278] Embodiment 10 a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, Contact lenses are an anterior surface and an opposite posterior surface, and a layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, an anterior outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer; A contact lens wherein each of the separate anterior and posterior outer hydrogel layers has a surface modulus that is reduced by at least about 20% compared to the inner layer.
[0279] Embodiment 11 11. The contact lens of embodiment 9 or 10, wherein the separate anterior and posterior outer hydrogel layers each have a surface modulus that is reduced by at least 25% compared to the inner layer.
[0280] Embodiment 12 11. The contact lens of embodiment 9 or 10, wherein the separate anterior and posterior outer hydrogel layers each have a surface modulus that is reduced by at least 30% compared to the inner layer.
[0281] Embodiment 13 11. The contact lens of embodiment 9 or 10, wherein the separate anterior and posterior outer hydrogel layers each have a surface modulus that is reduced by at least about 35% compared to the inner layer.
[0282] Embodiment 14 11. The contact lens of embodiment 9 or 10, wherein the separate anterior and posterior outer hydrogel layers each have a surface modulus that is reduced by at least 40% compared to the inner layer.
[0283] Embodiment 15 a normalized surface compressive force at an indentation depth of 400 nm of approximately 12 μN / MPa or less as measured by microindentation testing using a 1 mm microindentation probe; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, The contact lens has an anterior surface, an opposite posterior surface, and a layered structural configuration, the layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer.
[0284] Embodiment 16 a normalized surface compressive force at an indentation depth of 400 nm of approximately 12 μN / MPa or less as measured by microindentation testing using a 1 mm microindentation probe; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, The contact lens has an anterior surface, an opposite posterior surface, and a layered structural configuration, the layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer.
[0285] Embodiment 17 a normalized surface compressive force at an indentation depth of 400 nm of approximately 12 μN / MPa or less as measured by microindentation testing using a 1 mm microindentation probe; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, A contact lens comprises a lens bulk material that is a polymeric material.
[0286] Embodiment 18 a normalized surface compressive force at an indentation depth of 400 nm of approximately 12 μN / MPa or less as measured by microindentation testing using a 1 mm microindentation probe; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, A contact lens comprises a lens bulk material that is a polymeric material.
[0287] Embodiment 19 19. The contact lens of any one of embodiments 15-18, wherein the contact lens has a normalized surface compressive force at an indentation depth of 400 nm of less than or equal to about 10 μN / MPa.
[0288] Embodiment 20 19. The contact lens of any one of embodiments 15-18, wherein the contact lens has a normalized surface compressive force at an indentation depth of 400 nm of about 8 μN / MPa or less.
[0289] Embodiment 21 19. The contact lens of any one of embodiments 15-18, wherein the contact lens has a normalized surface compressive force at an indentation depth of 400 nm of about 6 μN / MPa or less.
[0290] Embodiment 22 19. The contact lens of any one of embodiments 15-18, wherein the contact lens has a normalized surface compressive force at an indentation depth of 400 nm of less than or equal to about 4 μN / MPa.
[0291] Embodiment 23 A reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), of about 50% or more (preferably about 55% or more, more preferably about 60% or more, even more preferably about 65% or more, and most preferably about 70% or more). 400nm and, a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, The contact lens has an anterior surface, an opposite posterior surface, and a layered structural configuration, the layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer.
[0292] Embodiment 24 A reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), of about 50% or more (preferably about 55% or more, more preferably about 60% or more, even more preferably about 65% or more, and most preferably about 70% or more). 400nm and, a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, The contact lens has an anterior surface, an opposite posterior surface, and a layered structural configuration, the layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, a front outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer.
[0293] Embodiment 25 A reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), of about 50% or more (preferably about 55% or more, more preferably about 60% or more, even more preferably about 65% or more, and most preferably about 70% or more). 400nm and, a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasion cycling, A contact lens comprises a lens bulk material that is a polymeric material.
[0294] Embodiment 26 A reduction in indentation force at an indentation depth of 400 nm, i.e., Δ(IF), of about 50% or more (preferably about 55% or more, more preferably about 60% or more, even more preferably about 65% or more, and most preferably about 70% or more). 400nm and, a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling, A contact lens comprises a lens bulk material that is a polymeric material.
[0295] Embodiment 27 Δ(IF) 400nm was determined by nanoindentation testing using a probe with a tip radius of approximately 9.0±0.9 μm,
number
[0296] Embodiment 28 Δ(IF) 400nm was determined by microindentation testing using a 1 mm hemispherical borosilicate glass probe,
number
[0297] Embodiment 29 Δ(IF) 400nm The contact lens of any one of embodiments 23 to 28, wherein the tensile strength is about 55% or greater.
[0298] Embodiment 30 Δ(IF) 400nm The contact lens of any one of embodiments 23 to 28, wherein the tensile strength is about 60% or greater.
[0299] Embodiment 31 Δ(IF) 400nm The contact lens of any one of embodiments 23 to 28, wherein the tensile strength is about 65% or greater.
[0300] Embodiment 32 Δ(IF) 400nm The contact lens of any one of embodiments 23 to 28, wherein the tensile strength is about 70% or greater.
[0301] Embodiment 33 33. The contact lens of any one of embodiments 1-32, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.20 micrograms / lens or less.
[0302] Embodiment 34 33. The contact lens of any one of embodiments 1-32, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.15 micrograms / lens or less.
[0303] Embodiment 35 33. The contact lens of any one of embodiments 1-32, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.10 micrograms / lens or less.
[0304] Embodiment 36 33. The contact lens of any one of embodiments 1-32, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.075 micrograms / lens or less.
[0305] Embodiment 37 33. The contact lens of any one of embodiments 1-32, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.050 micrograms / lens or less.
[0306] Embodiment 38 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing.
[0307] Embodiment 39 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 12.5 seconds after 30 cycles of finger rubbing.
[0308] Embodiment 40 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 15 seconds after 30 cycles of finger rubbing.
[0309] Embodiment 41 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 17.5 seconds after 30 cycles of finger rubbing.
[0310] Embodiment 42 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 20 seconds after 30 cycles of finger rubbing.
[0311] Embodiment 43 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 10 seconds after a simulated abrasion cycling treatment.
[0312] Embodiment 44 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 12.5 seconds after a simulated abrasion cycling treatment.
[0313] Embodiment 45 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 15 seconds after a simulated abrasion cycling treatment.
[0314] Embodiment 46 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 17.5 seconds after a simulated abrasion cycling treatment.
[0315] Embodiment 47 38. The contact lens of any one of embodiments 1-37, wherein the contact lens has a water disintegration time of at least 20 seconds after a simulated abrasion cycling treatment.
[0316] Embodiment 48 48. The contact lens of any one of embodiments 1-47, wherein the inner layer or lens bulk material is a preformed hard contact lens made essentially of a hard plastic material.
[0317] Embodiment 49 49. The contact lens of embodiment 48, wherein the hard plastic material is a crosslinked polymethacrylate.
[0318] Embodiment 50 48. The contact lens of any one of embodiments 1-47, wherein the inner layer or lens bulk material is a preformed rigid gas permeable contact lens made essentially of a rigid gas permeable lens material.
[0319] Embodiment 51 51. The contact lens of any one of embodiments 48-50, wherein each separate anterior and posterior outer hydrogel layer has a thickness of about 1.0 μm to about 20 μm when fully hydrated.
[0320] Embodiment 52 51. The contact lens of any one of embodiments 48-50, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 2.0 μm to about 15 μm when fully hydrated.
[0321] Embodiment 53 51. The contact lens of any one of embodiments 48-50, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 2.0 μm to about 10 μm when fully hydrated.
[0322] EMBODIMENT 54 51. The contact lens of any one of embodiments 48-50, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 2.5 μm to about 8 μm when fully hydrated.
[0323] Embodiment 55 48. The contact lens of any one of embodiments 1-47, wherein the inner layer or lens bulk material is a preformed soft silicone contact lens made essentially of cross-linked silicone material.
[0324] Embodiment 56 56. The contact lens of embodiment 55, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 2.0 μm to about 25 μm when fully hydrated.
[0325] Embodiment 57 56. The contact lens of embodiment 55, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 3.0 μm to about 25 μm when fully hydrated.
[0326] Embodiment 58 56. The contact lens of embodiment 55, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 4.0 μm to about 20 μm when fully hydrated.
[0327] Embodiment 59 56. The contact lens of embodiment 55, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 5.0 μm to about 20 μm when fully hydrated.
[0328] Embodiment 60 48. The contact lens of any one of embodiments 1 to 47, wherein the inner layer or lens bulk material is a preformed hybrid contact lens having a central optic zone made essentially of a rigid gas permeable lens material, surrounded by a peripheral zone made essentially of a non-silicone hydrogel material.
[0329] Embodiment 61 48. The contact lens of any one of embodiments 1-47, wherein the inner layer or lens bulk material is a preformed non-silicone hydrogel contact lens made essentially of a non-silicone hydrogel material.
[0330] Embodiment 62 62. The contact lens of embodiment 60 or 61, wherein the non-silicone hydrogel material comprises at least 50 mole % repeat units of at least one hydroxyl-containing vinyl monomer.
[0331] Embodiment 63 63. The contact lens of embodiment 62, wherein the at least one hydroxyl-containing vinyl monomer is selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, N-2-hydroxyethyl (meth)acrylamide, N-3-hydroxypropyl (meth)acrylamide, N-2-hydroxypropyl (meth)acrylamide, N-2,3-dihydroxypropyl (meth)acrylamide, N-tris(hydroxymethyl)methyl (meth)acrylamide, vinyl alcohol, allyl alcohol, and combinations thereof.
[0332] EMBODIMENT 64 63. The contact lens of embodiment 62, wherein the at least one hydroxyl-containing vinyl monomer is selected from the group consisting of hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and vinyl alcohol.
[0333] Embodiment 65 65. The contact lens of any one of embodiments 60-64, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.25 μm to about 20 μm when fully hydrated.
[0334] Embodiment 66 65. The contact lens of any one of embodiments 60 to 64, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.50 μm to about 15 μm when fully hydrated.
[0335] Embodiment 67 65. The contact lens of any one of embodiments 60 to 64, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.5 μm to about 10 μm when fully hydrated.
[0336] Embodiment 68 65. The contact lens of any one of embodiments 60 to 64, wherein the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.5 μm to about 6 μm when fully hydrated.
[0337] Embodiment 69 48. The contact lens of any one of embodiments 1-47, wherein the separate inner layer and bulk lens material are a preformed contact lens made essentially from a silicone hydrogel material.
[0338] Embodiment 70 70. The contact lens of embodiment 69, wherein the silicone hydrogel material comprises at least one polysiloxane vinyl monomer repeat unit.
[0339] Embodiment 71 71. The contact lens of embodiment 69 or 70, wherein the silicone hydrogel material comprises at least one polysiloxane vinyl crosslinker repeat unit.
[0340] Embodiment 72 72. The contact lens of any one of embodiments 69 to 71, wherein the silicone hydrogel material comprises repeating units of at least one hydrophilic vinyl monomer.
[0341] Embodiment 73 73. The contact lens of any one of embodiments 69 to 72, wherein the silicone hydrogel material comprises repeating units of at least one hydrophilic N-vinylamide monomer.
[0342] EMBODIMENT 74 74. The contact lens of any one of embodiments 69 to 73, wherein the silicone hydrogel material comprises repeating units of at least one polycarbosiloxane vinyl monomer.
[0343] Embodiment 75 75. The contact lens of any one of embodiments 69 to 74, wherein the silicone hydrogel material comprises at least one polycarbosiloxane vinyl crosslinker repeat unit.
[0344] Embodiment 76 76. The contact lens of any one of embodiments 69 to 75, wherein the silicone hydrogel material comprises repeating units of at least one silicone-containing vinyl monomer having a bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl group.
[0345] Embodiment 77 77. The contact lens of any one of embodiments 69-76, wherein the silicone hydrogel material comprises repeat units of one or more blended vinyl monomers.
[0346] Embodiment 78 77. A contact lens according to any one of embodiments 69 to 76, wherein the silicone hydrogel material comprises repeat units of one or more blended vinyl monomers in an amount of about 25% by weight or less, based on the dry weight of the inner layer of the silicone hydrogel material.
[0347] Embodiment 79 77. A contact lens according to any one of embodiments 69 to 76, wherein the silicone hydrogel material comprises repeat units of one or more blended vinyl monomers in an amount of about 20% by weight or less, based on the dry weight of the inner layer of the silicone hydrogel material.
[0348] Embodiment 80 77. A contact lens according to any one of embodiments 69 to 76, wherein the silicone hydrogel material comprises repeat units of one or more blended vinyl monomers in an amount of about 15% by weight or less, based on the dry weight of the inner layer of the silicone hydrogel material.
[0349] Embodiment 81 81. The contact lens of any one of embodiments 69 to 80, wherein the silicone hydrogel material comprises repeating units of one or more non-silicone vinyl crosslinkers.
[0350] Embodiment 82 81. The contact lens of any one of embodiments 69-80, wherein the silicone hydrogel material comprises repeating units of one or more non-silicone vinyl crosslinkers in an amount of about 1.0 wt. % or less, based on the dry weight of the inner layer.
[0351] Embodiment 83 81. The contact lens of any one of embodiments 69-80, wherein the silicone hydrogel material comprises repeating units of one or more non-silicone vinyl crosslinkers in an amount of about 0.8% by weight or less, based on the dry weight of the inner layer.
[0352] Embodiment 84 81. A contact lens according to any one of embodiments 69 to 80, wherein the silicone hydrogel material comprises repeating units of one or more non-silicone vinyl crosslinkers in an amount of about 0.05% to about 0.6% by weight based on the dry weight of the inner layer.
[0353] Embodiment 85 85. The contact lens of any one of embodiments 69 to 84, wherein the silicone hydrogel material has an oxygen permeability of at least about 50 barrers.
[0354] Embodiment 86 85. The contact lens of any one of embodiments 69 to 84, wherein the silicone hydrogel material has an oxygen permeability of at least about 60 barrers.
[0355] Embodiment 87 85. The contact lens of any one of embodiments 69 to 84, wherein the silicone hydrogel material has an oxygen permeability of at least about 70 barrers.
[0356] Embodiment 88 85. The contact lens of any one of embodiments 69 to 84, wherein the silicone hydrogel material has an oxygen permeability of at least about 90 barrers.
[0357] Embodiment 89 85. The contact lens of any one of embodiments 69 to 84, wherein the silicone hydrogel material has an oxygen permeability of at least about 110 barrers.
[0358] Embodiment 90 90. The contact lens of any one of embodiments 69-89, wherein the silicone hydrogel material has an equilibrium water content of about 10% to about 70% by weight.
[0359] Embodiment 91 90. The contact lens of any one of embodiments 69-89, wherein the silicone hydrogel material has an equilibrium water content of about 10% to about 65% by weight.
[0360] Embodiment 92 90. The contact lens of any one of embodiments 69-89, wherein the silicone hydrogel material has an equilibrium water content of about 10% to about 60% by weight.
[0361] Embodiment 93 90. The contact lens of any one of embodiments 69-89, wherein the silicone hydrogel material has an equilibrium water content of about 15% to about 55% by weight.
[0362] Embodiment 94 90. The contact lens of any one of embodiments 69-89, wherein the silicone hydrogel material has an equilibrium water content of about 15% to about 50% by weight.
[0363] Embodiment 95 95. A contact lens according to any one of embodiments 69 to 94, wherein the silicone hydrogel material is not naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.5 μm to about 25 μm when fully hydrated.
[0364] Embodiment 96 95. A contact lens according to any one of embodiments 69 to 94, wherein the silicone hydrogel material is not naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 1.0 μm to about 20 μm when fully hydrated.
[0365] Embodiment 97 95. A contact lens according to any one of embodiments 69 to 94, wherein the silicone hydrogel material is not naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 1.0 μm to about 15 μm when fully hydrated.
[0366] Embodiment 98 95. A contact lens according to any one of embodiments 69 to 94, wherein the silicone hydrogel material is not naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 1.5 μm to about 10 μm when fully hydrated.
[0367] Embodiment 99 99. A contact lens according to any one of embodiments 69 to 98, wherein the silicone hydrogel material is naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.25 μm to about 20 μm when fully hydrated.
[0368] Embodiment 100 99. A contact lens according to any one of embodiments 69 to 98, wherein the silicone hydrogel material is naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.5 μm to about 20 μm when fully hydrated.
[0369] Embodiment 101 99. A contact lens according to any one of embodiments 69 to 98, wherein the silicone hydrogel material is naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 0.5 μm to about 15 μm when fully hydrated.
[0370] Embodiment 102 99. A contact lens according to any one of embodiments 69 to 98, wherein the silicone hydrogel material is naturally wettable and the separate anterior and posterior outer hydrogel layers have a thickness of from about 1.0 μm to about 10 μm when fully hydrated.
[0371] Embodiment 103 103. The contact lens of any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers are a crosslinked hydrophilic polymeric material comprising at least 25 mol % repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of alkyl(meth)acrylamides, N-2-dimethylaminoethyl(meth)acrylamides, dimethylaminoethyl(meth)acrylates, hydroxyl-containing acrylic monomers, N-vinylamide monomers, methylene-containing pyrrolidone monomers, (meth)acrylate monomers having C1-C4 alkoxyethoxy groups, vinyl ether monomers, allyl ether monomers, and combinations thereof.
[0372] Embodiment 104 103. The contact lens of any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers are a crosslinked hydrophilic polymeric material comprising at least 35 mol % repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of alkyl(meth)acrylamides, N-2-dimethylaminoethyl(meth)acrylamides, dimethylaminoethyl(meth)acrylates, hydroxyl-containing acrylic monomers, N-vinylamide monomers, methylene-containing pyrrolidone monomers, (meth)acrylate monomers having C1-C4 alkoxyethoxy groups, vinyl ether monomers, allyl ether monomers, and combinations thereof.
[0373] Embodiment 105 103. The contact lens of any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers are a crosslinked hydrophilic polymeric material comprising at least 45 mol % repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of alkyl(meth)acrylamides, N-2-dimethylaminoethyl(meth)acrylamides, dimethylaminoethyl(meth)acrylates, hydroxyl-containing acrylic monomers, N-vinylamide monomers, methylene-containing pyrrolidone monomers, (meth)acrylate monomers having C1-C4 alkoxyethoxy groups, vinyl ether monomers, allyl ether monomers, and combinations thereof.
[0374] Embodiment 106 103. The contact lens of any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers are a crosslinked hydrophilic polymeric material comprising at least 55 mol % repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of alkyl(meth)acrylamides, N-2-dimethylaminoethyl(meth)acrylamides, dimethylaminoethyl(meth)acrylates, hydroxyl-containing acrylic monomers, N-vinylamide monomers, methylene-containing pyrrolidone monomers, (meth)acrylate monomers having C1-C4 alkoxyethoxy groups, vinyl ether monomers, allyl ether monomers, and combinations thereof.
[0375] Embodiment 107 103. The contact lens of any one of embodiments 1-102, wherein the separate anterior and posterior outer hydrogel layers are crosslinked hydrophilic polymeric materials comprising at least 25 mol % repeating monomer units of at least one phosphrylcholine-containing vinyl monomer.
[0376] Embodiment 108 103. The contact lens of any one of embodiments 1-102, wherein the separate anterior and posterior outer hydrogel layers are crosslinked hydrophilic polymeric materials comprising at least 35 mol % repeating monomer units of at least one phosphyrylcholine-containing vinyl monomer.
[0377] Embodiment 109 103. A contact lens according to any one of embodiments 1 to 102, wherein the separate anterior and posterior outer hydrogel layers are crosslinked hydrophilic polymeric materials comprising at least 45 mole % repeating monomer units of at least one phosphyrylcholine-containing vinyl monomer.
[0378] Embodiment 110 103. A contact lens according to any one of embodiments 1 to 102, wherein the separate anterior and posterior outer hydrogel layers are crosslinked hydrophilic polymeric materials comprising at least 55 mol % repeating monomer units of at least one phosphyrylcholine-containing vinyl monomer.
[0379] Embodiment 111 103. The contact lens of any one of embodiments 1-102, wherein the separate anterior and posterior outer hydrogel layers are cross-linked hydrophilic polymeric materials comprising poly(ethylene glycol) chains.
[0380] Embodiment 112 A contact lens according to any one of embodiments 1 to 102, wherein the anterior and posterior outer hydrogel layers, which are independent of each other, are crosslinked hydrophilic polymeric materials comprising: (1) pol(ethylene glycol) having only one functional group selected from the group consisting of -NH, -SH, or -COOH; (2) poly(ethylene glycol) having two terminal functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof; (3) multi-arm poly(ethylene glycol) having one or more functional groups selected from the group consisting of -NH, -COOH, -SH, and combinations thereof; or (4) poly(ethylene glycol) chains derived directly from combinations thereof.
[0381] Embodiment 113 A contact lens described in any one of embodiments 1 to 112, wherein the anterior and posterior outer hydrogel layers are identical to one another, are substantially uniform in thickness, and merge at the edge of the contact lens to completely cover the inner layer.
[0382] Embodiment 114 114. The contact lens of any one of embodiments 1-113, wherein the separate anterior and posterior outer hydrogel layers have an equilibrium water content of at least 80% by weight.
[0383] Embodiment 115 114. The contact lens of any one of embodiments 1-113, wherein the separate anterior and posterior outer hydrogel layers have an equilibrium water content of at least 85% by weight.
[0384] Embodiment 116 114. The contact lens of any one of embodiments 1-113, wherein the separate anterior and posterior outer hydrogel layers have an equilibrium water content of at least about 90% by weight.
[0385] Embodiment 117 114. The contact lens of any one of embodiments 1-113, wherein the separate anterior and posterior outer hydrogel layers have an equilibrium water content of at least 95% by weight.
[0386] Embodiment 118 118. The contact lens of any one of embodiments 1-117, wherein the separate anterior and posterior outer hydrogel layers are substantially free of silicone.
[0387] Embodiment 119 118. The contact lens of any one of embodiments 1-117, wherein the separate anterior and posterior outer hydrogel layers are completely silicone-free.
[0388] Embodiment 120 A contact lens described in any one of embodiments 1 to 119, wherein the contact lens further comprises two transition layers of polymeric material, each of the two transition layers being located between the inner layer or lens bulk material and one of the anterior and posterior outer hydrogel layers.
[0389] Embodiment 121 121. The contact lens of embodiment 120, wherein the two transitional layers merge at the peripheral edge of the contact lens and completely surround the inner layer of lens material or the lens bulk material.
[0390] Embodiment 122 122. The contact lens of embodiment 120 or 121, wherein the two transitional layers have a thickness of at least about 0.05 μm when fully hydrated.
[0391] Embodiment 123 122. The contact lens of embodiment 120 or 121, wherein the two transitional layers have a thickness of from about 0.05 μm to about 10 μm when fully hydrated.
[0392] Embodiment 124 122. The contact lens of embodiment 120 or 121, wherein the two transitional layers have a thickness of from about 0.1 μm to about 7.5 μm when fully hydrated.
[0393] Embodiment 125 122. The contact lens of embodiment 120 or 121, wherein the two transitional layers have a thickness of from about 0.1 μm to about 5 μm when fully hydrated.
[0394] Embodiment 126 126. The contact lens of any one of embodiments 120-125, wherein each of the two transitional layers is a layer of a polyanionic polymer neutralized and crosslinked with a polyaziridine having at least two aziridine groups and a number average molecular weight of 2000 Daltons or less.
[0395] Embodiment 127 127. The contact lens of embodiment 126, wherein the polyanionic polymer is a carboxyl-containing polymer comprising at least 60 mole % repeat units of one or more carboxyl-containing acrylic monomers.
[0396] Embodiment 128 127. The contact lens of embodiment 126, wherein the polyanionic polymer is polyacrylic acid, polymethacrylic acid, poly(ethylacrylic acid), poly(acrylic acid-co-methacrylic acid), poly[ethylacrylic acid-co-(meth)acrylic acid], poly(N,N-2-acrylamidoglycolic acid), poly[(meth)acrylic acid-co-acrylamide], poly[(meth)acrylic acid-co-vinylpyrrolidone], poly[ethylacrylic acid-co-acrylamide], poly[ethylacrylic acid-co-vinylpyrrolidone], poly[(meth)acrylic acid-co-vinyl acetate], poly[ethylacrylic acid-co-vinyl acetate], or a combination thereof.
[0397] Embodiment 129 127. The contact lens of embodiment 126, wherein the polyanionic polymer is a graft polymer that is grafted onto an inner layer or the lens bulk material, the graft polymer comprising repeating units of at least one carboxyl-containing vinyl monomer.
[0398] Embodiment 130 128. The contact lens of embodiment 127, wherein the polyanionic polymer is a graft polymer that is grafted onto an inner layer or the lens bulk material, the graft polymer comprising repeating units of at least one carboxyl-containing acrylic monomer.
[0399] Embodiment 131 131. The contact lens of any one of embodiments 126 to 130, wherein the polyaziridine is trimethylolpropane tris(2-methyl-1-aziridinepropionate), pentaerythritol tris[3-(1-aziridinyl)propionate], trimethylolpropane tris(3-aziridinopropionate), a Michael reaction product of a vinyl crosslinker having at least two (meth)acryloyl groups and 2-methylaziridine or aziridine, or a combination thereof.
[0400] Embodiment 132 A contact lens according to any one of embodiments 1 to 131, wherein the separate anterior and posterior outer hydrogel layers have a surface modulus that is reduced by at least about 25% compared to the inner layer.
[0401] Embodiment 133 132. A contact lens according to any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers have a surface modulus that is reduced by at least about 30% compared to the inner layer.
[0402] Embodiment 134 132. A contact lens according to any one of the preceding embodiments, wherein the separate anterior and posterior outer hydrogel layers have a surface modulus that is reduced by at least about 35% compared to the inner layer.
[0403] Embodiment 135 A contact lens according to any one of embodiments 1 to 131, wherein the separate anterior and posterior outer hydrogel layers have a surface modulus that is reduced by at least about 40% compared to the inner layer.
[0404] Embodiment 136 136. The contact lens of any one of embodiments 1-135, wherein the contact lens has a friction rating of about 1.5 or less after 30 cycles of finger rubbing.
[0405] Embodiment 137 136. The contact lens of any one of embodiments 1-135, wherein the contact lens has a friction rating of about 1.0 or less after 30 cycles of finger rubbing.
[0406] Embodiment 138 136. The contact lens of any one of embodiments 1-135, wherein the contact lens has a friction rating of about 0.5 or less after 30 cycles of finger rubbing.
[0407] Embodiment 139 an anterior surface and an opposite posterior surface; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing or simulated abrasive cycling; a structural configuration characterized by a cross-sectional surface-modulus profile along a shortest line between the anterior and posterior surfaces of a cross-sectional surface of the contact lens, the cross-sectional surface-modulus profile comprising an anterior-lateral zone including and proximal to the anterior surface, an inner zone including and peripheral to a central portion of the shortest line, and a posterior-lateral zone including and proximal to the posterior surface, The anterior lateral zone has a mean anterior surface elastic modulus
number
number
number
number
[0408] Embodiment 140 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 10 seconds after 30 cycles of finger rubbing.
[0409] Embodiment 141 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 12.5 seconds after 30 cycles of finger rubbing.
[0410] Embodiment 142 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 15 seconds after 30 cycles of finger rubbing.
[0411] Embodiment 143 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 17.5 seconds after 30 cycles of finger rubbing.
[0412] Embodiment 144 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 20 seconds after 30 cycles of finger rubbing.
[0413] Embodiment 145 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 10 seconds after a simulated abrasion cycling treatment.
[0414] Embodiment 146 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 12.5 seconds after a simulated abrasion cycling treatment.
[0415] Embodiment 147 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 15 seconds after a simulated abrasion cycling treatment.
[0416] Embodiment 148 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 17.5 seconds after simulated abrasion cycling treatment.
[0417] Embodiment 149 140. The contact lens of embodiment 139, wherein the contact lens has a water disintegration time of at least 20 seconds after a simulated abrasion cycling treatment.
[0418] Embodiment 150 an anterior surface and an opposite posterior surface; a polyquaternium-1 uptake rate ("PU") of about 0.40 micrograms / lens or less (or about 0.30 micrograms / lens or less); a friction rating of about 2.0 or less after 30 cycles of finger rubbing or simulated abrasion cycling; a structural configuration characterized by a cross-sectional surface-modulus profile along a shortest line between the anterior and posterior surfaces of a cross-sectional surface of the contact lens, the cross-sectional surface-modulus profile comprising an anterior-lateral zone including and proximal to the anterior surface, an inner zone including and peripheral to a central portion of the shortest line, and a posterior-lateral zone including and proximal to the posterior surface, The anterior lateral zone has a mean anterior surface elastic modulus
number
number
number
number
[0419] Embodiment 151 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 2.0 or less after 30 cycles of finger rubbing.
[0420] Embodiment 152 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 1.5 or less after 30 cycles of finger rubbing.
[0421] Embodiment 153 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 1.0 or less after 30 cycles of finger rubbing.
[0422] Embodiment 154 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 0.5 or less after 30 cycles of finger rubbing.
[0423] Embodiment 155 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 2.0 or less after a simulated abrasion cycling treatment.
[0424] Embodiment 156 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 1.5 or less after a simulated abrasion cycling treatment.
[0425] Embodiment 157 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 1.0 or less after a simulated abrasion cycling treatment.
[0426] Embodiment 158 151. The contact lens of embodiment 150, wherein the contact lens has a friction rating of about 0.5 or less after a simulated abrasion cycling treatment.
[0427] Embodiment 159
number
[0428] Embodiment 160
number
[0429] Embodiment 161
number
[0430] Embodiment 162
number
[0431] Embodiment 163 163. The contact lens of any one of embodiments 139-162, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.20 micrograms / lens or less.
[0432] Embodiment 164 163. The contact lens of any one of embodiments 139-162, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.15 micrograms / lens or less.
[0433] Embodiment 165 163. The contact lens of any one of embodiments 139-162, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.10 micrograms / lens or less.
[0434] Embodiment 166 163. The contact lens of any one of embodiments 139-162, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.075 micrograms / lens or less.
[0435] Embodiment 167 163. The contact lens of any one of embodiments 139-162, wherein the contact lens has a polyquaternium-1 uptake rate ("PU") of about 0.050 micrograms / lens or less.
[0436] Embodiment 168 168. The contact lens of any one of embodiments 1-167, wherein the contact lens has a UVB transmittance of about 10% or less from 280 to 315 nanometers, a UVA transmittance of about 30% or less from 315 to 380 nanometers, and a violet transmittance of 0% to about 70% from 380 nm to 440 nm.
[0437] Embodiment 169 169. The contact lens of embodiment 168, wherein the contact lens has a UVB transmittance of about 5% or less from 280 to 315 nanometers.
[0438] Embodiment 170 169. The contact lens of embodiment 168, wherein the contact lens has a UVB transmittance of about 2.5% or less from 280 to 315 nanometers.
[0439] Embodiment 171 169. The contact lens of embodiment 168, wherein the contact lens has a UVB transmittance of about 1% or less from 280 to 315 nanometers.
[0440] Embodiment 172 172. The contact lens of any one of embodiments 168-171, wherein the contact lens has a UVA transmittance of about 20% or less from 315 to 380 nanometers.
[0441] Embodiment 173 172. The contact lens of any one of embodiments 168-171, wherein the contact lens has a UVA transmittance of about 10% or less from 315 to 380 nanometers.
[0442] Embodiment 174 172. The contact lens of any one of embodiments 168-171, wherein the contact lens has a UVA transmittance of about 5% or less from 315 to 380 nanometers.
[0443] Embodiment 175 175. The contact lens of any one of embodiments 168 to 174, wherein the contact lens has a violet transmittance of 5% to about 60% between 380 and 440 nanometers.
[0444] Embodiment 176 175. The contact lens of any one of embodiments 168 to 174, wherein the contact lens has a violet transmittance of 5% to about 50% between 380 and 440 nanometers.
[0445] Embodiment 177 175. The contact lens of any one of embodiments 168 to 174, wherein the contact lens has a violet transmittance of about 5% to about 40% between 380 and 440 nanometers.
[0446] Embodiment 178 A contact lens described in any one of embodiments 1 to 177, wherein the contact lens is substantially free of (i.e., less than three) surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0447] Embodiment 179 178. The contact lens of any one of embodiments 1-177, wherein the contact lens does not contain any surface crack lines visible under dark field after rubbing the contact lens between fingers 10 times.
[0448] The above disclosure will enable those skilled in the art to practice the present invention. Various modifications, variations, and combinations can be made to the various embodiments described herein. In order to enable the reader to better understand certain embodiments and their advantages, reference to the following examples is suggested. It is intended that the specification and examples be considered as illustrative. [Example]
[0449] Example 1 chemicals In the examples below, the following abbreviations are used: AMA represents allyl methacrylate, NVP represents N-vinylpyrrolidone, DMA represents N,N-dimethylacrylamide, VMA represents N-vinyl-N-methylacetamide, MMA represents methyl methacrylate, TEGDMA represents triethylene glycol dimethacrylate, TEGDVE represents triethylene glycol divinyl ether, EGMA represents ethylene glycol methyl ether methacrylate, VAZO64 represents 2,2-dimethyl-2,2 azodipropioninitrile, Nobloc is 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate from Aldrich, UV28 represents 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-chloro-2H-benzotriazole, RB246 is Reactive Blue 246, and RB247 is Reactive Blue 247, TAA stands for tert-amyl alcohol, PrOH stands for 1-propanol, IPA stands for isopropanol, PAA stands for polyacrylic acid, PMAA stands for polymethacrylic acid, PAE stands for polyamidoamine-epichlorohydrin (also known as polyamine-epichlorohydrin), MPC stands for 2-methacryloyloxyethyl phosphorylcholine, poly(AAm-co-AA) stands for poly(acrylamide-co-acrylic acid), and PZ-28 stands for trimethylolpropane tris(2-methyl-1- aziridine propionate), PZ-33 represents pentaerythritol tris[3-(1-aziridinyl)propionate], BTP or bis-tris-propane represents bis[tris(hydroxymethyl)methylamino]propane, Tris-HCl represents tris(hydroxymethyl)aminomethane hydrochloride, EDTA represents ethylenediaminetetraacetic acid, and PBS has a pH of 7.2 ± 0.2 at 25 °C and contains approximately 0.044 wt% NaH2PO4·H2O, approximately 0.388 wt% Na2HPO4·H2O, and approximately 0.represents phosphate buffered saline containing 79 wt% NaCl, where wt% represents weight percent, mSi1 represents monobutyl-terminated monomethacryloxypropyl-terminated polydimethylsiloxane (Mw: approximately 600–800 g / mol: manufactured by Gelest), D9 represents monobutyl-terminated monomethacryloxypropyl-terminated polydimethylsiloxane (Mw: approximately 984 g / mol: manufactured by Shin-Etsu Chemical Co., Ltd.), and LM-CEPDMS is a polymer consisting of two PDMS segments, each with one terminal methacrylate group and one urethane bond, connected by diurethane bonds between two PDMS segments. "GA" macromer represents a dimethacrylate-terminated chain-extended polydimethylsiloxane (Mn: about 6000 g / mol) having three polydimethylsiloxane (PDMS) segments and prepared according to a method similar to that described in Example 2 of U.S. Pat. No. 8,529,057; "GA" macromer represents a dimethacryloyloxypropyl-terminated polysiloxane (Mn: about 6,800 g / mol, OH content: about 1.2 meq / g) of formula (A); and "G4" macromer represents a dimethacryloyloxypropyl-terminated polysiloxane (Mn: about 13,500 g / mol, OH content: about 1.8 meq / g) of formula (A). [ka]
[0450] Oxygen permeability measurement Apparent oxygen permeability (Dk app ), apparent oxygen transmissibility (Dk / t), intrinsic (or edge-corrected) oxygen permeability (Dk c ) is determined according to the procedure described in Example 1 of US Patent Application Publication No. 2012 / 0026457A1.
[0451] Finger rubbing treatment The lenses are finger rubbed with RENU® Multipurpose Lens Care Solution (or another multipurpose lens care solution) for 20 seconds (while wearing disposable powder-free latex gloves), followed by rinsing with saline. The above procedure is repeated i times (i.e., i cycles of finger rubs) to mimic daily cleaning in an i-day lens care regime, 7 times (i.e., 7 cycles of finger rubs) to mimic daily cleaning and disinfection in a 7-day lens care regime, or 30 times (i.e., 30 cycles of finger rubs) to mimic daily cleaning and disinfection in a 30-day lens care regime.
[0452] Simulated polishing cycle processing To simulate the worst-case scenario of manual cycling, a simulated polishing technique was used to ensure constant pressure and shear conditions. To do this, a customized lens holder was fabricated to clamp and simultaneously shear the lens. As shown in Figure 3, the lens (part 1) was placed on a rubber insert (part 2) into which a 7.7 mm diameter central shaft (part 3) was axially fitted. The top clip (part 4) was clipped onto the bottom clip (part 5), which firmly held the lens against the silicone gasket. The central shaft was then stretched so that the lens protruded above the outer body surface, exposing the circumferential region of the lens around its center. Optionally, a piece of fabric (i.e., Twillx 1622 (Berkshire)) was placed between the central shaft and the contact lens to improve polishing visualization.
[0453] The entire lens holder was placed onto the mounting end of a Taber linear abrasive system (Taber Industries, Model 5750, http: / / www.taberindustries.com / linear-abraser). Without any additional weight attached, the total weight of the support arm and lens holder (230g normal force) was measured at 47mm. 2A pressure of 49 kPa is applied to the contact lens area of the suction cup, and 49 kPa is applied to the counter surface. On the counter surface, a sheet of silicone rubber (10 A, ¼ inch thick) is placed under the support arm and the reservoir channel is clipped onto the silicone rubber. The reservoir is then filled with room temperature PBS.
[0454] During the experiment, the lens holder is slowly lowered onto the counter surface and the lens is polished 20 times at 75 cycles per minute (3 inches per stroke, 6 inches total travel per cycle). The lens surface can be analyzed using the water disintegration time method, lubricity evaluation, and / or Sudan Black staining test.
[0455] Although this technique applies shear forces far in excess of those experienced by typical contact lenses, this controlled shear technique (i.e., simulated abrasive cycling) has been found to be a reasonable equivalent to 30 cycles of finger rubbing, ensuring that these contact lenses can handle even the most severe mechanical cycling.
[0456] Lubricity evaluation The lubricity of contact lenses is assessed by using a finger-felt lubricity test, which qualitatively characterizes the slipperiness of the lens surface on a friction rating scale of 0 to 4. The higher the friction rating, the less slipperiness (or lubricity).
[0457] Commercially available lenses, DAILIES® TOTAL 1®, ACUVUE® OASYS™, ACUVUE® ADVANCE PLUS™, DAILIES® Aqua Comfort Plus®, and AIR OPTIX®, are assigned friction ratings (hereafter referred to as "FR") of 0, 1, 2, 3, and 4, respectively, and are used as reference lenses to determine the friction ratings of the lenses under test.
[0458] The samples are placed in PBS for at least two rinses of 30 minutes each, then transferred to fresh PBS before evaluation. Prior to evaluation, hands are rinsed with soapy water and thoroughly rinsed with DI water, followed by drying with a KimWipe® towel. The samples are handled between the fingers, and each sample is assigned a numerical value relative to the standard lens described above. For example, if a lens is determined to be slightly better than an AIR OPTIX® lens, a numerical value of 3 is assigned. Friction rating values are obtained by averaging the results of at least two friction ratings of contact lenses by two or more individuals, and / or by averaging the friction ratings of two or more contact lenses (from the same batch of lens production) by one individual.
[0459] The finger lubricity (i.e., friction rating) of contact lenses can be determined either out-of-pack (OOP) (but after immersion in PBS for 30 minutes or more), or after i cycles (e.g., 7, 14, 21, or 30 cycles) of finger rubbing according to the procedure described above, or after simulated abrasion cycling.
[0460] Surface Wettability Test The water contact angle (WCA) on a contact lens is a general measure of the surface wettability of a contact lens. Specifically, a lower water contact angle corresponds to a more wettable surface. The dynamic trapped air bubble contact angle on a contact lens is measured using an FDS instrument manufactured by Future Digital Scientific Corp. The FDS instrument is capable of measuring advancing and receding contact angles. Measurements are performed at room temperature on hydrated contact lenses. The contact lens is removed from the vial, immersed in approximately 40 mL of fresh PBS, and shaken for at least 30 minutes, then replaced with fresh PBS, immersed, and shaken for another 30 minutes unless otherwise specified. The contact lens is then placed on lens paper and gently tapped to remove surface water. It is then placed on a lens holder with the front curve facing upward, and the top of the lens holder is then screwed on. The secured lens holder is placed in a glass cell cuvette filled with filtered PBS. The glass cell cuvette is placed on the FDS instrument platform. The height of the platform and syringe needle is adjusted to distribute the air bubble onto the lens surface. All lenses are subjected to three dispense / withdraw cycles to obtain advancing and receding contact angles, which are reported in the Examples below.
[0461] Water Breakdown Time (WBUT) Test The surface hydrophilicity of the lenses (after autoclaving) is assessed by determining the time required for the water film to begin to break down on the lens surface. Lenses exhibiting a WBUT of 10 seconds or greater are considered to have a hydrophilic surface and are expected to exhibit adequate wettability (ability to support a tear film) on the eye.
[0462] Lenses are prepared for aqueous disintegration measurements by removing them from their blisters with soft plastic tweezers (e.g., from Menicon) and placing them in test tubes containing phosphate-buffered saline. The tubes contain 10 mL of phosphate-buffered saline per lens, one lens per tube. Allow the lenses to soak overnight (at least 16 hours) before testing.
[0463] WBUT is measured at room temperature as follows: The lens is removed from the test tube and placed on a pedestal submerged in PBS. The pedestal is then withdrawn from the PBS solution (t=0) and a video camera monitors the fluid flowing down from the lens surface. When the fluid on the lens surface breaks down, this WBUT time is recorded. Optionally, a stopwatch may be used to measure the time between when the pedestal is withdrawn from the PBS solution and when the fluid on the lens surface breaks down. As the pedestal is withdrawn, it pulls the lens beneath the surface of the PBS. At least three points per lens are measured, and at least three lenses are measured to obtain an average WBUT measurement for each group of lenses.
[0464] equilibrium moisture content The equilibrium water content (EWC) of a contact lens is determined as follows.
[0465] The amount of water (expressed as weight percent) present in hydrated hydrogel contact lenses that are fully equilibrated in saline solution is determined at room temperature. The lenses are blotted with a cloth, then quickly stacked and the lens stack is transferred to an aluminum dish on an analytical balance. Each sample dish typically contains five lenses. The hydrated weight of the dish and lenses is recorded. The dish is covered with aluminum foil. The dish is placed in a laboratory oven at 100±2°C and allowed to dry for 16-18 hours. The dish and lenses are removed from the oven and allowed to cool in a desiccator for at least 30 minutes. A single dish is removed from the desiccator and the aluminum foil is discarded. The dish and dry lens sample are weighed on the analytical balance. Repeat for all changes. The wet and dry weights of the lens sample can be calculated by subtracting the weight of the empty weighing dish.
[0466] Elastic modulus The modulus of elasticity of contact lenses is determined using an MTS insight instrument. First, contact lenses are cut into 3.12 mm wide strips using a Precision Concept two-stage cutter. Five thickness values are measured within a 6.5 mm gauge length. The strips are placed on the instrument's grips and submerged in PBS, the temperature of which is controlled at 21 ± 2°C. Typically, a 5 N load cell is used for testing. A constant force and velocity are applied to the sample until it collapses. Force and displacement data are collected using TestWorks software. The modulus value, which is the slope of the stress in the elastic displacement region or the tangent to the strain curve near zero elongation, is calculated by the TestWorks software.
[0467] Mechanical properties of contact lens surfaces Every contact lens can have different mechanical properties at its surface, especially when the contact lens has a soft hydrogel coating thereon. The mechanical properties of the region near and including the surface of the contact lens can be characterized by measuring the surface compressive or indentation force as a function of displacement in a microindentation or nanoindentation test.
[0468] It has been found that for contact lenses that do not have any soft hydrogel coating thereon, the indentation force at a given displacement or indentation depth (e.g., 400 nm) correlates well with the bulk (Young's) modulus (i.e., there is a linear bulk modulus-indentation force relationship between bulk modulus and indentation force at a given displacement), whereas for contact lenses that have a soft hydrogel coating thereon, the indentation force at a given displacement is much less than would be predicted based on the linear bulk modulus-indentation force relationship. Such deviations can be used as a good indicator of the soft hydrogel coating on a contact lens.
[0469] Micro-indentation test The surface compressive force of contact lenses at an indentation depth of 400 nm is measured using the following microindentation test. The contact lenses to be tested are rinsed and placed in PBS overnight. The lenses are then placed on a hemispherical platform submerged in PBS and indented using a pressure-driven quasistatic transducer indentation system (Bruker Hysitron® BioSoft™ In-Situ Indenter) equipped with a 1 mm hemispherical borosilicate glass probe. Between experiments, the probe is cleaned using a plasma cleaner (e.g., oxygen, air, or argon plasma cleaner) and coated with F-127 Pluronic (by dipping in an aqueous solution of F-127 at a concentration above the CMC of F-127, e.g., about 0.1 wt %). The probe is attached to the indentation system and pulled down at a constant indentation rate of 1 μm / s along a typical loading and unloading curve (i.e., normal force vs. indentation depth). The normal force and displacement position (or indentation depth) are measured simultaneously by a quasi-static transducer at a rate of 125 Hz. The above procedure is repeated 20 times per lens (i.e., 20 indentations). The surface compressive force (unit: microNewtons (μN)) at an indentation depth of 400 nm is obtained by averaging all normal forces at an indentation depth of 400 nm along each of the 20 indentation load curves. The normalized surface compressive force (NSCF) is obtained by dividing the obtained surface compressive force at an indentation depth of 400 nm by the elastic modulus of the contact lens under test.
[0470] Nanoindentation Test The indentation force of a contact lens at an indentation depth of 400 nm is measured by the following microindentation test.
[0471] The indentation force as a function of displacement is determined using an Optics11 Piuma instrument. Prior to performing the indentation, the Piuma probe is calibrated in PuriLens™ Plus, a sterile, preservative-free saline solution manufactured by LifeStyle Company, Inc. (Freehold, NJ). This calibration involves first calibrating the optical sensor by submerging the probe in PuriLens™ Plus but not engaging the substrate surface. A second cantilever calibration is then performed by forming a test indentation on a glass slide. The lens is rinsed with PuriLens™ Plus to remove excess lens packaging solution, followed by blotting dry. The lens is then placed in a 3D-printed lens holder with the front curve facing down (Figure 4). The base curve is then partially filled with PuriLens™ Plus to hold the lens in place, but the amount of PuriLens™ Plus added should not be so large that it overflows the base curve during testing. Finally, the Piuma probe is moved just above the lens surface, and a nanoindentation routine is performed according to the manufacturer's typical procedures. The indentation routine consists of 10 μm indentations at a speed of 1 μm / s, with a sampling rate of 100 Hz. The probe is moved to the surface, where the contact point is determined by the first deflection detected by the cantilever.
[0472] Two different Piuma probes were used to collect the data: one with a stiffness of 0.500 N / m and a tip radius of 9.500 μm, and the other with a stiffness of 4.710 N / m and a tip radius of 9.000 μm. Both probes penetrate to the same depth (400 nm), resulting in slightly different contact areas. The contact areas (S cap ) can be calculated by the following formula: S cap =2πRh where "R" is the tip radius and h is the indentation depth. Therefore, the two probe tips have a 23.9 μm2 and 22.6 μm 2 The resulting pressure of the 9 μm tip should be only 5% higher than that of the 9.5 μm tip. This small pressure difference should have little effect on the measured force compared between these tips.
[0473] It should be understood that using a single type of Piuma probe for all nanoindentation experiments is preferable. However, if multiple Piuma probes are needed to optimize measurements for contact lenses with a wide range of bulk moduli (e.g., 0.2 MPa to 1.5 MPa), Piuma probes with tip radii differing by approximately 10% or less can be used.
[0474] Once the indentation is performed, both the indentation depth and the indentation force are recorded. Five lenses per lens type are tested, with three measurements per lens, resulting in a total of 15 data points per lens group.
[0475] All raw data is processed using MATLAB and analyzed using Excel. The indentation force value at a depth of 400 nm is determined by interpolating between the two closest force values. For each lens group, all indentation forces at a depth of 400 nm are averaged, and the averaged indentation force at a depth of 400 nm is used to characterize the contact lenses in that lens group.
[0476] Transmittance The contact lens is manually placed into a specially constructed sample holder that maintains the lens' shape when placed on the eye. The holder is then submerged in a quartz cuvette with a 1 cm path length containing PBS as a standard. A UV / visible spectrophotometer, such as a Varian Cary 3E UV-Visible Spectrophotometer equipped with a LabSphere DRA-CA-302 beam splitter, can be used for this measurement. The percent transmittance spectrum is collected over the wavelength range of 250-800 nm, with T values collected at 0.5 nm intervals. This data is transferred to an Excel spreadsheet and used to determine whether the lens meets Class 1 UV absorbance standards. The transmittance is calculated using the following formula:
number
[0477] Determination of polyquaternium-1 uptake rate (PU). The rate of polyquaternium-1 uptake by contact lenses is determined according to the DNA intercalation method based on the PicoGreen dsDNA assay kit (i.e., Quanti-iT PicoGreen dsDNA kit (ThermoFisher)). The rate of polyquaternium-1 uptake by contact lenses is determined as follows.
[0478] A basis solution is prepared by dissolving the following components in purified water, 5 ppm myristamidopropyl dimethylamine, 1000 ppm sodium decanoylethylenediamine triacetate, 83 ppm sodium citrate dehydrate, 1000 ppm NaCl, 1000 ppm Tetronic 1304, 1150 ppm sodium borate decahydrate, and 10000 ppm propylene glycol, followed by adjusting the pH to approximately 7.8.
[0479] Prepare polyquaternium-1 (PQ) test solutions by dissolving the desired amount in the standard solution prepared above to have 5 ppm PQ, followed by adjusting the pH to approximately 7.8 if necessary. Prepare a series of PQ standard solutions, each with a range of concentrations, to establish a calibration curve between 0 and 6 ppm (or higher) of PQ.
[0480] The contact lenses are removed from their individual lens packages and shaken in 25 mL of PBS per lens for 30 minutes. The PBS-soaked lenses are blotted with a paper towel of a constant weight (i.e., 0.6 kg) (preferably a Kimberly Clark W4 polypropylene towel) and then incubated overnight.
[0481] A 24-well plate is used in the overnight incubation experiment. The wells are divided into the following categories: negative control wells, each containing 0.5 mL of standard solution and two blotted contact lenses fully immersed therein; positive control wells, each containing 0.5 mL of polyquaternium-1 test solution; sample wells, each containing 0.5 mL of polyquaternium-1 test solution and two blotted contact lenses fully immersed therein; and standard wells, each containing 0.5 mL of one of the standard solutions. The 24-well plate is then shaken on an orbital shaker for 20 minutes, then placed on the benchtop at room temperature overnight (16-20 hours).
[0482] Add a 25 µL aliquot from each well of the overnight-incubated 24-well plate to a cell well of a 96-well plate (e.g., DNA LoBind (Eppendorf)) containing 450 µL of lambda DNA solution (1 µg / mL lambda DNA, 10 mM Tris-HCl, 1 mM EDTA, pH 7.5). Mix the solution and incubate for 60 min at 700-800 rpm on an orbital shaker.
[0483] A 100 μL aliquot from each DNA-incubated cell well is transferred to a 96-well plate (e.g., black opaque, medium binding (Grenier)). Next, 100 μL of PicoGreen solution (ThermoFisher, diluted in Tris-EDTA buffer [10 mM Tris-HCl, 1 mM EDTA, pH 7.5] according to the kit instructions) is added to each well and mixed. The cell wells are then incubated for 5 minutes on an orbital shaker at 250 rpm. Each plate is read in a fluorescent plate reader (e.g., Victor X5 Plate Reader (Perkin Elmer)) using standard fluorescence excitation and emission wavelengths for PicoGreen. Each sample is compared to a linear fit of the standard curve to obtain the final PQ concentration in each solution. The amount of PQ uptake per lens is obtained by multiplying by the incubation volume and dividing by the number of lenses incubated. The percentage of PQ uptake by the lens is calculated as the difference in [polyquaternium-1] between the DNA-incubated positive control and the sample solution multiplied by the incubation volume (0.5 mL) and divided by two.
[0484] Surface Crack (SC) Test The test for assessing surface cracks is performed as follows: Remove the lens from its packaging. Gently invert the lens (i.e., place the lens in an inverted configuration) by holding the edge of the lens between the thumb and index finger of one hand. The concave side of the lens should be facing the experimenter's body. Using the thumb and / or index finger of the other hand, gently bend the top of the lens over the index finger holding the lens until lens confirmation inverts. Next, gently fold the lens in half and apply slight pressure to the folded lens. Then, return the lens to its original configuration before inverting it, and repeat the above steps. Place the lens in a Petri dish and inspect it using a dark-field stereo microscope. Surface cracks on the lens are first inspected at low magnification (i.e., 10-20x) by focusing on the center of the lens. If crack lines are not discernible, further inspect the lens at higher magnification (e.g., 35-45x). If no cracks are observed at 45x magnification, the lens receives a surface crack rating of zero (0). If cracks are observed, a crack rating is obtained by counting the number of split lines, with a rating of 1 being 2-4 lines in the field of view, a rating of 2 being 5-8 lines, and a rating of 3 being 8 or more lines.
[0485] Coating Intactness Test The integrity of the coating on the surface of a contact lens can be tested according to the Sudan Black staining test as follows: A contact lens having a coating (LbL coating, plasma coating, hydrogel coating, or any other coating) is immersed in a Sudan Black dye solution (Sudan Black in a mixture of about 80% mineral oil and about 20% vitamin E oil). Sudan Black dye is hydrophobic and has a high tendency to be adsorbed by hydrophobic materials or onto hydrophobic lens surfaces or onto hydrophobic spots on the partially coated surface of a hydrophobic lens (e.g., a silicone hydrogel contact lens). If the coating on the hydrophobic lens is intact, no staining spots should be observed on or within the lens. All lenses under test are fully hydrated. Visible fine lines on the lens surface may indicate cracks in the crosslinked coating.
[0486] Comparative Example The method disclosed in US Patent Application Publication No. 2016 / 0326046A1 is used in this example to reduce the uptake rate of positively charged antimicrobial agents by water gradient contact lenses.
[0487] PMAA coating solution: A polymethacrylic acid (PMAA) coating solution was prepared by dissolving a certain amount of PMAA (Mn: 300-600 kDa (Polysciences, Inc.)) in a predetermined volume of 1-propanol / water (90% / 10% wt / wt) mixture to a concentration of approximately 0.011 wt%, and the pH was adjusted to approximately 2.0 using formic acid.
[0488] PAE Solution-1: A PAE solution is prepared by dissolving a certain amount of polyamidoamine epichlorohydrin (Kymene) in a certain volume of water to a concentration of about 0.5% by weight, and the pH is adjusted to the desired pH (e.g., 2.0, 3.5, 7, or 9).
[0489] PAE Solution-2: A PAE solution is prepared by dissolving a certain amount of polyamidoamine epichlorohydrin (Kymene) in a predetermined volume of a mixture of water (68 wt%) and 1-propanol (32 wt%) to a concentration of about 0.5 wt%, and the pH is adjusted to pH 2.0.
[0490] Preparation of in-package coated (IPC) saline (IPC-1) About 90 mole % 2-methacryloyloxyethyl phosphorylcholine (MPC) and about 10 mole % [ka] (wherein X is a monovalent radical of -CH2CH(OH)CH2SCH2CH2NH2 or -CH2CH(CH2OH)SCH2CH2NH2), and an MPC-containing copolymer (MW: 230-320 kD) containing is prepared according to a procedure similar to that described in Examples 1-2 of U.S. Pat. No. 9,127,099 B2. The MPC-containing copolymer used is an aqueous solution containing a solids content of about 10 wt % of the MPC-containing copolymer.
[0491] PAE solution (Kymene) is purchased from Ashland as an aqueous solution and is used as is.
[0492] IPC-1 saline is prepared as follows: Approximately 74 wt% MPC-containing copolymer solution, approximately 6 wt% PAE solution, and approximately 20 wt% phosphate buffer (approximately 0.22 wt% NaH2PO4·H2O, 1.95 wt% Na2HPO4·2H2O, and approximately 4 wt% NaCl) are mixed (the concentrations of the MPC-containing copolymer and PAE are approximately 10 times that of the final saline solution). The pH is adjusted to approximately 7.3 with 1 N NaOH. The mixture is reacted in a water bath at 70°C for 4 hours to form a water-soluble, thermally crosslinkable polymeric material (i.e., "in-package crosslinker" or "IPC agent"). The mixture is removed from the water bath and cooled in a room-temperature water bath. The mixture is diluted 10-fold with PBS and the pH is adjusted to approximately 7.3. The mixture is filtered through a 0.22 μm PES sterile filter unit.
[0493] Cast Silicone Hydrogel (SiHy) Contact Lenses: SiHy contact lenses (uncoated) are cast according to the procedure described in Example 3 of US Patent Application Publication No. 2016 / 0326046A1.
[0494] Application of the crosslinked coating. Cast SiHy contact lenses are extracted and coated by dipping them in a series of baths: Baths 1-3—three MEK baths (approximately 22 seconds, 138 seconds, and 224 seconds, respectively); Bath 4—DI water bath (approximately 56 seconds); Baths 5-7—shown in Table 1; Bath 8—DI water (approximately 56 seconds unless otherwise indicated); Bath 9—DI water (approximately 56 seconds); and Bath 10—DI water (approximately 168 seconds). Unless otherwise indicated, all baths are at room temperature (i.e., approximately 22-26°C). After Bath 10, the contact lenses are individually packaged in polypropylene lens packaging shells (blisters) with 0.6 mL of IPC-1 saline (half of which is added before inserting the lenses). The blisters are then sealed with foil and autoclaved at 121°C for approximately 30 minutes to form a crosslinked coating on the lenses.
[0495] [Table 1]
[0496] The lenses are then tested for the amount of carboxyl groups per lens according to the procedure described in Example 2 of US 2016 / 0326046 A1, and are also subjected to a finger rubbing test to evaluate lubricity (friction rating) according to the procedure described in Example 1.
[0497] The control lenses (C3 and C4) and the test lenses (T8 and T9) have a lubricity rating of 4 as they are taken out of the package and without being subjected to the cycling-lubricity test. These results may indicate that heating a lens that has a PMAA coating thereon can result in significant loss of PMMA, leaving an insufficient amount of PMAA on the lens to react with the thermally crosslinkable material to form a hydrogel top coating.
[0498] The test lenses (T2 and T3) have out-of-package lubricity levels of 3 and 4, respectively. These results may indicate that at high pH (7 or 9), PMAA is loaded and PAE cannot penetrate into the PMAA coating but forms a layer on top of the PMAA coating. The top layer of PAE prevents the underlying PMAA from reacting with the thermally crosslinkable polymeric material to form a hydrogel top coating. During autoclaving, the top layer of PAE crosslinks with the PMAA coating to form a crosslinked coating with less lubricity.
[0499] The results in Table 2 indicate that the approach disclosed in U.S. Patent Application Publication No. 2016 / 0326046A1 may not be sufficient to produce water gradient contact lenses that have sufficient lubricity after cycling with Renu lens care solution and that do not have a significant decrease in the uptake rate of the positively charged antimicrobial agent.
[0500] [Table 2]
[0501] Example 2 Preparation of polymerizable composition Two lens formulations (polymerizable compositions) I and II are prepared having the compositions (part by part) shown in Table 3.
[0502] [Table 3]
[0503] The formulation is prepared by adding the listed ingredients in their target amounts to a clean bottle and mixing with a stir bar at 600 rpm for 30 minutes at room temperature. After all solids are dissolved, the formulation is filtered using a 2.7 μm glass microfiber filter (GMF).
[0504] Cast-molded silicone hydrogel contact lenses The lens formulation is purged with nitrogen at room temperature for 30-35 minutes. The N2-purged lens formulation is introduced into a polypropylene mold and thermally cured under the following cure conditions: ramp from room temperature to 55°C at a ramp rate of approximately 7°C / min, hold at 55°C for approximately 30 minutes, ramp from 55°C to 80°C at a ramp rate of approximately 7°C / min, hold at 55°C for approximately 30 minutes, ramp from 80°C to 100°C at a ramp rate of approximately 7°C / min, hold at 100°C for approximately 30 minutes. The mold is opened and the molded lens is removed from the mold.
[0505] Formulations I and II are used in the coating studies in the following examples. Generally, Formulation II is used unless otherwise indicated.
[0506] The resulting silicone hydrogel (SiHy) contact lenses are subjected to the following post-molding process before the lenses are characterized. After demolding, the SiHy lenses prepared above are immersed in PBS twice at room temperature for approximately 60 minutes. After rinsing with PBS for 5 minutes, the lenses are placed in polypropylene lens packaging shells (or blisters) (one lens per shell) with 0.6 mL of PBS. The blisters are then sealed with foil and autoclaved at approximately 121°C for approximately 45 minutes. The SiHy lenses have an oxygen permeability (measured by polarographic methods) of about 91 barrers (for Formulation I) or about 83 barrers (for Formulation II), a bulk modulus of about 0.80 MPa (for Formulation I) or 0.67 MPa (for Formulation II), a water content of about 49% by weight (for Formulation I) or about 50% by weight (for Formulation II), a relative ion permeability of about 12.5 (for Formulation I) or about 11.0 (for Formulation II) relative to Alsacon lenses, a WBUT of 0 seconds, and a friction rating of 4.
[0507] Example 3 Preparation of polymerizable composition Lens formulations (polymerizable compositions) III-VI are prepared to have the compositions (part by part) shown in Table 4.
[0508] [Table 4]
[0509] The formulation is prepared by adding the listed ingredients in their target amounts to a clean bottle and mixing with a stir bar at 600 rpm for 30 minutes at room temperature. After all solids are dissolved, the formulation is filtered using a 2.7 μm glass microfiber filter.
[0510] Cast-molded silicone hydrogel contact lenses The lens formulation is purged with nitrogen at room temperature for 30-35 minutes. The N2 purged lens formulation is introduced into a polypropylene mold and thermally cured in an oven under the following cure conditions: ramp from room temperature to a first temperature followed by a first cure time at the first temperature; ramp from the first temperature to a second temperature and a second cure time at the second temperature; optionally ramp from the second temperature to a third temperature and a third cure time at the third temperature; and optionally ramp from the third temperature to a fourth temperature and a fourth cure time at the fourth temperature.
[0511] The lens mold is opened using a demolding machine equipped with a pressure pin. The lens is pushed onto the base curve mold using the pressure pin, and the mold is subsequently separated into a base curve mold half and a front curve mold half. The base curve mold half with the lens thereon is placed in an ultrasonic device (e.g., a Dukane single horn ultrasonic device). A specific energy force is used to release the dry lens from the mold. The dry lens is loaded into a designed extraction tray. Alternatively, the lens can be removed from the base curve mold half by floating it off (i.e., immersion in an organic solvent such as IPA without ultrasound).
[0512] The resulting silicone hydrogel (SiHy) contact lenses are subjected to the following post-molding process before the lenses are characterized. After demolding, the SiHy lenses prepared above are extracted with 100% IPA for 15 minutes, immersed in a 50% / 50% IPA / water mixture for 30 minutes, followed by DI water for 30 minutes, and finally rinsed with PBS saline at room temperature for approximately 60 minutes. After rinsing with PBS for 5 minutes, the lenses are placed in polypropylene lens packaging shells (or blisters) (one lens per shell) with 0.6 mL of PBS. The blisters are then sealed with foil and autoclaved at approximately 121°C for approximately 45 minutes. The resulting SiHy contact lenses are characterized according to the procedure for having the following properties: Dkc: approximately 105 barrer to 118 barrer, EWC: approximately 54% to 57%, elastic modulus: approximately 0.45 MPa to 0.62 MPa, WBUT: approximately 23 seconds to 40 seconds, water contact angle due to trapped bubbles: approximately 47 degrees to 52 degrees, friction rating: approximately 2.0.
[0513] Example 4 Preparation of PAA aqueous solution An aqueous solution of polyacrylic acid (PAA) is prepared by adding an appropriate amount of PAA (Mn: approximately 450 KD) to water (distilled or deionized water). After the PAA is completely dissolved, the pH is adjusted to approximately 2 by adding approximately 1.85% formic acid to the PAA aqueous solution. The target concentration of PAA is approximately 0.1% by weight. The prepared PAA aqueous solution is filtered to remove any particulates or foreign matter.
[0514] Phosphate-buffered saline (PBS) Prepare phosphate buffered saline by dissolving NaH2PO4·H2O and Na2HPO4·2H2O in a predetermined amount of purified water (distilled or deionized) to a composition of approximately 0.044 wt / wt% NaH2PO4·H2O, approximately 0.388 wt / wt% Na2HPO4·2H2O, and approximately 0.79 wt / wt% NaCl.
[0515] Phosphate buffered (PB) (PB, No NaCl) Prepare PB using the same procedure as for preparing PBS but without the addition of NaCl.
[0516] IPC-2 saline Prepare IPC-2 saline by dissolving / mixing the appropriate amounts of poly(AAm-co-AA) (90 / 10), PAE, NaHPO·H2O, NaHPO·2H2O, and NaCl in DI (deionized) water to have the following concentrations: approximately 0.132 wt% poly(AAm-co-AA), approximately 0.11 wt% PAE, approximately 0.044 wt% NaHPO·H2O, approximately 0.388 wt% NaHPO·2H2O, and approximately 0.79 wt% NaCl, followed by adjusting the pH to approximately 7.3. Poly(AAm-co-AA) (90 / 10) partial sodium salt (poly(AAm-co-AA) 90 / 10, Mw 200,000) was purchased from Polysciences, Inc. and used as is. The prepared solution is pretreated at 65°C for approximately 6 hours. After heat pretreatment, the IPC saline solution is cooled to room temperature. Up to 5 ppm of hydrogen peroxide may be added to the final IPC saline solution to prevent bioburden buildup, and the IPC saline solution is filtered using a 0.22 micrometer membrane filter.
[0517] SiHy lenses containing PAA-based coatings After demolding, the dried SiHy contact lenses (prepared with Example 2, Formulation II) are placed in an appropriate tray. The tray containing the lenses is then immersed in the PAA solution for a predetermined time, either 120 minutes in one PAA bath or two sequential PAA baths, 30 minutes in the first bath and 90 minutes in the second. The PAA dip solution is heated above room temperature, for example, to 40°C. Sufficient agitation (e.g., horizontal shaking or up-and-down motion) may be used to ensure proper flow of the PAA solution during the dipping process.
[0518] After PAA dipping, the lenses are transferred to a bath containing PB for up to about 1 hour, usually at room temperature. Sufficient agitation (e.g., horizontal shaking or up-and-down motion) may be used to ensure adequate flow of the PB during the dipping process.
[0519] The lenses are then transferred to a bath containing water for approximately 5-10 minutes, usually at room temperature. Sufficient agitation (e.g., horizontal shaking or up-and-down motion) may be used to ensure adequate flow of water during the dipping process.
[0520] Water Gradient SiHy Contact Lenses The SiHy lenses having the PAA-based coating thereon, prepared as described above, are placed into polypropylene lens packaging shells (one lens per shell) along with 0.55 mL or 0.65 mL of IPC-2 saline (approximately half of the saline may be added prior to inserting the lens). The blisters are then sealed with foil and autoclaved at about 121° C. for about 45 minutes to form SiHy contact lenses having a crosslinked hydrophilic coating (i.e., a hydrogel coating) thereon.
[0521] Surface properties of water-gradient SiHy contact lenses The resulting water gradient SiHy contact lenses are lubricious (having a friction rating of 1) out of the package, have a WBUT greater than 10 seconds, and a sessile drop (static) water contact angle of approximately 30 degrees.
[0522] Example 5 This example uses the water gradient contact lenses prepared in Example 4. These are determined to have a PU (Polyquaternium-1 uptake) of approximately 9 μg / lens.
[0523] Preparation of aqueous polyaziridine solutions A 1 wt% PZ-28 solution is prepared by simply adding PZ-28 to PBS and adjusting the pH to about 7.5, and a 1 wt% PZ-33 solution is prepared by simply adding PZ-33 to PBS and adjusting the pH to about 7.5.
[0524] Reduction of PU with water gradient contact lenses The water gradient contact lenses prepared in Example 4 are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL or 0.65 mL of 1% PZ-28 solution and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (have a friction rating of 1) and have a PU of 0.56 μg / lens, i.e., a reduction in PU of 93.8%.
number
[0525] The water gradient contact lenses prepared in Example 4 are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL or 0.65 mL of 1% PZ-33 solution and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (friction rating of 1) and have a PU of 1.95 μg / lens, i.e., a 78.3% reduction in PU.
[0526] Example 6 Preparation of PMAA solution A solution of polymethacrylic acid (PMAA) was prepared by adding an appropriate amount of PMAA (Mn: approximately 400-700 kDa (PolyMaterials, Inc.)) to an IPA / water (50 / 50 volume ratio) mixture to a concentration of approximately 0.12 wt%. After the PMAA was completely dissolved, the pH was adjusted to approximately 2 by adding formic acid to the PMAA solution. The prepared PMAA solution was filtered to remove any particulates or foreign matter.
[0527] Phosphate-buffered saline (PBS) PBS is prepared according to the procedure described in Example 4.
[0528] Phosphate buffer solution (PB) containing no NaCl (PB, No NaCl) PB is prepared according to the procedure described in Example 4.
[0529] Preparation of aqueous polyaziridine solutions A 1 wt% PZ-28 solution is prepared by simply adding PZ-28 to PBS and adjusting the pH to about 7.5, and a 1 wt% PZ-33 solution is prepared by simply adding PZ-33 to PBS and adjusting the pH to about 7.5.
[0530] IPC-3 saline About 90 mole % 2-methacryloyloxyethyl phosphorylcholine (MPC) and about 10 mole % [ka] (wherein X is a monovalent radical of -CH2CH(OH)CH2SCH2CH2NH2 or -CH2CH(CH2OH)SCH2CH2NH2), and an MPC-containing copolymer (Mw: 230-320 kD) containing is prepared according to a procedure similar to that described in Examples 1-2 of U.S. Pat. No. 9,127,099 B2. The MPC-containing copolymer used is an aqueous solution containing a solids content of about 10 wt % of the MPC-containing copolymer.
[0531] PAE solution (Kymene) is purchased from Ashland as an aqueous solution and is used as is.
[0532] IPC-3 saline is prepared as follows: Approximately 74.3 wt% MPC-containing copolymer solution, approximately 3.7 wt% PAE solution, and approximately 22 wt% phosphate buffer (approximately 0.22 wt% NaH2PO4·H2O, 1.95 wt% Na2HPO4·2H2O, and approximately 4 wt% NaCl) are mixed (the concentrations of the MPC-containing copolymer and PAE are approximately 10 times that of the final saline solution). The pH is adjusted to approximately 7.3 with 1 N NaOH. The mixture is reacted in a water bath at 70 °C for 4 hours to form a water-soluble, thermally crosslinkable polymeric material (i.e., "in-package crosslinker" or "IPC agent"). The mixture is removed from the water bath and cooled in a room-temperature water bath. The mixture is diluted 10-fold with PBS and the pH is adjusted to approximately 7.3. The mixture is filtered through a 0.22 μm PES sterile filter unit.
[0533] Water Gradient SiHy Contact Lenses After demolding, the cast SiHy contact lenses (prepared in Example 3) were extracted with isopropanol (IPA) for 180 minutes for lens extraction, dip-coated in the PMAA solution prepared above for approximately 1 hour, rinsed with PBS for approximately 60 minutes, and then packaged / sealed in polypropylene lens packaging shells (blisters) with 0.6 mL of IPC-3 saline (half of which was added before inserting the lens). The sealed lens packages were autoclaved at approximately 121°C for approximately 45 minutes to form SiHy contact lenses having a crosslinked hydrophilic coating (i.e., hydrogel coating) thereon. The coating uniformity or integrity was tested using the Sudan Black dye test, and the coating passed the Sudan Black dye test.
[0534] The resulting water gradient SiHy contact lenses are fairly lubricious (having a friction rating of 2), with a WBUT greater than 10 seconds and a PU (polyquaternium-1 uptake) of 1.2 μg / lens.
[0535] Reduction of PU uptake rate by water gradient contact lenses The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL or 0.65 mL of 1% PZ-28 solution and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still fairly lubricious (having a friction rating of about 1.7) and have a PU of 0.06 μg / lens, i.e., a 95% reduction in PU.
number
[0536] The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL or 0.65 mL of 1% PZ-33 solution and autoclaved for about 45 minutes at about 121° C. The resulting lenses remain lubricious (friction rating of about 1.0) and have a PU of 0.32 μg / lens, i.e., a reduction in PU of 73.3%.
[0537] Example 7 This example uses water gradient contact lenses prepared according to the procedure described in Example 19 of U.S. Patent No. 8,480,227. The water gradient SiHy contact lenses have a water content of about 32% by weight, an oxygen permeability of about 146 barrers, a bulk modulus of about 0.76 MPa, a relative ion permeability of about 6 (compared to Alsacon lenses), a friction rating of 0, a WBUT of greater than 20 seconds, a water contact angle (by static drop) of about 34-47 degrees, and a PU of about 11 μg / lens.
[0538] Preparation of BTP solution Prepare a bis-tris-propane (BTP) solution by dissolving BTP in deionized (DI) or distilled water to a concentration of 0.03%, followed by adjusting the pH to 7.5.
[0539] Preparation of aqueous polyaziridine solutions PZ-28 BTP buffer solutions with PZ-28 concentrations of 0.1 wt%, 0.2 wt%, or 0.3 wt% are prepared by simply adding PZ-28 to the BTP solution and adjusting the pH to about 7.4.
[0540] A PZ-28 phosphate buffer solution with a PZ-28 concentration of 0.1% by weight is prepared by simply adding PZ-28 to PBS and adjusting the pH to about 7.5.
[0541] Reduction of PU uptake rate by water gradient contact lenses The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of the 0.1% PZ-28BTP buffer solution prepared above and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (have a friction rating of 0) and have a PU of 1.2 μg / lens, i.e., a reduction in PU of 89.1%.
number
[0542] The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of 0.2% PZ-28BTP buffer solution and autoclaved for approximately 45 minutes at approximately 121° C. The resulting lenses remain lubricious (friction rating of 0) and have a PU of 0.4 μg / lens, i.e., a PU reduction of 96.4%.
[0543] The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of 0.3% PZ-28BTP buffer solution and autoclaved for approximately 45 minutes at approximately 121° C. The resulting lenses remain lubricious (friction rating of 0) and have a PU of 0.3 μg / lens, i.e., a PU reduction of 97.3%.
[0544] The water gradient contact lenses prepared above are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of the 0.1% PZ-28 phosphate buffer solution prepared above and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (have a friction rating of 0) and have a PU of 0.6 μg / lens, i.e., a PU reduction of 94.5%.
[0545] Example 8 This example uses the water gradient contact lenses prepared in Example 4. These are determined to have a PU of approximately 9 μg / lens.
[0546] Preparation of BTP solution A bis-tris-propane solution is prepared by dissolving BTP in DI (or distilled) water to a concentration of 0.03 wt % and then adjusting the pH to 7.5.
[0547] Preparation of aqueous polyaziridine solutions PZ-28 solutions with concentrations of 0.1%, 0.2%, or 0.3% PZ-28 are prepared by simply adding PZ-28 to the BTP solution and adjusting the pH to about 7.5.
[0548] Reduction of PU uptake rate by water gradient contact lenses The water gradient contact lenses prepared in Example 4 are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of the 0.1% PZ-28 solution prepared above and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (have a friction rating of 0) and have a PU of 0.42 μg / lens, i.e., a reduction in PU of 95.3%.
number
[0549] The water gradient contact lenses prepared in Example 4 are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of the 0.2% PZ-28 solution prepared above and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (friction rating of 0) and have a PU of 0.3 μg / lens, i.e., a 96.7% reduction in PU.
[0550] The water gradient contact lenses prepared in Example 4 are individually repackaged in polypropylene lens packaging shells (one lens per shell) with 0.55 mL of the 0.3% PZ-28 solution prepared above and autoclaved for about 45 minutes at about 121° C. The resulting lenses are still lubricious (friction rating of 0) and have a PU of 0.05 μg / lens, i.e., a 99.4% reduction in PU.
[0551] Example 9 Preparation of PAA coating solution The PAA coating solution is prepared by adding an appropriate amount of PAA (Mn: approximately 450 KD) to a 50 / 50 water-IPA mixture. After the PAA is completely dissolved, the pH is adjusted to approximately 2 by adding approximately 1.85% formic acid to the PAA aqueous solution. The target concentration of PAA is approximately 0.1 wt%. The prepared PAA coating solution is filtered to remove any particulates or foreign matter.
[0552] Phosphate-buffered saline (PBS) Prepare phosphate buffered saline by dissolving NaH2PO4·H2O and Na2HPO4·2H2O in a predetermined amount of purified water (distilled or deionized) to a composition of approximately 0.044 wt / wt% NaH2PO4·H2O, approximately 0.388 wt / wt% Na2HPO4·2H2O, and approximately 0.79 wt / wt% NaCl.
[0553] Phosphate buffer solution (PB) containing no NaCl (PB, No NaCl) Prepare PB using the same procedure as for preparing PBS but without the addition of NaCl.
[0554] Preparation of aqueous polyaziridine solutions PZ-28 solutions with concentrations of 0.125%, 0.25%, or 0.5% PZ-28 are prepared by simply adding PZ-28 to DI water and adjusting the pH to about 7.4.
[0555] Reduction of PU by PZ in PAA-coated SiHy contact lenses After demolding, the dried SiHy contact lenses (prepared in Example 3) are extracted with isopropanol (IPA) for 180 minutes for lens extraction, dip coated in the PAA solution prepared above for about 30 minutes, rinsed twice with PB for about 15 minutes each, and then immersed in the PZ-28 solution prepared above for about 2 hours at about 60° C. After the PZ-28 dipping step, the lenses are again rinsed twice with PB (for 15 minutes each) and then subjected to various tests as shown in Table 5.
[0556] [Table 5]
[0557] The results in Table 5 show that after various PZ-dip treatments, the Polyquartenium-1 uptake rate by PAA-coated SiHy contact lenses can be significantly reduced by PZ-28 due to the reaction of the aziridine groups of PZ-28 with the -COOH groups in the PAA coating on the lens surface at approximately 60 °C (a relatively high temperature). Even at a concentration of approximately 0.125 wt%, PZ-28 can significantly reduce the Polyquartnium-1 uptake rate (PU) by PAA-coated SiHy lenses, while adversely affecting their lubricity.
[0558] Table 6 shows the results of treating PAA-coated SiHy contact lenses with 0.25 wt. % PZ-28 for approximately 1 hour at room temperature and 45°C to evaluate the effect of PZ-28 dipping temperature on the efficacy of PZ-28 in reducing PU. Table 6 shows that the efficacy of PZ-28 is significantly improved at 45°C compared to when the PZ dipping is performed at room temperature (RT). The reduction in polyquatonium-1 uptake is approximately 55% at room temperature compared to approximately 93% when the dipping is performed at 45°C. This indicates that the efficacy of PZ-28 increases at temperatures above RT.
[0559] [Table 6]
[0560] Example 10 Preparation of PMAA solution The polymethacrylic acid (PMAA) coating solution was prepared by dissolving a certain amount of PMAA (Mn: 400-700 kDa, manufactured by PolyMaterials, Inc.) in a predetermined volume of 1-propanol / water (25 / 75 volume ratio) mixture to a concentration of approximately 0.06 wt %, and the pH was adjusted to approximately 2.0 using formic acid (typically approximately 1.8 wt % in the final solution).
[0561] Phosphate-buffered saline (PBS) PBS is prepared according to the procedure described in Example 4.
[0562] Phosphate buffer solution (PB) containing no NaCl (PB, No NaCl) PB is prepared according to the procedure described in Example 4.
[0563] IPC Saline (IPC-4, IPC-5, IPC-6, and IPC-7) IPC-3 saline is prepared according to the procedure described in Example 6.
[0564] Four IPC saline solutions (IPC-4 to IPC-7) with PZ-28 concentrations of 0.05%, 0.1%, 0.5%, and 1% by weight, respectively, were prepared by adding the desired amount of PZ-28 to IPC-3 saline solution and then adjusting the pH to 7.5. Up to 5 ppm of hydrogen peroxide may be added to each IPC saline solution to prevent microbial contamination, and each IPC saline solution was filtered using a 0.22 micrometer membrane filter.
[0565] Water Gradient SiHy Contact Lenses After demolding, the cast SiHy contact lenses (prepared in Example 3) were extracted with isopropanol (IPA) for 180 minutes for lens extraction, dip-coated in the PMAA solution prepared above for approximately 1 hour, rinsed with PBS for approximately 60 minutes, and then packaged and sealed in polypropylene lens packaging shells (blisters) with 0.6 mL of one of the IPC-3 to IPC-7 saline solutions prepared above (half of the IPC saline solution was added before inserting the lens). The sealed lens packages were autoclaved at approximately 121°C for approximately 45 minutes to form SiHy contact lenses having a crosslinked hydrophilic coating (i.e., a hydrogel coating) thereon. The coating uniformity or integrity was tested using the Sudan Black dye test, and the coating passed the Sudan Black dye test.
[0566] The resulting water gradient SiHy contact lenses are fairly lubricious (having a friction rating of approximately 0), with a WBUT greater than 20 seconds and a static drop water contact angle of 40. They are determined to have PUs of 0.5, 0.19, 0.19, 0, and 0 for water gradient contact lenses prepared from IPC-3 saline (0 wt.% PZ-28), IPC-4 saline (0.05 wt.% PZ-28), IPC-5 saline (0.1 wt.% PZ-28), IPC-6 saline (0.5 wt.% PZ-28), and IPC-7 saline (1.0 wt.% PZ-28), respectively.
[0567] Example 11 Preparation of PAA coating solution The PAA coating solution is prepared by adding an appropriate amount of PAA (Mn: about 450 KD) into a water-IPA mixture having a water content shown in Table 7 to achieve the desired PAA concentration shown in Table 7. After the PAA is completely dissolved, the pH is adjusted to about 2 by adding about 1.85% formic acid to the PAA aqueous solution. The prepared PAA coating solution is filtered to remove any particulates or foreign matter.
[0568] Phosphate-buffered saline (PBS) PBS is prepared according to the procedure described in Example 4.
[0569] Phosphate buffer solution (PB) containing no NaCl (PB, No NaCl) PB is prepared according to the procedure described in Example 4.
[0570] Preparation of poly(MPC-co-AEM) (96 / 4 wt / wt) The copolymer poly(2-methacryloyloxyethyl phosphorylcholine-co-2-aminoethyl methacrylate) (96 / 4 wt / wt) (i.e., poly(MPC-co-AEM)) was prepared by thermally polymerizing a polymerizable composition containing about 96 wt% MPC, about 4 wt% AEM, about 0.02 wt% Vazo56 [2,2'-azobis(2-methylpropionamidine) dihydrochloride], and about 0.1 wt% chain transfer agent (HS-CHCHOH) in water at about 60°C for about 2 hours and then at 20°C for about 2 hours. The resulting poly(MPC-co-AEM) (aqueous solution with a solids content of about 10%) was determined to have an amine functionality of about 0.22 meq / g and an Mn of about 160 kDa.
[0571] The resulting copolymer is used as a hydrophilicity enhancer for reaction with polyamidoamine-epichlorohydrin (PAE) to prepare water-soluble thermally crosslinkable polymeric materials (i.e., "in-package crosslinkers" or "IPC agents"). PAE solution (Kymene) is purchased from Ashland as an aqueous solution and used as is.
[0572] IPC-8 saline IPC-8 saline is prepared as follows: The 77% w / w poly(MPC-co-AEM) aqueous solution prepared above, 6.1% w / w PAE, and 16.9% w / w phosphate buffer (approximately 128 mM sodium phosphate and approximately 4% NaCl) are mixed (the concentrations of poly(MPC-co-AEM) and PAE are approximately 10 times that of the final saline solution). The pH is adjusted to approximately 7.3 with 1N NaOH. The mixture is reacted in a water bath at 70°C for 3 hours. The mixture is removed from...
Claims
1. A polyquaternium-1 uptake rate of less than 0.40 micrograms / lens; The contact lens was placed in a lens holder with the circumferential area around the center of the contact lens exposed, and the lens holder was lowered onto the opposing surface. 49 kPa was applied to the contact lens at 47 mm. 2 and holding for 20 abrasions at a frequency of 75 cycles per minute with a total travel of 3 inches per stroke and 6 inches per cycle, said counter surface being a quarter inch thick sheet of silicone rubber clipped onto a reservoir filled with PBS. A contact lens having a water disintegration time of at least 10 seconds after being treated according to the technique, the contact lens comprises an anterior surface and an opposite posterior surface, and a layered structural configuration comprising, in a direction from the anterior surface to the posterior surface, an anterior outer hydrogel layer, an inner layer of lens material, and a posterior outer hydrogel layer; the inner layer having a first equilibrium moisture content of less than or equal to 70 wt.%; the front and rear outer hydrogel layers, independently of one another, have a thickness of 0.25 μm to 25 μm when fully hydrated and a second equilibrium water content greater than the first equilibrium water content; A contact lens wherein said anterior and posterior outer hydrogel layers, independently of one another, have a water swelling rate of at least 140%.
2. A polyquaternium-1 uptake rate of less than 0.40 micrograms / lens; The contact lens was placed in a lens holder with the circumferential area around the center of the contact lens exposed, and the lens holder was lowered onto the opposing surface. 49 kPa was applied to the contact lens at 47 mm. 2 a controlled shear technique, applied to a contact lens area of 10 mm x 10 mm, held for 20 abrasions at a frequency of 75 cycles per minute, with 3 inches per stroke and 6 inches of total travel per cycle, said counter surface being a quarter inch thick sheet of silicone rubber clipped to a reservoir filled with PBS, and a water disintegration time of at least 10 seconds after being treated according to the technique; a water content gradient that increases from an interior side to one of an anterior or posterior surface of the contact lens, the contact lens comprises a lens bulk material completely covered with a front outer hydrogel layer and a rear outer hydrogel layer; said front and rear outer hydrogel layers, independently of one another, have a thickness of from 0.25 μm to 25 μm when fully hydrated; the lens bulk material having a first equilibrium water content of less than or equal to 70% by weight; A contact lens wherein said anterior and posterior outer hydrogel layers, independently of one another, have a second equilibrium water content that is at least 1.2 times said first equilibrium water content and is at least 80% by weight.
3. 3. The contact lens of claim 1, wherein the contact lens has a polyquaternium-1 uptake rate of 0.20 micrograms / lens or less.
4. The contact lens of any one of claims 1 to 3, wherein the contact lens has a water disintegration time of at least 15 seconds after being processed according to a controlled shear technique.
5. 5. The contact lens of claim 1, wherein the anterior and posterior outer hydrogel layers are crosslinked hydrophilic polymeric materials comprising at least 25 mol % repeating monomer units of at least one hydrophilic vinyl monomer selected from the group consisting of alkyl (meth)acrylamides, N-2-dimethylaminoethyl (meth)acrylamide, dimethylaminoethyl (meth)acrylate, hydroxyl-containing acrylic monomers, N-vinyl amide monomers, methylene-containing pyrrolidone monomers, (meth)acrylate monomers having C1-C4 alkoxyethoxy groups, vinyl ether monomers, allyl ether monomers, and combinations thereof, independently of one another.
6. The contact lens of any one of claims 1 to 4, wherein the anterior and posterior outer hydrogel layers are, independently of one another, crosslinked hydrophilic polymeric materials comprising at least 25 mole % repeating monomer units of at least one phosphorylcholine-containing vinyl monomer.
7. The contact lens of any one of claims 1 to 4, wherein the anterior and posterior outer hydrogel layers are, independently of each other, crosslinked hydrophilic polymeric materials comprising poly(ethylene glycol) chains.
8. 10. The contact lens of claim 1, wherein the anterior and posterior outer hydrogel layers are identical to one another, are substantially uniform in thickness, and merge at the edge of the contact lens to completely cover the inner layer.
9. The contact lens of any one of claims 1 to 8, wherein the anterior and posterior outer hydrogel layers, independently of one another, have an equilibrium water content of at least 80% by weight.
10. The contact lens of any one of claims 1 to 9, wherein the anterior and posterior outer hydrogel layers, independently of each other, are substantially free of silicone.
Citation Information
Patent Citations
Silicone hydrogel lenses with a surface that has a high moisture content
JP2013533517A
Multifocal bimodulus contact lenses
US20160334640A1
Method for producing contact lenses with durable lubricious coatings thereon
US20170068019A1